Structure and characteristics of quercetin-loaded starch nanoparticles and their surface charges for protein corona formation with gastrointestinal digestive enzymes - Yu-Ru Wu; Zhi-Yuan Yang; Shan-Dan Zhao; Dan-Yang Shen; Ya-Jun Lin; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2026)

From target identification to intervention: Tackling microbial contamination challenges in cultivated meat production using antimicrobial peptides - Zejia Lin; Yuan Guo; Dini Deng; Xianzhe Li; Emma Y.H. Koay; Mario P.S. Chin; Carrie K.Y. Chan; Dan Li (Food Microbiology, 2026)

Life history strategy composition of fishes in the Yangtze River Basin and their response to the Ten-Year Fishing Ban - Lan Zhu; Dan Yu; Pengcheng Lin; Fei Liu; Tao Chang; Xin Gao; Mingzheng Li; Huanzhang Liu (Reviews in Fish Biology and Fisheries, 2026)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Nitrogen availability mediates long-term warming effects on deep-soil dissolved organic matter concentration and composition in cropland - Xinhui Liu; Tim J. Clough; Dan Yuan; Jiao Yuan; Lin Ma; Chunsheng Hu; Wenxu Dong; Ping Wu; Shuping Qin; Oene Oenema (Agriculture, Ecosystems & Environment, 2026)

Neuroprotective effect of miR-519a-3p downregulation against sevoflurane-induced cognitive dysfunction via regulating ESR1 - Weiwei Lin; Dan Yu; Xiating Shi; Wanchao Liu (Toxicology and Applied Pharmacology, 2026)

Mesozoic crustal thinning in the northern North China Craton: Evidence from Triassic and Jurassic plutons in the Huyu area, northwestern Beijing - Liang Qiu; Dan-Ping Yan; Jun-Ting Qiu; Wei Yang; Yiyu Lin; Suhua Cheng; Xiuhua Cao; Xuchao Chai; Pei Zhang; Lei Gao; Zeyilin Ma (Journal of Asian Earth Sciences, 2026)

Transformation of crop structure intensified extreme drought shocks to prehistoric settlements: an integrated study of lacustrine sediments and environmental archaeology in southwestern China - Tao Wang; Duo Wu; Zehui Li; Qili Xiao; Dan Luo; Shilong Guo; Lili Pan; Lin Chen; Yongxiu Lu; Shuai Shao; Zijie Yuan; Peiyao Xu; et al. (Global and Planetary Change, 2026)

Association of structural characteristics with immunostimulatory activity of pectic polysaccharides prepared from Tartary buckwheat sprouts by enzymatic degradation and partial acid hydrolysis - Lin Zhang; Bo Li; Xuan Gao; Mao-Qing Wang; Ya-Nan Cao; Mao-Ling Tan; Yi-Chen Hu; Liang Zou; Dan Li; Yong Deng; Jing-Wei Huang; Ding-Tao Wu (Food Research International, 2026)

Contrasting impacts of biodegradable and conventional microplastics on heavy metal bioavailability in soils: A multilevel meta-analysis - Xue-Dan Cui; Zheng-Xiao Jiang; Yi-Hao Mei; Ting-Ting He; Xiao Tan; Ai-Jun Lin; Gui-Lan Duan (Environmental Pollution, 2026)

Flexural performance and calculations of concrete-encased square concrete-filled steel tubular (CFST) hybrid structures - Dan-Yang Ma; Jie Gong; Lin-Hai Han; Long-Hui Du (Engineering Structures, 2026)

Defect-engineered Cu-TCPP/ZIF-L nanosheet-modified PVDF membrane with enhanced water purification and dye removal performance - Yiming Zhao; Jingyuan Zhang; Junmei Liu; Jiatong Han; Dan Xu; Jing Wang; Fengzhi Lyu; Lin Qin; Donghui Xu; Ge Chen; Guangyang Liu (Chemical Engineering Journal, 2026)

Mitigation of antibiotic resistance risk in aerobic sludge by zero-valent iron: From pathogen reduction to conjugation inhibition and network weakening - Ying Wu; Lin Zhu; Guoping Lin; Xuezhu Han; Jingpeng Li; Jiaming Yi; Dan Huang; Meizhen Wang (Bioresource Technology, 2026)

Fabrication of microwave-absorbing MFe2O4@sepiolite (M = Mn, Mn0.5Ni0.5, Ni) nanorods with enhanced catalytic performance for degradation and assessment of intermediate toxicity - Ruolin Ni; Lei Jiang; Jinhui Lin; Dan Wu; Keming Zhang; Lu Fu; Zhaohong Zhang; Fang Ma; Yongcai Zhang (Applied Clay Science, 2026)

Lactiplantibacillus plantarum LP15-1 alleviates deoxynivalenol-induced intestinal injury in mice by inhibiting ferroptosis and modulating the gut microbiota - Kunru Teng; Jiefeng Li; Beibei He; Dan Song; Tao Duan; Kuanbo Liu; Lin Qiao; Aike Li; Weiwei Wang; Shijie Fan (Toxicon, 2026)

Structure and bioactivity of protolimonoids from the root bark of Dictamnus dasycarpus Turcz. - Hua Yue; Zi-Xuan Li; Zi-Tong Hao; Dan Zeng; Jie Bao; Ling-Zhi Zhang; Xue-Man Lin; Hua Sun; Shu-Fang Li; Su-Juan Wang (Phytochemistry, 2026)

Pollution prediction of heating boiler plants based on data preprocessing and CNN-LSTM-attention model - Zhengda Lin; Jifeng Wang; Bingjie Yan; Zhe Fu; Liyan Liu; Dan Zhong; Xingwei Du; Jun Zhang (Journal of Environmental Chemical Engineering, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Process-dependent structural and functional modification of yeast protein: Alkaline extraction-acid precipitation versus high-pressure homogenization-assisted pH shifting - Lin Li; Xiaoyu Ma; Dan Huang; Ming Du; Shuo Wan; Shuzhen Cheng (Food Chemistry, 2026)

W1/O/W2 emulsion stabilized by β-lactoglobulin/exopolysaccharides/epigallocatechin gallate complex: Protective effects on Lactobacillus plantarum A81 during storage, pasteurization and gastrointestinal digestion - Cuicui Duan; Yi Zhang; Hongru Wang; Siyang Sui; Hui Liu; Cheng Wu; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Chemistry, 2026)

Fermentation of ginseng juice by Lactiplantibacillus plantarum SP055 and Limosilactobacillus fermentum LB-9: Fermentation characteristics and ginsenoside biotransformation pathways - Jianwei Zang; Wei Liu; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Yimeng Kou; Chunling Meng; Jiamin Xu; Tao Lin; Xin Rui; Dan Gan; et al. (Food Microbiology, 2026)

Microplastics as pathway-selective modulators rewire nitrogen cycling in coastal wetlands: Polymer identity outweighs concentration - Dan Wang; Niu Li; Jining Shao; Xingna Lin; Youzheng Zhang; Wenting Cao; Xuexin Shao; Ming Wu (Environmental Pollution, 2026)

PFAS exposure is associated with retinal neurotoxicity in Chinese adolescents: Mechanistic insights from integrated toxicogenomic and in vitro analyses - Xing-Xuan Dong; Shi-Yi Gong; Yu-Hui Hu; Gang Liang; Hua Xu; Dan-Lin Li; Yun Zhao; Chen-Wei Pan (Environmental Pollution, 2026)

Element substitution engineering of Li3VO4: Exposing high-activity (110) facets for stable interface and superior lithium storage - Huan Liu; Zhaozhao Han; Honglei Zhao; Andong Lin; Dan Zhang; Huaifang Zhang; Jianchuan Wang; Yuanyuan Feng (Chemical Engineering Journal, 2026)

Microbial mechanisms of sulfamethoxazole biodegradation at bio-anode elucidated by integrated metagenomics and stable-isotope probing - Hongli Lu; Hui Lin; Da Kang; Donglin Wang; Qiaojuan Wang; Jie Mao; Dan Cui; Yaohui Bai; Jiuhui Qu; Yongzhen Peng (Chemical Engineering Journal, 2026)

Overcoming bacterial fouling: Self-cleaning CNTs-PEI/Cu-ZnIn2S4 membranes for sustained water disinfection - Yuan Gao; Jiaqi Sun; Pei-Lin Gao; Qi Zhao; Xinyi Yu; Yujie Song; Jun Hu; Dan Wang; Zhi-Gang Shen; Ze-Hai Xu; Hua Sheng; Zhong-Ting Hu (Chemical Engineering Journal, 2026)

Hyaluronic acid-based core-shell microneedles for staged local delivery of psoralen toward anti-inflammatory and cartilage-protective therapy of rheumatoid arthritis - Qihui Lin; Zijian Yan; Qiangyu Chen; Yongan Lin; Dan Ying; Zhuhao Tan; Zheng Liu; Mengxing Lu; Wenjing Song; Li Ren (Carbohydrate Polymers, 2026)

Heterologous expression of anaerobic reductive dehalogenases: host nanoarchitectonics and synthetic biology optimization - Yashi Lin; Wenxi Yang; Qianwei Tang; Juan Yin; Dan Yang; Yaqing Liu (Bioresource Technology, 2026)

Stage-dependent roles of Trichoderma longibrachiatum and manganese sulfate in humification and nitrogen conservation during chicken manure composting - Yuchen Yang; Shuzhen Fan; Dan Zhang; Pan Wu; Shuang Peng; Qingqing Hua; Beibei Zhou; Yiming Wang; Xiangui Lin (Bioresource Technology, 2026)

Antagonistic effects of PM2.5 and ozone on respiratory morbidity: A multi-pollutant interaction analysis using outpatient data from China's Pearl River Delta - Shui-Yue Lu; Xue-Dan Xu; Dao-Qin Wang; Muhammad Amjad; Guang-Hui Dong; Li-Zi Lin; Hong-Wei Tu (Atmospheric Environment, 2026)

Substrate characteristics controls fungal denitrification and nitrous oxide emissions in an acidic upland soil - Guiping Ye; Zongsheng Yuan; Konglin Zhou; Chen Liang; Dan Wang; Wenbin Zhang; Luyuan Sun; Xiangying Wei; Yongxin Lin (Applied Soil Ecology, 2026)

The influence of replacing soybean meal with corn gluten meal on the digestive and absorptive capacity and amino acid metabolism of sub-adult grass carp (Ctenopharyngodon idella) - Yan Liu; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Wen-Jie Tang; Cheng-Bo Zhong; Pei Wu (Aquaculture, 2026)

In vitro assessment of the osteotoxic potential of diuron in human BMSCs - Yiwei Xie; Zixuan Chen; Xiaohui Wu; Lin Du; Zhibao Chen; Dan Fang; Jiangming Yu (Toxicology and Applied Pharmacology, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Soil organic carbon, soil heterotrophic respiration, and microbial community assembly in response to vegetation restoration in the karst area of Southwest China - Tongqing Su; Geng Lin; Dan Chen; Tingting Cui; Jianbing Zhang; Weiqun Luo; Baoqing Hu (Pedobiologia, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

Reannotation of the ABCC transporters reveals a miR-980-BdABCC1 regulatory axis driving avermectin tolerance in Bactrocera dorsalis - Hou-Ji Song; Lin Wang; Wei Zhao; Guy Smagghe; Jin-Jun Wang; Dan-Dan Wei (Insect Biochemistry and Molecular Biology, 2026)

Universal deep learning strategy leveraging peptide atomic 3D structural information identifies diverse bioactive peptides from wheat germ protein hydrolysates - Like Lin; Dan Xiao; Wei Song; Weihong Lu (Food Chemistry, 2026)

Nanoconfined humic acid-supported nZVI enhances imidacloprid remediation without compromising soil microbiome or exacerbating ARG health risks - Na Li; Jiaming Yi; Lin Zhu; Du Chen; Meizhen Wang; Dan Huang (Environmental Research, 2026)

The oxidative potential of PM2.5 outperforms its mass concentration in association with childhood sleep disorders: Evidence from a large-scale study in China - Yun-Hui Shao; Dan Cai; Qian Yao; Xi-Hua Lin; Jin-Shan Ge; Lu-Yin Wu; Yun-Jiang Yu; Guang-Hui Dong; She-Xia Ma (Environmental Pollution, 2026)

Spatial patterns and ecological transition potential of high-abandonment-risk cropland in China: A MaxEnt-based assessment - Dan Lu; Zhanpeng Wang; Yuqing Zhu; Hongbo Zhao; Jingjing Liu; Haipeng Zhang; Aiwen Lin (Environmental Impact Assessment Review, 2026)

Information flow reveals three-tiered oceanic drivers of precipitation over the middle–lower Yangtze River Basin - Li-Ying Ning; Dan Wu; Ying Qu; Guo-Lin Feng; Yong-Ping Wu (Climate Dynamics, 2026)

Effects of dietary genistein supplementation in oxidized fish oil feed on growth performance, hepatic lipid metabolism, and intestinal health of juvenile turbots (Scophthalmus maximus L.) - Xiaoqian Zhou; Lin Yang; Junfeng Hu; Yu Gong; Xin Xiao; Zhijie Dan (Animal Feed Science and Technology, 2026)

Retraction notice to “Scenario analysis on optimal farmed-fish-species composition in China: A tentative theoretical methodology to benefit wild-fishery stock, water conservation, economic and protein outputs under the context of climate change” [Sci. Total Environ. 806 (2022) 150600] - Guobao Song; Xinyue Zhao; Lin Lv; Qi Yuan; Yongchi Ma; Laura Batlle Bayer; Dan Zhang; Pere Fullana-i-Palmer (Science of The Total Environment, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Preparation of a MOF-derived Mn-Ti catalyst and its simultaneous removal of NOx and toluene: Strong metal-support interaction and Lewis acid sites - Yongchao Zhong; Dan He; Qiangwei Lu; Lu Wang; Yunkuo Luo; Dongliang Zhang; Chaochao Li; Lin Li; Fengying Li; Xiang Tu; Chenglong Yu (Journal of Environmental Chemical Engineering, 2026)

Effects of different processing methods on bioaccessibility of phenolic compounds in flaxseed meal - Lin Cheng; Mengjiao Zhao; Hongtao Guo; Yongxia Cheng; Yue Shen; Dan Hai; Lianjun Song; Yinping Wang; Guangshan Zhao; Xianqing Huang; Yan Ma (Food Chemistry, 2026)

Insights into the molecular basis of umami in premium green teas via integrated metabolomics, peptidomics, and in silico molecular docking - Jiaqi Yang; Shitao Fang; Qi Zhou; Yizhi Wang; Kangni Yan; Peng Qunhua; Lin Zhi; Wu Yan; Fu Jianyu; Mu Dan; Lv Haipeng; Shi Jiang (Food Chemistry, 2026)

Ecotoxicity of single silver nanoparticles and combined silver nanoparticles and humic acid on Limnobium laevigatum - Dan Zhang; Zhen Lin; Zhonghua Wu (Environmental Pollution, 2026)

Integration of local climatic factors and global climate oscillations for enhanced monthly precipitation forecasting in the Asian monsoon region - Congcong Li; Lulu He; Lin Luo; Dan Liu; Junxia Liao (Theoretical and Applied Climatology, 2026)

Infection risks associated with b/tsDMARDs in rheumatoid arthritis: a systematic review and network meta-analysis - Xue-Mei Zhang; Li Liu; Yi-Dan Yan; Zai-Li Zhang; Ke-Jia Le; Yang-Xi Liu; Xiao-Jun Ni; Liang-Jing Lu; Guo-Hua Zhou; Zhi-Chun Gu; Jia Li; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2026)

Critical Role of Mid-Tropospheric Southwesterly Steering in a Failed Extreme Rainfall Simulation over Northeastern Qinghai–Xizang Plateau - Wei Si; Duming Gao; Xingwen Jiang; Peng Fan; Qing Zheng; Yong Feng; Zhiwei Heng; Dan Lin (Journal of Meteorological Research, 2026)

Linking Pore Structure Parameters with Coal Strength and Initial Gas Desorption for Outburst Risk Identification: A Preliminary, Region-Specific Threshold Framework - Hongkun Wang; Lin Hong; Dameng Gao; Dan Zheng; Ye Zhang (Rock Mechanics and Rock Engineering, 2026)

Study on Fertility and Genetic Diversity of Introduced Sugar Beet Germplasm Resource FC220 - Shi-Kun Zhang; Ya-Dan Xiao; Lin Liao; Ze-Dong Wu; Lin-Lin Sun (Sugar Tech, 2026)

Construction of a process-driven 3D spatio-temporal model for precision soil remediation: Coupling dynamic retention with multi-objective cost optimization - Zhengda Lin; Bingjie Yan; Xinhao Sun; Caoqingqing Li; Liyan Liu; Dan Zhong; Jun Zhang (Process Safety and Environmental Protection, 2026)

A versatile colorimetric array sensor based on FeCu-based prussian blue analogue heterostructures for efficient discrimination of tetracycline antibiotics and rapid identification of urinary tract infection pathogens - Dan Wu; Xin-Yu Cheng; Chao-Man Wang; Ya-Nan Kong; Shu-Chang Zhao; Rui-Lin Liu (Journal of Hazardous Materials, 2026)

Interfacial heterogeneous electro-Fenton membrane distillation for risk-controlled concentration of high-salinity coal-chemical wastewater - Hongxin Liu; Kuiling Li; Lin Fang; Yang Yao; Zhigang Dan; Jun Wang (Journal of Environmental Sciences, 2026)

New insights into pubertal onset: Exploring the impact of low-calorie sweeteners exposure in school-aged children - Qin Zhou; Yao Lu; Xiao-Ya Lin; Shi-Jian Liu; Dan Wang; Ying-Jie Zhang; Ying Guo (Journal of Environmental Sciences, 2026)

Chronic chlorpyrifos exposure induced depression and anxiety by gut microbiota alterations combined with metabolic disorders of ammonia and quinolinate - Jiahao Yuan; Akang Dan; Peisi Xie; Jing Chen; Zian Lin; Zongwei Cai (Journal of Environmental Sciences, 2026)

Thunderstorm activity over Fujian and Vicinity: Insights from thunderstorm tracking technology - Biao Zhu; Binbin Lin; Tingting Chen; Dan Li; Bo Pang; Hengyi Liu (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Study on the characteristics of W1/O/W2 emulsion delivery system stabilized by soybean protein isolate/(−)-epigallocatechin gallate/exopolysaccharides complex - Cuicui Duan; Cheng Wu; Hui Liu; Siyang Sui; Hongru Wang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Research International, 2026)

A tropical fermented-food-derived Lactiplantibacillus plantarum SP055 alleviates DSS-induced colitis through coordinated regulation of gut microbiota and intestinal barrier function - Jianwei Zang; Yibo Shi; Xiaotong Hao; Xia Fan; Yimeng Kou; Wanxiang Zhang; Luyao Xiao; Chang Xu; Tao Lin; Xin Rui; Dan Gan; Wei Li (Food Bioscience, 2026)

Experimental behaviour of concrete-encased square concrete-filled steel tubular (CFST) hybrid structure subjected to axial compression - Dan-Yang Ma; Long-Hui Du; Lin-Hai Han (Engineering Structures, 2026)

Ultrastable Pt clusters confined on CeO2 nano-islands for efficient low-temperature propane dehydrogenation over carbon nanotube - Jian Tao; Shu-Lin Liu; Zi-Dan Li; Wan-Yi Wang; Chuan-Feng Huang; Bao-Lian Su; Zhao Wang (Chemical Engineering Journal, 2026)

Graphitization-driven interfacial polarization and conductivity in core–shell Fe3O4@hydrochar composites achieving high-performance electromagnetic wave absorption - Lin Wang; Yingshan Deng; Zurong Zhu; Dan Michelle Wang; Dafu Chen; Guanghui Bai; Zhongyi Feng; Yao Han; Yueyao Liu; Jinxia Zhai; Chengyun Ning; Zhengao Wang (Chemical Engineering Journal, 2026)

Probabilistic predictions of the impacts of climate warming on permafrost stability along the Qinghai-Xizang Railway, China - Chengsong Yang; Guodong Cheng; Wei Wei; Lin Chen; Wenqiang Zhang; Xinbin Wang; Qihao Yu; Dan Wang (Cold Regions Science and Technology, 2026)

Comparative analysis of chemical compositional profiles and immunomodulatory activity of ginseng in different habitats - Chen-Yue Zeng; Quan-Kuan Dai; Hua-Ze Wu; Ao Li; Yong-Lin Chen; Qing-Hui He; Dan Tang; Hong-Yan Ma (Journal of Natural Medicines, 2026)

Environmental Factors Drive Neurodegenerative Diseases Through Glutamate Excitotoxicity: A Convergent Mechanistic Pathway - Yulu He; Tingting Yi; Meixin Min; Ke Xu; Huan Lin; Rong Xu; Dan Deng; Xiaoping Xiao (Neuroscience Bulletin, 2026)

Petrogenesis of Late Triassic adakitic rocks and basalts from the southern Lhasa: Insights into subduction initiation of Neo-Tethys - Cheng Li; Lin Ma; Andrew C. Kerr; Wei Dan; Qiang Wang; Zhiwei Yu; Wei Qiao; Rui Pu; Fan Yang (Lithos, 2026)

Association of dietary intake of copper and zinc with systemic inflammation: A cross-sectional study integrating machine learning - Xuefei Zhang; Yuqing Deng; Huan Su; Xueran Huang; Yongfen Gao; Zhuangzhuang An; Zouyan He; Dan Li; Haiying Zhang; Rui Lin (Journal of Trace Elements in Medicine and Biology, 2026)

Engineering Mn-confined Fe0-carbon with isolated oxygen-containing groups breaks the bottleneck for concurrent self-driven Fenton degradation of antibiotics and heavy metals immobilization - Yujiang Huang; Dan Liu; Zhouyang Shi; Tong Hu; Huiwang Dai; Sicheng Pan; Wenjun Zhou; Fei Ge; Daohui Lin; Lizhong Zhu (Journal of Hazardous Materials, 2026)

Mechanistic insights into efficient phenol degradation mediated by anodic respiration in Acinetobacter sp. LA-1 - Binxin Liu; Jingyi Yu; Rongsheng Lin; Wendong Xian; Dan Luo; Li Chen; Jianxin Wang; Wenhui Wang; Qingqing Zhang; Peng Li (Journal of Hazardous Materials, 2026)

Static magnetic field-assisted fermentation of corn dietary fiber by Hericium erinaceus: Insight into fermentation mechanisms and related characteristics - He Ban; Jingwei Wang; Ding Xu; Xiangmeng Yin; Wei Li; Lin Xiu; Dan Cai; Jingsheng Liu (Food Chemistry, 2026)

Groundwater flow estimation from energy pile thermal responses: A case study from laboratory experiments to field testing - Haoyu Wang; Dan Zhang; Bo Yang; Kai Lin; Zhuoqun Xu (Engineering Geology, 2026)

Ameliorating ischemic stroke by systematically screening natural polyphenols to counteract the dual effects of AMPK activation in microglia - Jingwei Liu; Jian Wang; Huan Liu; Luyao Zhu; Kang Li; Qiangfei Su; Dan Luo; Tao Guo; Zheng Wang; Lin Wang (Chemical Engineering Journal, 2026)

Levan-derived oligosaccharides (LOS) prime barley against fungal pathogens through asparagine metabolism - Dan Lian; Yanjing Li; Jiaxin Ma; Junjie Zhou; Yitong Xia; Mengyuan Yang; Ruiming Lin; Huiquan Shen; Li Xu; Huijuan Zhang; Jingjing Xu; Wei Wu; et al. (Carbohydrate Polymers, 2026)

A T4SS effector directly disarms competing antibacterial T6SSs by hijacking their conserved spike component - Dan Xiong; Jinxing Liao; Zhiyuan Zhang; Julien F. Giraud; Xiuyuan Li; Dongjing Cheng; Bingxin Wang; Limin Wang; Xiaolong Shao; Long Lin; Jinshui Zheng; Xiangyang Li; et al. (Science China Life Sciences, 2026)

DynamicDTA: Drug-Target Binding Affinity Prediction Using Dynamic Descriptors and Graph Representation - Dan Luo; Jinyu Zhou; Le Xu; Sisi Yuan; Xuan Lin (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Description of a new cyprinid gudgeon, Saurogobio rarus sp. nov., found in central and northeastern China, with comments on its population status - Yahan Wu; Dan Yu; Lin Chen; Mingzheng Li; Huanzhang Liu (Journal of Fish Biology, 2026)
A new cyprinid gudgeon, Saurogobio rarus sp. nov., is described here based on morphological and molecular data. Morphologically, the new species resembles its congener S. dabryi the most, but with distinct differences. S. rarus sp. nov. has the naked area on chest restricted to or a little over the pectoral‐fin base, as opposed to extending much over the pectoral base or extending to posterior portion of the pectoral fin rays in S. dabryi . Besides, S. rarus sp. nov. has a relatively shorter snout, shorter and deeper caudal peduncle and a shorter distance between the anus and the pelvic‐fin base, compared with S. dabryi . The new species can be distinguished from other congeners by having eight branched dorsal‐fin rays, thick lips with numerous globular papillae and the absence of fin spots. Phylogenetically, based on cytb sequence analyses, S. rarus sp. nov. is clearly separated from all congeners, with a mean genetic distance from 0.022 to S. dabryi , exceeding the mean intraspecific distance of 0.012 observed within S. dabryi . At present, this new species has been found only in Central (Poyang Lake) and Northeastern China (Ussuri River and Songhua River). Based on our recent surveys, its abundance is becoming lower and lower, and calls for urgent conservation.

L-arginine enhances skeletal muscle energy metabolism and maintains mitochondrial homeostasis to promote locomotor function in zebrafish embryos - Qiu-Yan Chen; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2026)

Hydroxytyrosol preserves myofibrillar protein integrity in grass carp (Ctenopharyngodon idella): Implications for flesh quality enhancement - Yi-Wei Liao; Pei Wu; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

Hollow-structured covalent organic framework nanocapsules enable sustained benzaldehyde release for antimicrobial preservation of postharvest peach fruit - Dan Jiang; Yuting Ma; Xubin Wu; Zhihao Li; Siyin Lin; Kunsong Chen; Jian Wu; Ke Zhu; Pingwei Liu; Bo Zhang (Postharvest Biology and Technology, 2026)

Triphenyl phosphate exposure at physiologically/environmentally relevant concentrations promotes malignant progression of breast cancer: Insights from metabolomics and lipidomics - Akang Dan; Ying Sun; Zhi Ye; Juan Lin; Zian Lin; Zongwei Cai (Journal of Hazardous Materials, 2026)

Sustainable multifunctional packaging films based on chitosan and food waste-derived carbon nanodots for fruit preservation - Ying Ren; Dan Chen; Shiyu Lin; Xiaoping Fan; Liming Cao (Journal of Food Engineering, 2026)

Static magnetic field assists corn germination: Changes in nutritional composition and improvement of functional properties - Xin Jiang; Yelinxin Chen; Xiaoxi Yu; Jingwei Wang; Ding Xu; Huimin Liu; Dan Cai; Lin Xiu; Jingsheng Liu (Food Chemistry, 2026)

Dehydroepiandrosterone activates ADGRG2 to regulate chloride homeostasis and sperm motility via Gs-cAMP pathways - Dan Jiang; Ji-Fei Han; Xian-Zheng Guo; Yu-Qi Ping; Fan Yang; Peng Xiao; Jin-Peng Sun; Xiao Yu; Zhao Yang; Hui Lin (Science China Life Sciences, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Discovery and engineering of a new BvCas12a nuclease for mammalian genome editing and nucleic acid detection - Xuechun Shen; Lei Huang; Dan Wang; Chen Qi; Baitao Li; Chuan Liu; Ke Chen; Yuanqiang Zou; Liang Xiao; Yuan Jiang; Qiupeng Lin; Hongxia Lan; et al. (Science China Life Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

The E3 ubiquitin ligase MIEL1 promotes thermo-responsive growth by blocking auto-ubiquitination and self-degradation of XBAT31 - Lin-Lin Zhang; Qiang-Hua Zhou; Zhi-Ping Deng; Juan Gao; Hui-Dan Luo; Ying-Ying Tian; Jian-Xiang Liu (Science Bulletin, 2026)

A hybrid spatial framework for risk mapping and driving factor diagnosis of soil combined contamination in Guangzhou - Lian Chen; Zhenjiang Wang; Lingyun Sun; Zhipeng Wu; Sen Lin; Dan Wang; Jianan Wu; Zhiyi Li; Gaocong Li (Journal of Geochemical Exploration, 2026)

High-value utilization of chromium ore processing residue (COPR) through corn straw-soda roasting followed leaching processes - Cheng Tian; Zilong Li; Cunfang Lu; Rui Xu; Min Zhang; Lin Yang; Wenlin Xie; Zhengnan Zhong; Yuanyuan He; Juan Wen; Dan Luo (Journal of Environmental Chemical Engineering, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Review: Synergistic effects of environmental pollutants: Multiple stressors driving the transmission of vector-borne diseases and the vicious cycle - Tingting Liu; Jia Wang; Minghao Yu; Yining Li; Huan Lin; Dan Deng; Xiaolu Shi; Xiaoping Xiao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

PCA: A tFNA-based targeted nucleic acid nanocomposite hydrogel for the treatment of androgenetic alopecia through the promotion of angiogenesis and hair follicle stem cell proliferation - Dan Zhao; Meiying Shao; Yunfeng Lin (Chemical Engineering Journal, 2026)

Extracellular vesicles in cancer progression: mechanisms and significance - Ying Gao; Denghui Wei; Li Zhong; Dan Liao; Xueping Zheng; Yujie Lin; Dongmei Fang; Boyang Chang; Tiebang Kang (Science China Life Sciences, 2026)

Pressure-Driven Pore Structure Evolution in Coal: Insights from Low-Field NMR - Lin Hong; Hongkun Wang; Dan Zheng; Dameng Gao (Rock Mechanics and Rock Engineering, 2026)

Effects of Lactobacillus Acidophilus Mediated Improvement of Intestinal Barrier in Mice with Autism - Yong Song; Jia Shi; XiaoYi Fu; Dan Fu; Li Xu; WeiMei Liu; JingJing Cao; YaoCheng Ding; ShuPeng Huang; Lin Zhou; Kai Qian (Probiotics and Antimicrobial Proteins, 2026)

Grass mulching optimizes microbial communities and enhances carbon nitrogen cycling in peach orchard soils across slope positions - Chengyi Huang; Caiyun Lu; Huijuan Huang; Hongbin Zhang; Liu Yang; Yian Chen; Lijin Lin; Kairui Zhang; Wenjie Liu; Dan Zhu; Hongping Li; Shou Yan (Nutrient Cycling in Agroecosystems, 2026)

Drought, Conflict and the Use of Historical Data and Methodologies in Interdisciplinary Palaeoclimatic Research - Helen Foxhall Forbes; Mateusz Fafinski; Guy Halsall; James M. Harland; Dan Lawrence; Kelly Clarke-Neish; Lin Foxhall; Michele Abballe; Massimiliano Borroni; Ismini Lypiridou; Vicky Manolopoulou; Anastasia Nikulina; et al. (Climatic Change, 2026)
A major challenge in the interdisciplinary study of past climates is ensuring that evidence and data relating to different disciplines are analysed effectively using appropriate methodologies. In ‘Droughts and conflict during the late Roman period’, Clim. Chang 178, 2025, Norman et al. argue that historical sources support their conclusions that drought contributed causally to the ‘barbarian conspiracy’ of 367CE and to other late Roman conflicts. Although historians have developed rigorous methodologies for effective analysis and interpretation of surviving texts, the authors outline no methodologies for dealing with the textual evidence. Further, there are issues with the historical ‘conflict’ and numismatic datasets and with their interpretation. We focus on four major evidential points: 1) the ‘barbarian conspiracy’, 2) the agricultural economy; 3) the ‘conflict’ dataset and 4) the coin dataset. Historical evidence relating to drought and famine in the late Roman Empire does exist: future interdisciplinary research may indeed offer interesting observations on the relationships between drought and conflict, but the textual evidence discussed by Norman et al. does not, and cannot, support the authors’ assertions. Effective interdisciplinary research must allow all disciplines to engage on their own terms and with their own accepted standards of rigour.

Identifying trend reversals in atmospheric ethane from a multi-site analysis - Marina Friedrich; Siem Jan Koopman; Yicong Lin; Emmanuel Mahieu; Stephan Smeekes; Martine De Mazière; Victoria Flood; Matthias Max Frey; Michel Grutter; James W. Hannigan; Frank Hase; Nicholas Jones; et al. (Climatic Change, 2026)
Ethane is the most abundant non-methane hydrocarbon in Earth’s atmosphere and acts as an indirect greenhouse gas, influencing the atmospheric lifetime of methane. Therefore, understanding the development of trends and identifying trend reversals in atmospheric ethane is crucial. Ethane abundance is measured at different ground-based stations worldwide using Fourier transform infrared remote sensing techniques. We compile a new dataset comprising 26 ethane time series from the Northern and Southern Hemispheres. We analyze their long-term trends using different econometric techniques capable of handling missing data and strong seasonal components present in the data. The resulting trend patterns are consistent across the different methods, with similar estimated trends at the various stations. In the Northern Hemisphere, the common trend across stations declined from the 1990s to 2005, gradually increased over the next decade, and then resumed a similar downward trajectory from 2015 onward. The estimated trends reveal a pronounced peak around 2014/2015, marking a reversal from an upward to a downward trend.

The presence of native semi-fossorial herbivores enhances the coupling between species and functional diversity in alpine meadows - Yuan Yuan Duan; Kun Qin; Yu Chen; Jie Li; Ni Wang; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Agriculture, Ecosystems & Environment, 2026)

Increased Soil Carbon and Nitrogen Stocks Associate With Stronger Calcium–Microbial and Multi‐Trophic Interactions Under Warming - Dan Xiao; Wei Zhang; David R. Johnson; Peilei Hu; Lin Xu; Mingming Sun; Li Tang; Xunyang He; Jie Zhao; Xionghui Liao; Wanxia Peng; Hongsong Chen; et al. (Global Change Biology, 2026)
Converting cropland to planted forests improves soil organic carbon (SOC) and total nitrogen (TN) storage while contributing to climate change mitigation, primarily through the regulation of belowground organisms and mineral protection such as calcium (Ca). However, the mechanistic pathways linking exchangeable Ca 2+ , soil micro‐food web interactions, and nutrient accumulation under warming remain unclear. Here, we investigated their potential roles in driving the accumulation of mineral‐associated organic matter (MAOM), SOC, and TN in planted forests compared with croplands under warming conditions. Planted forests exhibited higher MAOM, SOC, and TN than cropland and had stronger coupling between carbon and nitrogen. Warming increased MAOM, SOC, and TN in planted forests but reduced SOC in cropland. Compared to cropland, planted forests displayed elevated levels of soil exchangeable Ca 2+ , microbial necromass carbon and nitrogen, stronger Ca–microbial and multi‐trophic associations. Warming further amplified positive Ca–microbial (e.g., bacteria and fungi) and cross‐trophic associations (e.g., nematode–bacteria, nematode–fungi, nematode–protist, and omnivore‐predator–bacteria/fungi) in planted forests by increasing plant productivity, litter biomass, and soil exchangeable Ca 2+ , whereas cropland showed limited responsiveness to temperature changes. In planted forests, soil exchangeable Ca 2+ was positively correlated with Ca–microbial and cross‐trophic associations, microbial necromass carbon and nitrogen, and the contents of MAOM, SOC, and TN. These relationships were absent in cropland. Notably, cross‐trophic associations rather than microbial abundance or diversity, with significant modulation by soil exchangeable Ca 2+ , had the strongest positive relationship with MAOM, SOC, and TN accumulation in planted forests. Collectively, our findings lead to the hypothesis that warming promotes SOC and TN storage in planted forests by jointly strengthening exchangeable Ca 2+ , Ca–microbial and cross‐trophic interactions. These results highlight the potential importance of multi‐trophic interactions and Ca‐mediated processes in stabilizing microbial necromass and fostering carbon and nitrogen preservation during vegetation restoration in response to warming.

Assessment of Health Risk from Aconiti Kusnezoffii Radix to its Processed Products and Origin Traceability Through Inorganic Element Analysis - Dan Yang; Yiwu Wang; Yuan Shen; Jialing Yu; Lin Yang; Dan He (Biological Trace Element Research, 2026)

Vitamin K is involved in liver protection and repair: Mitigating hepatotoxicity induced by the nitrite environment in grass carp (Ctenopharyngodon idella) by modulating Golgi function, hepatic stellate cells and mitochondrial dynamics - Jian-Fei Wang; Wei-Dan Jiang; Pei Wu; Yao-Bin Ma; Hong-Yun Zhang; Yang Liu; Lu Zhang; Hai-Feng Mi; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Synergistic recovering Fe, Al and biochar through biomass-reduction alkali roasting and wet magnetic separation for red mud (RM): behavior and mechanism - Rui Xu; Cunfang Lu; Min Zhang; Cheng Tian; Dan Luo; Lin Yang; Wenlin Xie; Zhengnan Zhong; Juan Wen (Minerals Engineering, 2026)

Spatiotemporal variations of chlorinated polycyclic aromatic hydrocarbons in Yellow Sea sediments: An eight-year field monitoring study - Xin Yang; Yunyong She; Qian Zhao; Dan Xu; Shenjie Li; Yueyao Yang; Guohua Zhu; Zhefu Yu; Junpeng Li; Bingcheng Lin; Minghui Zheng; Rong Jin (Journal of Hazardous Materials, 2026)

Dietary silymarin improves gut–liver health by enhancing intestinal barrier integrity and modulating TLR4/NF-κB and NLRP3-mediated inflammatory responses in Aeromonas hydrophila–infected grass carp - Feng Jia; Li Wei; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Hong-Yun Zhang; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Coated ferrous sulfate requirement for alleviating hypoxia-induced hepatopancreatic inflammation in sub-adult grass carp (Ctenopharyngodon idella) - Yu-Juan Yang; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Hong-Yun Zhang; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Ying-Gu Kuang; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Brazide: A breakthrough plant growth regulator that delays leaf senescence under heat stress to promote grain yield in winter wheat (Triticum aestivum L.) - Xingyu Zhong; Qihua Wu; Le Yang; Ziqing Lin; Dan Ren; Zhaohu Li; Yuyi Zhou; Liusheng Duan (Field Crops Research, 2026)

High-throughput microdroplet screening system based on surface-enhanced Raman spectroscopy for development of high-producing organic acid strains - Jianing Li; Iqra Rustam; Shanquan Liang; Wenwei Li; Fanzhen Lin; Zeyang Zhu; Li Chen; Qinhong Wang; Dan Wang (Bioresource Technology, 2026)

Differences in mAb Galactosylation Caused by the Leaching of Manganese Ions from Different Bioreactors - Xiaojing Liu; Guohong Qin; Jiaqi Mao; Guozhu Li; Chengying Tan; Shengnan Xu; Pan Wang; Xiaofei Wang; Yunfei Lin; Dan Xu (Pharmaceutical Research, 2026)

Mercury pollution at a typical ammunition production site in Northeast China: an integrated study on environmental behavior, risk assessment, and remediation strategies - Zhiyuan Wu; Tianxiang Xia; Dan Zhang; Lin Jia; Lina Zhang; Xiaoying Zhu; Shuang Li (Journal of Soils and Sediments, 2026)

Impact of Sea Buckthorn Fermented Microbial Fertilizer on Growth, Quality, and Rhizosphere Soil Environment of Red Quinoa (Chenopodium formosanum) Seedlings - Tianle Shen; Zhihao Yang; Yanbin Wang; Chai Lin; Xingqian Ye; Dan Wu (Journal of Soil Science and Plant Nutrition, 2026)

Dietary fraxetin modulates the gut-immune axis to alleviate DSS-induced enteritis in grass carp (Ctenopharyngodon idella) - Jie Zhang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; He-Qun Shi; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

Decontamination of volatile compounds from post-consumer recycled HDPE via supercritical CO2: Unravelling the critical role of co-solvent molecular structure - Ming-Yue Zhang; Qi-Zhi Su; Can Xu; Tian-Long Zhang; Huai-Ning Zhong; Qin-Bao Lin; Dan Li; Ben Dong (Waste Management, 2026)

Prediction on uplift displacement of tunnel induced by base grouting in soft clay - Jia-run Wu; Yu-liang Lin; Dan He; Ye Ma (Tunnelling and Underground Space Technology, 2026)

Intracellullar cholesterol accumulation caused by HBV induces ATF6-mediated endoplasmic reticulum stress to trigger endoplasmic reticulophagy - Yongxu Lin; Pingying Jiang; Weiqi Cai; Yongzhu Huang; Qiuyan Lin; Mingrong Wang; Fenglin Chen; Yuanlin Qi; Dan Li (Tissue and Cell, 2026)

Quinone-loaded biochar amplifies soil N2O mitigation by enhancing electron transfer for N2O reduction - Jiao Yuan; Dan Yuan; Tim J. Clough; Xinhui Liu; Lin Ma; Chunsheng Hu; Shuping Qin (Soil Biology and Biochemistry, 2026)

Pyrolysis of lime dried sewage sludge in a fixed-bed reactor: Effects of the addition amount of lime - Dan Lin; Wantong Kai; Xing Xie; Yusuf Makarfi Isa; Alexander Kozlov; Maxim Penzik; Shihong Zhang; Bin Li (Fuel, 2026)

A multi-stimuli-responsive supramolecular polymer from γ-Cyclodextrin and Viologen for dual-mode display and ammonia/amines sensing - Dong-Xue Xia; Chen-Yan Xu; Dan-Xuan Pan; Ming-Fu Ye; Rui-Lian Lin; Jing-Xin Liu (Chemical Engineering Journal, 2026)

"One-for-Two" dual-functional sodium percarbonate/α-MnO2/light strategy for water management: Ultrasensitive photoelectrochemical detection synergized with solar-driven advanced oxidation - Jia Zeng; Wei Ren; Yingxi Zhu; Die Gao; Xiaoxuan Li; Jiahao Lin; Zhou Li; Deng Li; Xiaodan Hu; Dan Li; Kezhi Liu; Jianming Wu; et al. (Chemical Engineering Journal, 2026)

Ternary deep eutectic solvents as multifunctional green solvents for lignocellulosic biomass pretreatment - Thenapakiam Sathasivam; Tingting Wu; Udyani Aloka Weerasinghe; Pek Yin Michelle Yew; Xin Lin Quek; Yi Jie Eng; Dan Kai (Bioresource Technology, 2026)

Assessment of dynamic drought risk and transition characteristics by combining an indicator-based approach and Markov chain model - Bin Huang; Tao Peng; Tianyi Fan; Vijay P. Singh; Xiaohua Dong; Qingxia Lin; Wenjuan Chang; Ji Liu; Yan Huang; Jiali Guo; Yinghai Li; Dan Yu (Natural Hazards, 2026)

Dynamic health risk assessment of chromium exposure in soil and groundwater at tannery sites: a Bayesian network perspective - Shan-shan Guo; Yu Wang; Yong qiang Tian; Hao Wu; Yang Li; Xiao dan Jin; Xin Li; Ze-lin Zhou; Han Zhang; Jin-yan Yang (Environmental Geochemistry and Health, 2026)

Cadzow Filtering Method Based on Adaptive Singular Value Decomposition - Zhong-lin Cao; Dan Wang; Peng-yuan Sun; Le Li; Ding-yu Xiong; Wen Yang; Yin-yu Wen; Jing Bai (Applied Geophysics, 2026)

Histidine deficiency-induced hepatic steatosis in teleost fish probably linked to the formimidoyltransferase cyclodeaminase - Xin Zeng; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

Architecting asymmetrical Janus membrane for robust membrane distillation desalination with enhanced anti-fouling performance - Caihong Liu; Xiyu Xu; Xu Lin; Xiao Wang; Xinran Guo; Qiang He; Dan Song; Haiqing Chang (Water Research, 2026)

Research progress on spike development of wheat - Yi Ding; Ying Zhang; Tengteng Zhang; Dan Zhao; Yufeng Yang; Kaiyue Wang; Ziqi Zheng; Chaoran Wang; Yongpeng Li; Runya Mao; Yifan Ye; Mengxue Li; et al. (Plant Science, 2026)

Acroeremophilanes A–I, eremophilane-type sesquiterpenoids from the Sinomenium acutum-derived symbiotic fungus Acrocalymma cycadis - Li-Bin Lin; Xue Cao; Wei Shi; Dan Shen; Mei-Niu Wang; Jing-Yu Wang; Jia-Hao Ning; Jia-Yao Hu; Dong-Zhu Duan; Xiao-Ling Wang; Jian Xiao (Phytochemistry, 2026)

Phylogenomics of an early-branching clade of Orthocladiinae (Diptera: Chironomidae) - Hai-Feng Xu; Zhi-Chao Zhang; Dan Zhang; Viktor Baranov; Chen-Hong Li; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Molten Li/Na/K ternary carbonate salt pyrolysis of biomass: A facile approach for co-production of porous biochar, CO-enriched syngas, and high-selectivity bio-oil - Jiazhen Tang; Tianyu Lu; Xing Xie; Dan Lin; Dongjing Liu; Qingfa Zhang; Mingfeng Wang; Weiwei Liu; Zhong Ma; Haiping Yang; Shihong Zhang; Bin Li (Journal of Cleaner Production, 2026)

Valuation of ecosystem services value based on dynamic equivalent factor in the Yangtze River Delta urban Agglomeration - Jiamin Xu; Lubing Li; Wenpeng Lin; Dan Xu; Qinping Yu; Yi Xiong; Yiwen Shi (Journal for Nature Conservation, 2026)

Dietary chromium picolinate alleviates hypoxia-induced liver inflammation in juvenile grass carp (Ctenopharyngodon idella): Involving the synergistic regulation of ion homeostasis and mitochondrial DNA integrity - Chuan-Shuai Xiong; Lin Feng; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Hong-Yun Zhang; Jun Jiang; Xiao-Qiu Zhou; Pei Wu (Fish & Shellfish Immunology, 2026)

Hyperbranched polyamine-graft-poly(ε-caprolactone) with integrated flame retardancy, plasticization, and filler-dispersion functions toward high-performance poly(vinyl chloride) plastics - Xing-Hao Wang; Liang Yang; Jing Zhao; Ze-Zhong Lin; Dan-Dan Shi; Yu Chen; Pei-Yao Chen (Chemical Engineering Journal, 2026)

Pulsed electric fields as a green alternative to chemical treatment: Toward enhanced molecular interactions and performance in biodegradable preservation films - Rui Wang; Pei-Feng Guo; Ying Xu; Xing-Chan Xie; Dan-Dan Lin; Yu-Wei Wu; Dong-Yang Xu; Lang-Hong Wang; Xin-An Zeng (Chemical Engineering Journal, 2026)

Oxygen carrying reactivity of ilmenites after long series of redox cycles in a 5 MWth CLC pilot unit - Yang Wang; Zhenshan Li; Dan Li; Jiaye Li; Chen Song; Qi Sun; Jinzhi Cai; Yongjia Yang; Hao Wang; Angran Zhao; Weicheng Li; Geng Wei; et al. (Chemical Engineering Journal, 2026)

Exploring the role of VAV2 rare variants in primary open-angle glaucoma: genetic insights and pathophysiological mechanisms - Runze Li; Yuhong Chen; Shanshan Zhang; Lin Ye; Huaping Tian; Zheng Li; Wentao Wang; Hongjing Li; Ruilin Liao; Haojue Xu; Junlan Chuan; Chao Qu; et al. (Science China Life Sciences, 2026)

Deciphering Ferroptosis-Related Astrocyte Subpopulations and Diagnostic Biomarkers in Parkinson’s Disease through RNA Transcriptomics - Zhongying Gong; Dan Guo; Yufeng Lin; Zhiwei Liu; Mengdi Lv; Xinxin Liu; Mingshuo Sun; Linlin Wang; Tianman Zhao; Zhiyun Wang; Xue Xue (Molecular Neurobiology, 2026)

The Combination of Sodium Tanshinone IIA Sulfonate and Mesenchymal Stem Cell-derived Exosomes Against Spinal Cord Injury via VEGF Pathway - Dan Luo; Lin Ma; Zhijian Pan; Ling Chen; Zhifeng Hu; Chaolun Liang; Zenglu Wang; Zhifeng Xiao; Dingkun Lin; Jinfeng Li; Da Guo; Xing Li (Molecular Neurobiology, 2026)

Evaluation of the lipolytic and antioxidant activities of different strains of coagulase-negative staphylococci in fermented sausages - Dan Li; Yuyu Du; Liya Su; Yaqiu Lin; Jiong Zheng; Fidel Toldrá; Chenglin Zhu; Muying Du; Yuan Liu; Juan Chen (Meat Science, 2025)

Trigger efficient peroxydisulfate-assisted photocatalysis by S-scheme Co3O4/BiOCl heterojunctions: Vital roles of Co2+/Co3+ redox centers and oxygen vacancies - Chang-Bin Yu; Chong Xu; Lin He; Wei-Ya Huang; Kai Yang; Dan Li (Journal of Environmental Chemical Engineering, 2025)

Spermidine enhances cold tolerance in tomato fruit by boosting antioxidant and energy metabolism synergy - Jian-Lin He; Shi-Yin Xie; Xiao-Dan Zhao; Da-Qi Fu (Food Research International, 2025)

Zein/ferulic acid/sodium alginate ternary nanoparticles: characterization and application in stable Pickering emulsions - Xu Zhang; Fangzhu Zheng; Xianglong Dai; Jingsheng Liu; Lin Xiu; Huimin Liu; Dan Cai (Food Chemistry, 2025)

Ultrasound-optimized phenolic recovery from feijoa (Acca sellowiana) peel: Cultivar variability, antioxidant capacity, and in vitro starch digestion - Qiyang Chen; Pei Li; Chunrong Li; Lin Luo; Yuanyuan Peng; Baiqian Wang; Dan Wang (Food Chemistry, 2025)

Use of dual-position and high-radioactivity 14C labeling, high-resolution mass spectrometry for pesticide transformation in vegetable: Uptake and metabolism of quinotrione in cabbage - Enguang Nie; Zheng Lin; Jingyan Huang; Jiaye Zhu; Dan Zhou; Yan Chen; Haiyan Wang; Zhen Yang (Food Chemistry, 2025)

Bio-templated nanocellulose/ZnO hybrids reinforced PVA/chitosan films with synergistic antibacterial activity for enhanced food preservation - Dan Chen; Shiyu Lin; Liming Cao; Wei Huang (Food Packaging and Shelf Life, 2025)

Optimizing RO membrane cleaning: A high-precision and efficient approach using electrochemical impedance spectroscopy - Jinyan Wang; Ming Gao; Manman Wang; Jingrun Xing; Dan Lu; Zhikan Yao; Lin Zhang (Desalination, 2025)

BreathFIT: Liquid metal-PDMS sticky conductors and AuNPs/MXene biosensors for synchronous EMG-lactate monitoring in respiratory health - Yang Liu; Zixin Lin; Yuetao Zhang; Xinyu Zhang; Zhiqi Li; Rubing Xiong; Chunxiao Long; Jiaqi Huang; Can Liu; Ziwei Zheng; Dan Li; Yongchang Ouyang; et al. (Chemical Engineering Journal, 2025)

Reversible flexible functional metal-organic frameworks sensor with artificial intelligence data analysis for real-time trace water monitor - Dan Lin; Anqi Liu; Lei Pan; Liang Yang; Changlong Jiang (Chemical Engineering Journal, 2025)

In-situ polymerized ether-ester copolymer electrolytes with regulated solvation structure for quasi-solid-state lithium metal batteries - Guocheng Wang; Yongjie Dan; Xinyu Lin; Qi Liu; Yanhua Niu; Guangxian Li (Chemical Engineering Journal, 2025)

Corrigendum to “Sirtuin 1/3 regulates p53 deacetylation to inhibit iron poisoning-induced alveolar epithelial cell death and contributes to Rapamycin-mediated protection against limb ischemia/reperfusion-induced lung injury” [Chem. Biol. Interact. 421 (2025) 111756] - Dan Huang; Yong-lin Liang; Lie-liang Zhang; Bin Zhou; Bin Tang (Chemico-Biological Interactions, 2025)

Body Composition-Derived Subtypes in Tibetan Adults Residing at Qinghai-High Plateau and Their Associations with Distinct Metabolite Profiles and Cardiometabolic Outcomes - Tiemei Li; Lin Shi; Qingxia Huang; Ruijie Xu; Bin Zhang; Dan Zhang; Qi Wang; Haijing Wang; Li Tong; Huiru Tang; Youfa Wang; Wen Peng (Phenomics, 2025)

Voltage-Gated sodium channel Nav1.6 mediates glioblastoma proliferation and migration via Na+/H+ Exchanger-1 and inhibits apoptosis through ERK-AKT pathway - Samed Ahmed Alezzi Alameri; Yue Kong; Qing-Da Shi; Yue-Lin Huang; Ao-Ran Sui; Dan-Dan Zhu; Ying-Zi Wang; Wang Miao; Shao Li; Guang Yang (Molecular Biology Reports, 2025)

Statistical inferences of differences and correlations in the seismic frequencies of large-scale fault zones in Western Sichuan, China - Yuan Xue; Dan Hu; Junreng Ge; Xinyu Yao; Mingyue Dai; Bingyan Fan; Yu Ming; Muchen Lin (Journal of Seismology, 2025)

Isolation and Characterization of a Novel Photo-Degradant of Brexpiprazole Due to an Intramolecular [2 + 2] Cycloaddition Via High Resolution MSn (n = 1 To 3) Analysis and Multi-Dimensional NMR Measurement - Jinsheng Lin; Qilin Wu; Xueyang Liu; Renjian Cao; Qiyun Yong; Dan Li; Wenbin Chen; Min Li; Weiyang Shen (Journal of Pharmaceutical Innovation, 2025)

Transcription factor MAZ activates the transcription of hypomethylated TYMP in ccRCC - Yihan Dong; Xinyu Liu; Jiaxin Li; Tianyu Lin; Rui Wang; Huamao Jiang; Yong Wang; Dan Yue (Functional & Integrative Genomics, 2025)

Neural oscillations predict flow experience - Bingxin Lin; Baoshun Guo; Lingyun Zhuang; Dan Zhang; Fei Wang (Cognitive Neurodynamics, 2025)

Modulation of growth, gut-liver axis, and antioxidant defense by Bacillus tequilensis (GCB-3) in grass carp (Ctenopharyngodon idella) under high-carbohydrate diet: Insights into health enhancement and oxidative stress mitigation - Xin Wang; Dongming Zhang; Xinping Zhang; Xinyu Lei; Dan Jiang; Lili Lin; Wenli Zhu; Sibu Wang; Quan Huang; Yuxin Li; Yu-ke Chen; Zhixin Guo (Animal Feed Science and Technology, 2025)

Assessment of habitat characteristics in typical seagrass bed ecosystems along the coast of Changhai County, Dalian - Yuchen Chu; Jun Yang; Juncheng Yin; Jie Tian; Jun Song; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; Yanjun Wang; Qian Sun; Quanxiang Meng; et al. (Acta Oceanologica Sinica, 2025)

Biogenic synthesis of selenium nanoparticles by Bacillus amyloliquefaciens: A promising method for mitigating mycotoxin contamination and fighting Fusarium graminearum - Ezzeldin Ibrahim; Yan Fang; Raghda Nasser; Dan Wang; Doaa Abd El-maksoud Khalil Kafsheer; Solabomi Olaitan Ayoade; Rahila Hafeez; Wafa Abdullah I. Al-Megrin; Bin Li; Haiping Lin (Journal of Hazardous Materials, 2025)

Ecological restoration in plateau pika-disturbed alpine meadows: Soil-microbe-enzyme stoichiometry and microbial adaptations during vegetation recovery of bare patches - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Journal of Environmental Management, 2025)

Extended thermophilic phase promotes fungal-bacterial collaboration to facilitate humification in batch-fed composting - Haichao Wang; Xiaowei Zheng; Dong Guo; Dan Liu; Bing Bai; Yan Shao; Bing Yue; Huan Zhang; Shuye Lin (Environmental Research, 2025)

Stable and efficient n-type perylene diimides radical as cathode interlayer with wide thickness tolerance for organic solar cells - Lin Hu; Senmei Lan; Guobin Shen; Fang Wang; Yingzhi Jin; Zhen Su; Jia Yao; Mengzhen Du; Zheng Yan; Wei Li; Dan Zhou; Erjun Zhou; et al. (Chemical Engineering Journal, 2025)

Deep eutectic solvent-assisted 3D printing of lignocellulosic biomass - Tingting Wu; Sigit Sugiarto; Udyani Aloka Weerasinghe; Ruochen Yang; Linran Jia; Pek Yin Michelle Yew; Danwei Zhang; Thenapakiam Sathasivam; Pei Lin Chee; Xunchang Fei; Dan Kai (Chemical Engineering Journal, 2025)

Signal molecule-mediated algae-bacteria interactions and membrane-enabled separation synergize wastewater bioremediation - Kai-Yuan Li; Jin-Long Zhou; Ashiwin Vadiveloo; Jia-Nan Li; Dan Zhou; Jia-Ming Wang; Ci Zhang; Yi-Lin Xie; Dong-Zhi Chen; Feng Gao (Chemical Engineering Journal, 2025)

Effects of plateau pika disturbance on soil net nitrogen mineralization from small to large scales in alpine meadows - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (CATENA, 2025)

Sirtuin 1/3 regulates p53 deacetylation to inhibit iron poisoning-induced alveolar epithelial cell death and contributes to Rapamycin-mediated protection against limb ischemia/reperfusion-induced lung injury - Dan Huang; Yong-lin Liang; Lie-liang Zhang; Bin Zhou; Bin Tang (Chemico-Biological Interactions, 2025)

Water savings policy in western Kansas: a decade-long satellite-based examination - Ramesh Dhungel; Robert Aiken; Xiaomao Lin; Shannon Kenyon; Paul D. Colaizzi; Dan O’Brien; R. Louis Baumhardt; Seth Kutikoff (Irrigation Science, 2025)

Correction: Flavisericum labens gen. nov., sp. nov., a novel member of the family Flavobacteriaceae isolated from the seawater of Dongshan Bay - Jieyi Li; Ziling Xu; Zhiyi Su; Guohua Liu; Yue Xu; Dan Lin; Kai Tang (Antonie van Leeuwenhoek, 2025)

Prediction on the seismic behaviour of a multi-stage anchored slope by a time-dependent displacement analysis - Yu-Liang Lin; Li Lu; Dan He; Xiaobin Chen; JunYi Duan (European Journal of Environmental and Civil Engineering, 2025)

Vitamin E alleviates ammonia‑nitrogen and hypoxia co-exposure-induced intestinal damage in grass carp (Ctenopharyngodon idella) by modulating mitochondrial function, cellular autophagy and apoptosis - Rui Su; Ke Yao; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Pei Wu (Aquaculture, 2025)

Bridging blue carbon and carbon markets: An interdisciplinary analysis of research and technology for climate mitigation - Nihed Benani; Pingjian Yang; Nicholas Miwornunyuie; Tao Wang; Dan Wu; Faming Wang; Jian lin Chen; Shuguo Lv; Guozhu Mao (Ocean & Coastal Management, 2025)

Carbon-nitrogen-phosphorus level regulation of potentially toxic elements and enzyme activities in paddy soil aggregates: Straw and organic fertilizer effects - Keqi Zhao; Wenbo Xiao; Nanyi Wang; Xiaobing Zhang; Ying Wang; Hua Peng; Jiachao Zhang; Anwei Chen; Renli Qi; Fangying Yu; Dan Wan; Lin Luo; et al. (Journal of Environmental Chemical Engineering, 2025)

Catalytic pyrolysis of paper mill sludge over self-sourced CaO/biochar catalyst under different temperatures - Wantong Kai; Xing Xie; Dan Lin; Yusuf Makarfi Isa; Alexander Kozlov; Maxim Penzik; Bin Li (Fuel, 2025)

Functional properties and sensitization of β-lactoglobulin were improved by covalent binding with exopolysaccharides and (−)-epigallocatechin gallate - Cuicui Duan; Yi Zhang; Cheng Wu; Siyang Sui; Hui Liu; Hongru Wang; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

Lithium bond-mediated multiple synergy enabling mechanical robustness, self-healing and ultrasensitive ion-conductive elastomers for flexible sensor - Lingli Kong; Tianwen Luo; Rufeng He; Dan Huang; Bai Huang; Lihua Fu; Baofeng Lin; Chuanhui Xu (Chemical Engineering Journal, 2025)

Acid-resistant microporous polyether nanofiltration membrane with high permeability for wastewater treatment - Chuanqi Zhang; Yanjun Zeng; Dan Lu; Yuxin Tao; Zhikan Yao; Saisai Lin; Yunlong Cui; Lin Zhang (Chemical Engineering Journal, 2025)

Heterojunction and electrolyte engineering of carbon-nanobow with built-in dual anions vacancies for sodium-metal storage - Jingjing Liu; Zili Yang; Quanzhi Lin; Feixue Luo; Mingjie Ou; Dan Tu; Wenyao Yang; Jianhua Xu; Yajie Yang (Chemical Engineering Journal, 2025)

Self-healing and thickness-insensitive perylene diimide-based cathode interfacial layers for organic solar cells - Wei Chen; Dan Zhou; Lin Hu; Jiangang Ma; Guobin Shen; Wentian Wan; Shuhua Wang; Fang Wang; Ruizhi Lv; Bin Hu; Haitao Xu; Zaifang Li; et al. (Chemical Engineering Journal, 2025)

Senegenin ameliorates diabetic encephalopathy via promoting mitophagy and repressing NLRP3 inflammasome activation - Xiao-dan Yan; Yu Yang; Wan-ting Zhang; Qing-quan Kong; Xi-tong Zheng; Lin-sen Li; Qing Yu (Psychopharmacology, 2025)

Phosphorus mitigates nitrite stress-induced liver damage in adult grass carp (Ctenopharyngodon idellus) by alleviating mitochondrial dysfunction and inhibiting apoptosis - Jia-Hao Zhang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Lu Zhang; Hai-Feng Mi; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

New perspective on mechanism of L-arginine in promoting skeletal muscle growth of grass carp (Ctenopharyngodon Idella): Via enhancing skeletal muscle functions and regulating energy metabolism - Qiu-Yan Chen; Yu-Long Ma; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Decreasing sensitivity of human populations to temperature variability during 50–10 ka in China - Zinan Lin; Dan Zhu; Jiayi Zhou; Yuhan Gao; Zhen Wang; Eric Galbraith; Jiaoyang Ruan; Jiafu Zhang (Quaternary Science Reviews, 2025)

Biodegradable microplastics exacerbate the risk of antibiotic resistance genes pollution in agricultural soils - Dan Zhang; Jianbin Sun; Shuang Peng; Yiming Wang; Xiangui Lin; Shanshan Wang (Journal of Hazardous Materials, 2025)

Predicting arsenic bioaccessibility: A global data-driven machine learning approach and its implication for reducing carbon emissions - Haonan Zhang; Dan Han; Maosheng Zhong; Tianxiang Xia; Suo Yang; Shijie Wang; Ping Zhang; Lin Jiang (Journal of Hazardous Materials, 2025)

Efficient recovery of spent catalysts in PAO production via annular drainage hydrocyclone: a sustainable approach for fluorinated waste reduction - Wei Zhao; Jian-ping Li; Tong Zhang; Shu Zhu; Ao-song Wei; Dan-hui Yang; Xue-jing Yang; Hua-lin Wang (Journal of Cleaner Production, 2025)

Adaptive fertilization strategies for premature senescence challenges in film-mulched maize: Insights from a 4-year field study - Haixiang Xiong; Chi Ma; Shujie Sun; Ziyi Wang; Ji Zhao; Chun Zhang; Lin Yang; Zhaoyun Dong; Zhikuan Jia; Dan Liu; Qingfang Han; Xudong Zhang (European Journal of Agronomy, 2025)

Enhanced biosynthesis of 6-aminocaproic acid in engineered Escherichia coli with artificial protein cage-organized enzymatic cascades - Ruoshi Luo; Lin Hu; Dan Wang; Kaixing Xiao; Xuemei Liu; Yaqi Kang; Qinhong Wang (Bioresource Technology, 2025)

The Adhesion Characteristics of Fouling Organism on Two Kinds of Mesh Coat - Lei Li; Jinmeng Bao; Dagui Liao; Yanan Wei; Cong Yan; Xiaoxu Fan; Shen Lin; Dan Liu; Wei Tian; Yanming Sui; Mei Jiang (Thalassas: An International Journal of Marine Sciences, 2025)

Carbon, nitrogen, and phosphorus ecological stoichiometry in Cenchrus fungigraminus and soil under waterlogging stress - Simeng Song; Hengyu Zhou; Pingxuan Li; Lin Zhang; Dewei Su; Dan Zheng; Zhaoxiong Zhang; Zongzhi Luo; Shikui Yu; Bin Liu; Zhanxi Lin; Dongmei Lin (Plant and Soil, 2025)

Regulatory Mechanism of CRTC1 on Autophagy and GluA2 Expression in Epilepsy - Xueying Wang; Liqian Zhou; Lin Yang; Shaoping Huang; Yuying Wang; Dan Li (Molecular Neurobiology, 2025)

Flavisericum labens gen. nov., sp. nov., a novel member of the family Flavobacteriaceae isolated from the seawater of Dongshan Bay - Jieyi Li; Ziling Xu; Zhiyi Su; Guohua Liu; Yue Xu; Dan Lin; Kai Tang (Antonie van Leeuwenhoek, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Discovery of 7-azaindole-3-acrylamide inhibitors of inflammasomes/IL-1β for the treatment of inflammatory bowel disease - Yuyun Yan; Xiuxiu Zhang; Ruiwen Wu; Xiangting Liang; Yiming Luo; Jie Yang; Dan Wu; Geng Lin; Ping Sun; Zhongjin Yang; Wenhui Hu (Molecular Diversity, 2025)

Two new cadinane-type sesquiterpene glycosides from Dendrobium findleyanum - Zi-Xi Lin; Zhong-Quan Cheng; Dan Yang (Natural Product Research, 2025)

Geochemistry of Mesozoic siliceous rocks in the Tongjiang accretionary complex of Northeast China: Implications for the evolution of the Paleo-Pacific subduction zone - Wen-Hao Zhang; Jian-Bo Zhou; Yuan-Lin Meng; Wei-Bin Liu; Dan-Dan Wang; Xu-Feng Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Seasonal patterns in diversity, complexity and community assembly of soil microorganisms in a subtropical coastal wetland - Guiping YE; Nan YANG; Ziyang HE; Ping YANG; Ruichao YE; Miaohua JIANG; Dan WANG; Dingding CAO; Wenbin ZHANG; Xiangying WEI; Yongxin LIN (Pedosphere, 2025)

Assessment of the combined response of heavy metals and human pathogens to different additives during composting of black soldier fly manure - Nanyi Wang; Yong He; Xiaobing Zhang; Ying Wang; Hua Peng; Jiachao Zhang; Xichen Zhao; Anwei Chen; Renli Qi; Dan Wan; Lin Luo; Liuqin He (Journal of Hazardous Materials, 2025)

Dietary vitamin C improves muscle hardness and springiness associated with collagen and elastin synthesis in grass carp (Ctenopharyngodon idella) - Xin-Lei Xue; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Yang Liu; Yao-Bin Ma; Jun Jiang; Dong Han; Wen-Bin Zhang; Wei-Dan Jiang (Food Research International, 2025)

Tea polyphenols: A promising alternative to antibiotics for preventing bacterial enteritis in grass carp (Ctenopharyngodon idella) - Yao-Bin Ma; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng (Food Research International, 2025)

Diffusion of sodium ions based on the interactions between gum arabic and oral mucin: Effects from the molecular weight of gum arabic - Yanlei Li; Ruiting Chang; Lin Lu; Zhiming Gao; Yuehan Wu; Wenxin Jiang; Dan Yuan; Katsuyoshi Nishinari (Food Chemistry, 2025)

Associations of long-term exposure to PM2.5 and its constituents with children renal function: a national retrospective study in China - Siwen Yu; Chunxia Cui; Wei Wu; Lianlong Yu; Yiya Liu; Qijiong Zhu; Zhiqing Chen; Shangfeng Yang; Yi Lin; Jianxiong Hu; Guanhao He; Xiaomei Dong; et al. (Environmental Research, 2025)

Experimental investigation on the interface of concrete-filled steel tubular (CFST) structures based on roughness and geometric deviation - Dan-Yang Ma; Ying-Qian Guo; Lin-Hai Han; Chuan-Chuan Hou (Engineering Structures, 2025)

Impact of cropland use transformation on ecosystem carbon sinks in a typical agroforestry mixed region: An analysis from explicit and implicit perspectives - Yajuan Zhou; Lijie He; Ershen Zhang; Dan Lu; Aiwen Lin (Environmental Impact Assessment Review, 2025)

Controllable synthesis of bimetallic Cu-Zn conjugated polymer microflowers with splendid laccase- and antioxidase-like activities for colorimetric detection of organic pollutants and eliminating cigarette smoke radicals - Shu-Chang Zhao; Dan Wu; Ya-Nan Kong; Jing-Jing Luo; Bo-Yi Yuan; Rui-Lin Liu (Journal of Hazardous Materials, 2025)

Mitigation of the toxic effects of nitrite: Role and mechanism of isoleucine in mitigating mitochondrial DNA leakage-induced inflammation in grass carp (Ctenopharyngodon idella) under nitrite exposure - Kai-Xuan Ren; Lin Feng; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Cheng-Bo Zhong; Xiao-Qiu Zhou; Wei-Dan Jiang (Journal of Hazardous Materials, 2025)

Effect of electron beam irradiation on the quality of chicken during post-mortem ageing - Xin Wang; Linya Wang; Jiangtao Yu; Yifeng Teng; Xiaomei Xiang; Dan Zhang; Luyao Kang; Yabin Niu; Xianchao Feng; Lin Chen (Food Chemistry, 2025)

Remediation of Heavy Metal Contaminated Soil by Functional Pellets of Charcoal Organic Fertilizer: Rhizosphere and Non-Rhizosphere Soil Microorganisms - Fanghong Li; Xichen Zhao; Renli Qi; Liuqin He; Dan Wan; Jiachao Zhang; Xiaobing Zhang; Ying Wang; Genyi Wu; Hongli Huang; Lin Luo; Lihua Zhang (Water, Air, & Soil Pollution, 2025)

Sphagnum cultivation enhances soil carbon stock by alleviating microbial phosphorus limitation - Dan Xue; Huai Chen; Xiaohan Yang; Jennifer Ene Idoko; Lin Wu (Agriculture, Ecosystems & Environment, 2025)

A nutritional strategy for improving sub-adult grass carp (Ctenopharyngodon idella) flesh flavor: The role of α-lipoic acid in regulating muscle nucleotide and fatty acid metabolism - Yang Zhang; Pei Wu; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Corrigendum to “Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella)” [Aquaculture Volume 598, 15 March 2025, 742053] - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Exploration of the structural features and anti-oxidative activity of whey protein hydrolysates produced by Lactiplantibacillus plantarum - Cuicui Duan; Shunan Hu; Cheng Wu; Yi Zhang; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

Unveiling high-light-use efficiency in Juglans mandshurica: Adaptive insights from leaf morphology and physiology - Qinhui Zhang; Dan Peng; Xiaona Pei; Yitong Chen; Zihan Yan; Mingrui Kang; Jinrong Hu; Yulu Pan; Jingxin Yu; Lu Xu; Huicong Lin; Xiyang Zhao (Forest Ecology and Management, 2025)

A breakthrough computational strategy for efficient enzymatic digestion of walnut protein to prepare antioxidant peptides - Like Lin; Dan Xiao; Wei Song; Weihong Lu (Food Chemistry, 2025)

An emulsion gel made by waxy maize starch hydrogel incorporated with tea polyphenols/exopolysaccharides: Structure and stability properties, antioxidant and delivery function - Cuicui Duan; Shunan Hu; Ran Wang; Cheng Wu; Yi Zhang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2025)

Long-term exposure to zearalenone: Assessing risks and effects on aquatic food safety and quality - Hong-Yun Zhang; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Xiao-Qiu Zhou; Lin Feng (Food Bioscience, 2025)

Dietary AiiO-AIO6 mitigated Aeromonas hydrophila-induced intestinal inflammation in juvenile grass carp (Ctenopharyngodon idella) involving in NF-κB signaling and pyroptosis - Jie Huang; Lin Feng; Wei-Dan Jiang; Yang Liu; Jun Jiang; Hong-Mei Ren; Chai-Mei Wu; Xiao-Qiu Zhou; Pei Wu (Fish & Shellfish Immunology, 2025)

Effects of shrub stem and litter on promoting concentrated flow branching, increasing flow resistance, and reducing sediment during gully bed erosion - Lin Liu; Donghong Xiong; Binyan Zhang; Wenduo Zhang; Suhua Fu; Liangtao Shi; Dan Yang; Baojun Zhang; Xiaodan Wang (CATENA, 2025)

Engineering a complete mevalonate pathway in Chlamydomonas reinhardtii for enhanced isoprenoid production - Jingkai Wang; Muhammad Anwar; Jiancheng Li; Lin Dan; Bin Jia; Zhangli Hu (Algal Research, 2025)

Spatiotemporal response of agricultural drought to meteorological drought in the upper Hanjiang River Basin from three-dimensional perspective - Shenghong Liu; Shaokang Yang; Ji Liu; Te Zhang; Qingxia Lin; Wenjuan Chang; Tao Peng; Dan Yu (Agricultural and Forest Meteorology, 2025)

COP1 Overexpression Attenuates Nociceptive Behaviors and Neuroinflammation in Cancer-Induced Bone Pain by Suppressing c/EBPβ - Dan-Yang Li; Lin Liu; Shao-Jie Gao; Dai-Qiang Liu; Long-Qing Zhang; Jia-Yi Wu; Fan-He Song; Xin-Yi Dai; Ya-Qun Zhou; Wei Mei (Journal of Neuroimmune Pharmacology, 2025)

New perspectives on the immune regulatory role of dietary silymarin in the intestines of juvenile grass carp (Ctenopharyngodon idella) - Feng Jia; Li Wei; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Comprehensive analysis of microplastics at typical outlets around Hainan Island: From spatial distribution to flux estimation and correlation analysis - Shiyu Xie; Yuanyuan Su; Dan Qi; Fei Liu; Liu Gao; Ruiqi Bao; Xing Cheng; Xubing Lin; Tingting Zhang; Licheng Peng (Water Research, 2025)

Developmental and reproductive toxicity (DART) study of a novel SARS-CoV-2 tetravalent recombinant protein vaccine (SCTV01E) in rats - Xiao Zhang; Jilei Jia; Gaojian Chen; Dan Meng; Juan Ma; Huimin Wang; Shaozheng Zhou; Lin Ma; Qianqian Qian; Xuejie Liu; Xuefeng Li; Liangzhi Xie (Reproductive Toxicology, 2025)

Histidine improves flesh quality: An assessment of grass carp (Ctenopharyngodon idella) muscle in terms of texture, nutritional value and flavor - Xin Zeng; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Lin Feng (Food Chemistry, 2025)

Microcapsules stabilized by cellulose nanofibrils/whey protein complexes and modified with cinnamaldehyde: Characterization and release properties - Dan Wang; Lin Liu; Tanghui Liu; Jie Zhao; Hai Chi; Hongrui Chen; Jie Tang; Xingzhong Zhang (Food Chemistry, 2025)

Assessment of health risk and identification of pollution sources of heavy metals in water in Chongqing's wastewater treatment plants based on ICP-MS - Yaxuan Li; Jingqing Zhang; Nanchuan Song; Yiwu Wang; Jialing Yu; Lin He; Ruijia Yang; Lin Yang; Dan He (Environmental Pollution, 2025)

Microbial strategies regulate organic carbon accumulation in saline paddy soils: A millennium chronosequence - Dan Cao; Xiangxiang Wang; Yi Miao; Chuanfa Wu; Haoqing Zhang; Shuang Wang; Feng Wang; Lin Chen; Chao Liang; Yakov Kuzyakov; Jianping Chen; Tida Ge; et al. (CATENA, 2025)

Exploring Potential Health Risk of Chenxiang Huaqi Tablets Based on Inorganic Elemental Evaluation Using ICP-MS - Shuxiang Pan; Lin Yang; Yiwu Wang; Yuan Shen; Jialing Yu; Dan He (Biological Trace Element Research, 2025)

Linoleic acid alleviates aluminum toxicity by modulating fatty acid composition and redox homeostasis in wheat (Triticum aestivum) seedlings - Yiqun Ou; Zhuoran Teng; Yuchen Shu; Yi Wang; Dan Wang; Chengliang Sun; Xianyong Lin (Journal of Hazardous Materials, 2025)

Investigation the antioxidant mechanisms of Capsaicinoids on myofibrillar protein based on multispectral and molecular docking - Jianhua Zhao; Chunyan Jiang; Meijuan Lei; Yilin Xie; Jie Zhao; Jiaxin Chen; Mingyuan Yang; Dan Xiang; Jie Tang; Hongbin Lin (Food Chemistry, 2025)

Effects of static magnetic field treatment on the digestive, structural and physicochemical characteristics of germinated corn starch - Xin Jiang; Fangzhu Zheng; Jiankun Yu; Pengwen Lv; He Ban; Huimin Liu; Dan Cai; Lin Xiu; Jingsheng Liu (Food Chemistry, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

Carbon emissions prediction based on ensemble models: An empirical analysis from China - Song Hu; Shixuan Li; Lin Gong; Dan Liu; Zhe Wang; Gangyan Xu (Environmental Modelling & Software, 2025)

Optimization of mechanical properties and finite element simulation analysis of hollow fiber membranes in gas-liquid membrane separation technology - Zhengda Lin; Yihe Wang; Zhe Fu; Dan Zhong; Xingwei Du; Jun Zhang (Desalination, 2025)

Perylene diimide cathode interface layer with siloxane bay-modification for efficient and stable organic solar cells - Dan Zhou; Yujie Pu; Yanyan Wang; Lin Hu; Jianwei Quan; Senmei Lan; Jiangang Ma; Fang Wang; Wentian Wan; Yongfen Tong; Ruizhi Lv; Haitao Xu; et al. (Chemical Engineering Journal, 2025)

Targeting cardiac fibrosis with Chimeric Antigen Receptor-Engineered Cells - Qinghang Zhang; Jinjie Dai; Tianbao Liu; Wutian Rao; Dan Li; Zhengying Gu; Lin Huang; Jiayi Wang; Xumin Hou (Molecular and Cellular Biochemistry, 2025)

Screening of Regulatory mRNAs and miRNAs that Suppress Staphylococcus aureus Proliferation via Macrophage Ferroptosis - Lili Wang; Jiajia Bao; Danyang Yang; Sijia Gao; Xintong He; Dan He; Lin Liu; Yulian Xu; Qinya Yang; Sifei He; Lei Xu; Anlong Li (Current Microbiology, 2025)

Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella) - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Diamide insecticides in PM2.5: The unreported rural and urban air pollutants - Yanhao Zhang; Zifang Peng; Peiru Luo; Lin Zhu; Qingyun He; Congcong Pei; Dan Yin; Wenfen Zhang; Shusheng Zhang; Zongwei Cai (Journal of Hazardous Materials, 2025)

Effects of mixed exposure to PFAS on adolescent non-alcoholic fatty liver disease: Integrating evidence from human cohorts, toxicogenomics, and animal models to uncover mechanisms and potential target sites - Xiushuai Du; Dan-Lin Li; Xueming Xu; Yitian Wu; Zhiyuan Du; Gang Liang; Yue-Zu Li; Ya-Jie Zheng; Yu Qin; Kelei Qian; Jing Xu; Liping Gao; et al. (Journal of Hazardous Materials, 2025)

Integration of UV-vis spectroscopy and machine learning for identification of recycled polyethylene terephthalate - Yan-Ling Xie; Qi-Zhi Su; Qin-Bao Lin; Huai-Ning Zhong; Dan Li; Ben Dong (Food Packaging and Shelf Life, 2025)

Enhancing membrane distillation performance by adsorption using modified zeolite for shale gas produced water treatment - Haiqing Chang; Lin Huang; Mengzhe Lu; Zhongsen Yan; Pengwei Ji; Dan Qu; Fangshu Qu; Heng Liang (Desalination, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

A zwitterionic polymer filtrate reducer with enhanced anti-polyelectrolyte effect for high-temperature and high-salinity conditions - Shangdong Gao; Dan Lin; Ao Li; Liandong Deng; Anjie Dong; Jianhua Zhang (Chemical Engineering Journal, 2025)

Functionalizing separator for dual application in liquid and solid-state lithium metal batteries: Achieving stable cycling from − 20 °C to 60 °C - Chen Cheng; Changyong Zhao; Shuiping Cai; Yingkang Tian; Rongjin Lin; Dan Luo; Xiaofei Yang; Xuejie Gao; Runcang Sun (Chemical Engineering Journal, 2025)

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

Effects of biochar and compost on the bioavailability of heavy metals in soil aggregates with varying particle sizes - Fanghong Li; Shilin Jiang; Ge Chen; Dan Wan; Liuqin He; Jiachao Zhang; Keqi Zhao; Hongli Huang; Lin Luo; Genyi Wu; Lihua Zhang (Journal of Soils and Sediments, 2025)

Integrating ICP-MS and Chemometrics for Profiling Inorganic Elements in Lianhua Qingwen Capsules and Evaluating Health Risk - Shuya Li; Ke Yin; Yiwu Wang; Lihong Tan; Jianing Zhao; Shuxiang Pan; Lin Yang; Dan He (Biological Trace Element Research, 2025)

Soil micro-food web composition determines soil fertility and crop growth - Yaping Lin; Qing Yi; Dandan Gao; Jiangnan Li; Wei Zhang; Kelin Wang; Dan Xiao; Peilei Hu; Jie Zhao (Soil Ecology Letters, 2025)

Enhancing astaxanthin production in Schizochytrium sp.: Insights from orthogonal experiments and transcriptome analysis - Jiaxue Zhao; Dan Chen; Chubin Lin; Xia Wan (Algal Research, 2025)

α-asarone activates mitophagy to relieve diabetic encephalopathy via inhibiting apoptosis and oxidative stress - Xiao-dan Yan; Rong-hua Fan; Yu Wang; Xiao-xu Duan; Xuan Wei; Lin-sen Li; Qing Yu (Metabolic Brain Disease, 2025)

Protective effect of betaine supplementation in low-met diet against Aeromonas hydrophila-induced intestinal injury in grass carp (Ctenopharyngodon idella) - Hao Sun; Wei-Dan Jiang; Pei Wu; Yang Liu; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

Protective effects of dietary protein against nitrite stress in grass carp (Ctenopharyngodon idella): A new perspective - Hong-Ju Liu; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Hai-Feng Mi; Min Dong; Lu Zhang; Lin Feng (Aquaculture, 2025)

Determining the key meteorological factors affecting atmospheric CO2 and CH4 using machine learning algorithms at a suburban site in China - Wanyu Liu; Zhenchuan Niu; Xue Feng; Weijian Zhou; Dan Liang; Guowei Wang; Lin Liu (Urban Climate, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

An exploration of the interaction, structural characterization and anti-oxidative properties of proanthocyanidin and beta-lactoglobulin complex - Cuicui Duan; Mengchun Qin; Lifan Liu; Yixue Sun; Lin Cai; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

Effects of high-temperature stages on the physicochemical properties and oxidation products formation of rapeseed oil with carnosic acid - Ying-dan Zhu; Yue-ting Luan; Cheng-liang Chai; Ya-lin Xue; Zhang-qun Duan (Food Chemistry, 2025)

Developing a spatial optimization design approach towards energy-saving and outdoor thermal comfortable densely-built residential blocks using a dynamic local energy balance model - Lin Liu; Zihong Zhang; Shiying Lan; Xiaoyu Tian; Jing Liu; Wei Liao; Dan Wang (Energy and Buildings, 2025)

Impact analysis of uncertainty in thermal resistor-capacitor models on model predictive control performance - Dan Wang; Wanfu Zheng; Siqi Li; Yixing Chen; Xiaorui Lin; Zhe Wang (Energy and Buildings, 2025)

In-situ trichosanthin-IL2/pectin dynamic hydrogel activates dendritic cells and reverses T cell exhaustion for post-operative cancer therapy - Zeyun Gu; Guihua Chen; Nan Gao; Shuo Yao; Xiaoru Zhang; Quangang Xu; Wei Xiong; Lin Liu; Qin Liu; Dan Yin; Xiao-Ming Zhu; Yongzhuo Huang (Chemical Engineering Journal, 2025)

Modulation of Fe0-FexSy heterostructure by sulfurization constitutes an electron transfer channel for efficient triclosan degradation - Hantong Qie; Xuan Pan; Daibing Hou; Zihan Wang; Xuedan Cui; Aijun Lin; Jun Cui; Wenjie Yang; Dan Zhao (Chemical Engineering Journal, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

The role of bile acid in regulating head-kidney, spleen and skin immune function of on-growing grass carp (Ctenopharyngodon idella) - Fei Zhao; Xiu-Rong Peng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

New insights of 4-Methylesculetin in alleviating the effect of aflatoxin B1 on flesh quality of grass carp (Ctenopharyngodon idella) - Xiang-Ning He; Jia-Jia Zhang; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; He-Qun Shi; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Comprehensively assessing seasonal variations in the impact of urban greenspace morphology on urban heat island effects: A multidimensional analysis - Liangguo Lin; Yaolong Zhao; Juchao Zhao; Dan Wang (Sustainable Cities and Society, 2025)

ALFIN-like proteins link histone H3K4me3 to H2A ubiquitination and coordinate diverse chromatin modifications in Arabidopsis - Xiao-Min Su; Dan-Yang Yuan; Na Liu; Zhao-Chen Zhang; Minqi Yang; Lin Li; She Chen; Yue Zhou; Xin-Jian He (Molecular Plant, 2025)

Patterns and drivers of terrace abandonment in China: Monitoring based on multi-source remote sensing data - Dan Lu; Kangchuan Su; Zhanpeng Wang; Mengjie Hou; Xinxin Li; Aiwen Lin; Qingyuan Yang (Land Use Policy, 2025)

A spatial source-oriented and probability-based risk-assessment framework for heavy metal and PAH contamination of urban soils in Guangzhou, China - Lian Chen; Minghe Xie; Gaocong Li; Sen Lin; Dan Wang; Zhiyi Li; Yuan Wang; Zhenjiang Wang (Journal of Hazardous Materials, 2025)

Environmental life cycle assessment on the recycling processes of power batteries for new energy vehicles - You Zhou; Xue-Dan Cui; Ai-Jun Lin; Yan Dong; Gui-Lan Duan (Journal of Cleaner Production, 2025)

Paddy-upland rotation combined with manure application: An optimal strategy for enhancing soil multifunctionality - Dan Zhang; Jianbin Sun; Shuang Peng; Yiming Wang; Qingqing Hua; Pan Wu; Xiangui Lin (Journal of Environmental Management, 2025)

Predicting the efficiency of arsenic immobilization in soils by biochar using machine learning - Jin-Man Cao; Yu-Qian Liu; Yan-Qing Liu; Shu-Dan Xue; Hai-Hong Xiong; Chong-Lin Xu; Qi Xu; Gui-Lan Duan (Journal of Environmental Sciences, 2025)

Molecular characterization of extended-spectrum β-lactamases from the Akkermansia genus - Jiafu Lin; Tiantian Wang; Yaliang Zhou; Jingzhou Sha; Xueke Chen; Wenjie Wang; Chuan Zhang; Feng Xie; Yiwen Chu; Xinrong Wang; Dan Luo; Tao Song (International Journal of Food Microbiology, 2025)

Temperature cycling between 4 °C and 37 °C could reduce Salmonella viability in low-moisture foods - Zejia Lin; Shuang He; Zhiqian Liang; Dan Li (International Journal of Food Microbiology, 2025)

Preparation, characterization, and binding mechanism of quercetin-loaded composite nanoparticles based on zein-soybean protein isolate - Zhouliang Sun; Dan Li; Peiying Lin; Yanjie Zhao; Ji Zhang; Irina Sergeeva; Yang Li; Huanyu Zheng (Food Chemistry, 2025)

Identification and quantification of volatile organic compounds in Chinese recycled HDPE: Consequences for its applicability - Ming-Yue Zhang; Qi-Zhi Su; Qin-Bao Lin; Huai-Ning Zhong; Sheng Chen; Dan Li; Ben-Dong; Min-Qing Xu; Wei-Li Li (Food Packaging and Shelf Life, 2025)

Corrigendum to “Soybean glycinin impaired immune function and caused inflammation associated with PKC-ζ/NF-κb and mTORC1 signaling in the intestine of juvenile grass carp (Ctenopharyngodon idella)” [Fish and Shellfish Immunol. 106 (2020) 393–403] - Ya-Lin Zhang; Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2025)

Cascade energy transfer endows phosphorescent carbon dots-based films with tunable and broadband afterglow for fingerprint recognition and anticounterfeiting - Zhanpeng Liu; Xiangbo Ding; Lin Cai; Yihan Jia; Xia Ran; Zhongzheng Guo; Dan Mo; Yatao Pan; Lijun Guo (Chemical Engineering Journal, 2025)

Graphene quantum dots decorated organic conductive polymer for advanced ternary amorphous solar-blind UV photovoltaic photodetectors - Han Cai; Haolin Yang; Weisen Li; Jiarong Liang; Zhuogeng Lin; Xingui Tang; Yanghui Liu; Dan Zhang; Wei Zheng (Chemical Engineering Journal, 2025)

Retraction Note: Micafungin exerts antitumor effect on breast cancer and osteosarcoma through preventing EMT in tumor cells in an USP7/AKT/GSK-3β pathway-dependent manner - Qian-Lin Wang; Li Wang; Qiong-Yu Li; Hui-Yin Li; Ling Lin; Dan Wei; Jin-Yun Xu; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Cerasicoccus fimbriatus sp. nov., isolated from the mid-ridge of the Southwest Indian Ocean - Xuanyun Qiu; Beihan Chen; Dan Lin; Guohua Liu; Zhiyi Su; Mingzhe Zhang; Kai Tang (Antonie van Leeuwenhoek, 2025)

Allocation Strategy Optimization Using Repulsion-Enhanced Quantum Particle Swarm Optimization for Multi-AUV Systems - Changjian Lin; Dan Yu; Shibo Lin (Journal of Marine Science and Engineering, 2024)
In the context of multi-autonomous underwater vehicle (multi-AUV) operations, the target assignment is addressed as a multi-objective allocation (MOA) problem. The selection of strategy for multi-AUV target allocation is dependent on the current non-cooperative environment. This paper establishes a multi-AUV allocation situation advantage evaluation system to assess and quantify the non-cooperative environment. Based on this framework, a multi-AUV target allocation model using a bi-matrix game theory is developed, where multi-AUV target allocation strategies are considered as part of the strategic framework within the game. The payoff matrix is constructed based on factors including the situational context of multi-AUV operations, effectiveness, and AUV operational integrity. The Nash equilibrium derived from the game analysis serves as the optimal solution for resource distribution in multi-AUV non-cooperative scenarios. To address the challenge of finding the Nash equilibrium in bi-matrix games, this paper introduces a repulsion process quantum particle swarm optimization (RPQPSO) algorithm. This method not only resolves the complexities of Nash equilibrium computation but also overcomes the limitations of traditional optimization methods that often converge to local optima. A simulation experiment of multi-AUV operations is designed to validate the multi-AUV target allocation model, demonstrating that the RPQPSO algorithm performs effectively and is applicable to multi-AUV task scenarios.

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Spherical covalent-organic framework-assisted laser desorption ionization mass spectrometry reveals the promotional effect of triphenyl phosphate on breast cancer in mice - Dan Ouyang; Akang Dan; Zian Lin; Zongwei Cai (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Pilot-scale study of turbid particle evolutional/removal characteristics during coagulation-sedimentation-filtration (CSF): Effects of coagulant dosage and secondary dosing after breakage - Dan Xiao; Jun Nan; Xiaoyue Zhang; Weipeng He; Yaqian Fan; Xianzeng Lin (Journal of Water Process Engineering, 2024)

Oxygen-deficient MnCO3 based on waste alkaline Zn-MnO2 battery as an enhanced activator for peroxymonosulfate removing Oxytetracycline hydrochloride - Yajie Wen; Jiabin Zhou; Lin He; Dan Liu (Journal of Water Process Engineering, 2024)

Long-term exposure to triclocarban induces splenic injuries in mice: Insights from spatial metabolomics and lipidomics - Peisi Xie; Jing Chen; Akang Dan; Zian Lin; Yu He; Zongwei Cai (Journal of Hazardous Materials, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Uncovering the toxic effects and adaptive mechanisms of aminated polystyrene nanoplastics on microbes in sludge anaerobic digestion system: Insight from extracellular to intracellular - Weixin Zhao; Hao Ma; Zhelu Gao; Dan Li; Yingzi Lin; Chuandong Wu; Liangliang Wei (Journal of Hazardous Materials, 2024)

Occurrence and human exposure risk of antibiotic resistance genes in tillage soils of dryland regions: A case study of northern Ningxia Plain, China - Jianbin Sun; Dan Zhang; Shuang Peng; Xiaoqian Yang; Qingqing Hua; Wei Wang; Yiming Wang; Xiangui Lin (Journal of Hazardous Materials, 2024)

Study on properties and CO2 emission of self-pulverizing calcium sulfoaluminate (SPCSA) after carbonization curing - Shuguo Li; Yang Lv; Chenhao He; Shengju Hou; Weinan Ma; Xiaodong Wen; Jianming Dan; Junpeng Mei; Lin Chi; Xiangguo Li (Journal of Environmental Chemical Engineering, 2024)

Plant oil-based phase change materials for sustainable thermal energy storage: A review - Wen-Ya Wu; Ming Gao; Reuben Yeo Jueyuan; Ming Lin; Suxi Wang; Warintorn Thitsartarn; Xikui Zhang; Dan Kai; Pei Wang; Zhenyao Qu; Jianwei Xu; Xian Jun Loh; et al. (Fuel, 2024)

Histidine is effective in promoting muscle growth and protein deposition: In vivo and in vitro experimental models of grass carp (Ctenopharyngodon idella) - Xin Zeng; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Ling Tang; Shu-Wei Li; Sheng-Yao Kuang; Lin Feng (Food Bioscience, 2024)

Microbial composition of spoiled irradiated ready-to-eat chicken feet and their spoilage characteristics - Xin Jia; Dan Wang; Ai-Lian Meng; Yong-Jie Lin; Ming Huang; Peng Gao; Pan Xu; Hao Chen (Food Microbiology, 2024)

The predominant role of IgM in grouper (Epinephelus coioides) mucosal defense against ectoparasitic protozoan infection - Zequan Mo; Huajian Lin; Xueli Lai; Pengbo Dan; Huicheng Wu; Xiaochun Luo; Xueming Dan; Yanwei Li (Fish & Shellfish Immunology, 2024)

Exposure to toluene diisocyanate induces dysbiosis of gut-lung homeostasis: Involvement of gut microbiota - Yuxuan Gou; Fu Lin; Li Dan; Dianyu Zhang (Environmental Pollution, 2024)

A novel ultra-sensitive semiconductor SERS substrate V5S4 nanopompons for the specific detection of antibiotics with AI technology - Weida Zhang; Yusi Peng; Chenglong Lin; Meimei Xu; Shuai Zhao; Dan Li; Yingchun Yang; Yong Yang (Chemical Engineering Journal, 2024)

Spatial heterogeneity of volatile organic compound pollution in a typical industrial park based on multi-point online monitoring: Pollution characteristics, health risks, and priority-controlled species - Mengjuan Han; Ge Ren; Xinna Zhao; Xiaodong Zhang; Hong Lin; Dan Liu; Lei Wang (Atmospheric Environment, 2024)

GLP-1 signaling-regulated SNAP25 is involved in improved insulin secretion in diabetic GK rats after Roux-en-Y gastric bypass surgery - Xiangchen Kong; Chao Lin; Chenxi Yang; Xin Wang; Bingfeng Li; Dan Yan; Yanhui Yang; Anyi Hu; Yanyin Chen; Xiaohui Xu; Xiaosong Ma (Molecular Biology Reports, 2024)

Transplantation of Wnt5a-modified Bone Marrow Mesenchymal Stem Cells Promotes Recovery After Spinal Cord Injury via the PI3K/AKT Pathway - Haimei Yang; Chaolun Liang; Junhua Luo; Xiuzhen Liu; Wanshun Wang; Kunrui Zheng; Dan Luo; Yu Hou; Da Guo; Dingkun Lin; Xiasheng Zheng; Xing Li (Molecular Neurobiology, 2024)
Spinal cord injury (SCI) is a severe neurological condition that can lead to paralysis or even death. This study explored the potential benefits of bone marrow mesenchymal stem cell (BMSC) transplantation for repairing SCI. BMSCs also differentiate into astrocytes within damaged spinal cord tissues hindering the cell transplantation efficacy, therefore it is crucial to enhance their neuronal differentiation rate to facilitate spinal cord repair. Wnt5a, an upstream protein in the non-classical Wnt signaling pathway, has been implicated in stem cell migration, differentiation, and neurite formation but its role in the neuronal differentiation of BMSCs remains unclear. Thus, this study investigated the role and underlying mechanisms of Wnt5a in promoting neuronal differentiation of BMSCs both in vivo and in vitro. Wnt5a enhanced neuronal differentiation of BMSCs in vitro while reducing astrocyte differentiation. Additionally, high-throughput RNA sequencing revealed a correlation between Wnt5a and phosphoinositide 3-kinase (PI3K)/protein kinase B(AKT) signaling, which was confirmed by the use of the PI3K inhibitor LY294002 to reverse the effects of Wnt5a on BMSC neuronal differentiation. Furthermore, transplantation of Wnt5a-modified BMSCs into SCI rats effectively improved the histomorphology (Hematoxylin and eosin [H&E], Nissl and Luxol Fast Blue [LFB] staining), motor function scores (Footprint test and Basso-Beattie-Bresnahan [BBB]scores)and promoted neuron production, axonal formation, and remodeling of myelin sheaths (microtubule associated protein-2 [MAP-2], growth-associated protein 43 [GAP43], myelin basic protein [MBP]), while reducing astrocyte production (glial fibrillary acidic protein [GFAP]). Therefore, targeting the Wnt5a/PI3K/AKT pathway could enhance BMSC transplantation for SCI treatment.

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Circ-Luc7l Absence Attenuates Diabetic Nephropathy Progression by Reducing Mesangial Cell Excessive Proliferation, Inflammation, and Extracellular Matrix Accumulation via Mediating the miR-205-5p/Tgfbr1 Pathway - Zhan Fang; Dan Wang; Fang Sun; Jing Chang; Dong Yuan; Shuhua Lin; Jian Teng (Biochemical Genetics, 2024)

Roseihalotalea indica gen. nov., sp. nov., a halophilic Bacteroidetes from mesopelagic Southwest Indian Ocean with higher carbohydrate metabolic potential - Beihan Chen; Mingzhe Zhang; Dan Lin; Jianing Ye; Kai Tang (Antonie van Leeuwenhoek, 2024)

Three-Dimensional CKANs: UUV Noncooperative Target State Estimation Approach Based on 3D Convolutional Kolmogorov–Arnold Networks - Changjian Lin; Dan Yu; Shibo Lin (Journal of Marine Science and Engineering, 2024)
Accurate and stable estimation of the position and trajectory of noncooperative targets is crucial for the safe navigation and operation of sonar-equipped underwater unmanned vehicles (UUVs). However, the uncertainty associated with sonar observations and the unpredictability of noncooperative target movements often undermine the stability of traditional Bayesian methods. This paper presents an innovative approach for noncooperative target state estimation utilizing 3D Convolutional Kolmogorov–Arnold Networks (3DCKANs). By establishing a non-Markovian model that characterizes state estimation of UUV noncooperative targets under uncertain observations, we leverage historical data to construct 3D Convolutional Kolmogorov–Arnold Networks. This network learns the patterns of sonar observations and target state transitions from a substantial offline dataset, allowing it to approximate the posterior probability distribution derived from past observations effectively. Additionally, a sliding window technique is integrated into the convolutional neural network to enhance the estimator’s fault tolerance with respect to observation data in both temporal and spatial dimensions, particularly when posterior probabilities are unknown. The incorporation of the Kolmogorov–Arnold representation within the convolutional layers enhances the network’s capacity for nonlinear expression and adaptability in processing spatial information. Finally, we present statistical experiments and simulation cases to validate the accuracy and stability of the proposed method.

Effect of alfalfa downy mildew (Peronospora aestivalis) infection on the growth and development of Therioaphis trifolii (Homoptera: Aphidiidae) - Lin-bo Xu; Liang-bin Yu; Fang-zheng Yue; Dan-yang Wang; Wen-long Li; Ba-teer Wulan; Yan-wei Cui (Crop Protection, 2024)

Characterization of the transmembrane C-type lectin reveals a novel phagocytic receptor for hemocytes of Tegillarca granosa - Dan Su; Jie Lin; Yang Zhang; Zexin Yang; Yefeng Lin; Yingbin Xu; Shanjie Zha; Yongbo Bao; Hongxing Liu (Aquaculture, 2024)

Meteorological effects of ventilation corridor in central urban areas: A case study of Wuhan - Xuesong Li; Kai Lin; Dan Cheng; Han Zou; Yulong Shu; Zhiguo Jin; Jiabei Zhu (Sustainable Cities and Society, 2024)

On the FT-ICR mass spectrometry analysis of dissolved organic matter released by adsorbent during coal chemical wastewater treatment - Qi Wei; Cai Chen; Hong-Peng Ma; Tao Liu; Bing Liu; Tian-Xiang Wang; Sen Zhang; Dan-Hui Yang; Wen-Jie Lv; Hua-Lin Wang (Science of The Total Environment, 2024)

Shallow groundwater table fluctuations weaken nitrogen accumulation in the thin layer vadose zone of cropland around plateau lakes, Southwest China - Qingfei Chen; Anqiang Chen; Jinheng Min; Lin Li; Wanli Hu; Chi Wang; Bin Fu; Shufang Guo; Dan Zhang (Science of The Total Environment, 2024)

Effect of shape on the transport and retention of nanoplastics in saturated quartz sand - Haiyan Yang; Xunyang Lin; Jizhe Lu; Xiaoning Zhao; Dan Wu; Hyunjung Kim; Lei Su; Li Cai (Journal of Hazardous Materials, 2024)

The carbon emission reduction benefits of the transformation of the intensive use of cultivated land in China - Yajuan Zhou; Ershen Zhang; Lijie He; Xinli Ke; Dan lu; Aiwen Lin; Xiaomin Lai (Journal of Environmental Management, 2024)

Rapid redox-response featured visual ascorbic acid sensor based on simple-assembled europium metal-organic framework - Lin-Lin Zhang; Li Li; Dan Wang; Yanping Hong; Kaijie Tang; Jiaxin Hong; Zeng Chen; Wuying Yang; Limin Lu; Lu-Ying Duan (Food Chemistry, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

3D printing technologies in water Treatment: Applications, Challenges, and emerging trends - Yun-fei Zhang; Jin-ze Li; Yue Zou; Yan-lin Liu; Lei Li; Jian-hui Xu; Dan Li; Qiang-qiang Rong; Jian-ying Li; Yi-xin Geng; Jia-wei Lai (Chemical Engineering Journal, 2024)

Comprehensive investigation of daytime radiative cooling technology for sustainable grain storage: A combined approach of field measurement and CFD simulations - Chongjia Lin; Yunlong Wang; Zhihang Zhao; Xisheng Lin; Rui Li; Zhaoping Zheng; Xuhua Shen; Zhongqing Lang; Weizhi Zhou; Jinbei Wang; Dan Yuan; Yankai Sun; et al. (Building and Environment, 2024)

Temporal characteristics and vertical profiles of atmospheric CH4 at the northern foot of the Qinling Mountains in China - Wanyu Liu; Xue Feng; Zhenchuan Niu; Weijian Zhou; Huilin Chen; Dan Liang; Mengni Lyu; Guowei Wang; Lin Liu (Atmospheric Environment, 2024)

A new ship tracing technology from oil spills based on multi-source data - Dan Luo; Peng Chen; Jingsong Yang; Xin Chen; Xiunan Li; Gang Zheng; Lin Ren; Yizhi Zhao (Marine Pollution Bulletin, 2024)

Real-time detection of mature table grapes using ESP-YOLO network on embedded platforms - Jiaoliao Chen; Huan Chen; Fang Xu; Mengnan Lin; Dan Zhang; Libin Zhang (Biosystems Engineering, 2024)

Early Cretaceous fayalite-, ferrosilite-, and biotite-bearing rhyolitic porphyries in the Baishuizhai area, South China: Formation by fractional crystallization in the shallow crust - Xiao Liu; Qiang Wang; Xi-Jun Liu; Lin Ma; Derek A. Wyman; Gong-Jian Tang; Wei Dan; Zi-Qi Jiang; Hao Wu; Wan-Long Hu; Jin-Heng Liu; Chuan-Bing Xu; et al. (Lithos, 2024)

Multi-deformable interpenetrating network thermosensitive hydrogel fluorescent device for real-time and visual detection of nitrite - Lingfei Li; Dan Lin; Shihao Xu; Liang Yang; Changlong Jiang (Journal of Hazardous Materials, 2024)

Alpha-linolenic acid/linoleic acid ratio can effectively promote muscle growth and protein deposition in grass carp (Ctenopharyngodon idella) - Chi-Bei Yao; Lin Feng; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Xiao-Qiu Zhou; Wei-Dan Jiang (Food Bioscience, 2024)

Myo-inositol: A potential game-changer in preventing gill cell death and alleviating “gill rot” in grass carp (Ctenopharyngodon idellus) - Jie Chen; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Rui-Nan Zhang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

The effect of selenium on the intestinal health of juvenile grass carp based on the ERS-autophagy pathway - Ya Wang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Enhancing safe and effective treatment of carbapenem-resistant Klebsiella pneumoniae with polymyxin B-loaded dendritic nanoparticles - Wen Zhong; Yuyin Fu; Xukun Liao; Na Xu; Lingyi Shen; Jinglin Wu; Dan Zheng; Yadi Zhou; Lin Tan; Binyi Xia; Xinghua Fan; Meng Zhou; et al. (Chemical Engineering Journal, 2024)

Surface reconstruction of defect-engineered MIL-88@Fe2O3 p-n heterojunction for enhanced electrocatalytic water and urea oxidation - Bo Huang; Jianan Wang; Dongling Xie; Qiuping Huang; Dan Wen; Xueqin Zeng; Dunmin Lin; Wenhan Guo; Huachuan Sun; Fengyu Xie (Chemical Engineering Journal, 2024)

Analysis on typical characteristics and causes of coal mine gas explosion accidents in China - Zhijun Lin; Min Li; Shan He; Deming Wang; Shiliang Shi; Dan Wang (Environmental Science and Pollution Research, 2024)

The role of pantothenic acid in alleviating hypoxia-induced liver injury of sub-adult grass carp (Ctenopharyngodon idellus): Possible mechanisms and implication - Yan Xia; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Jia-Yong Tang; Rui-Nan Zhang; Lu Zhang; Hai-Feng Mi; Lin Feng (Aquaculture, 2024)

MCT1-mediated transport of valeric acid promotes porcine preimplantation embryo development by improving mitochondrial function and inhibiting the autophagic AMPK-ULK1 pathway - Xiu-Li Zhang; Zhi-Yong An; Gao-Jie Lu; Tuo Zhang; Cheng-Wei Liu; Meng-Qi Liu; Qing-Xin Wei; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Fruits’ cold tolerance: a review of mechanisms and methods - Jian-Lin He; Gang-Shuai Liu; Xiao-Dan Zhao; Lan-Ting Xiang; Shi-Yin Xie; Yun-Xiang Wang; Da-Qi Fu (Postharvest Biology and Technology, 2024)

Expression of a novel hydrolase MhpC in Brevibacillus parabrevis BCP-09 and its characteristics for degrading synthetic pyrethroids - Yingyue Zhang; Dan Xiang; Jie Tang; Chuanning Peng; Siqi Chen; Siqi Huang; Qi Wen; Lin Liu; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Pesticide Biochemistry and Physiology, 2024)

10Be exposure age data reveals last Glacial ice sheet histories in the Larsemann Hills of East Antarctica - Luming Chen; Zhigang Zhang; Jingxue Guo; Lin Li; Xueyuan Tang; Dan Zhao; Hongmei Zhang; Yi Lin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

First identification of Carboniferous mafic dikes during a period of arc magmatic quiescence in the Northern Qiangtang terrane, central Tibet: Back-arc extension and implications for opening of the Xijir Ulan Ocean - Zhi-Wei Yu; Wei Dan; Qiang Wang; Xiu-Zheng Zhang; Jun Wang; Bing Chen; Lin Gong (Lithos, 2024)

Steam gasification of lime dried sewage sludge: Effects of temperature and addition of lime - Dan Lin; Wantong Kai; Xing Xie; Alexander Kozlov; Maxim Penzik; Bin Li (Fuel, 2024)

Declined flesh quality resulting from niacin deficiency is associated with elevated glycolysis and impaired mitochondrial homeostasis in grass carp (Ctenopharyngodon idella) - Shun-Shi Sun; Lin Feng; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Xiao-Qiu Zhou; Pei Wu (Food Chemistry, 2024)

Transcriptomics to evaluate the influence mechanisms of ethanol on the ester production of Wickerhamomyces anomalus with the induction of lactic acid - Wenqin Cai; Yin Wan; Yanru Chen; Haowei Fan; Mengxiang Li; Shengwen Wu; Pei Lin; Tingting Zeng; Huibo Luo; Dan Huang; Guiming Fu (Food Microbiology, 2024)

Small molecule perylene diimide derivatives with different bay site modifications as cathode interface layers for organic solar cells - Yanyan Wang; Dan Zhou; Senmei Lan; Jianwei Quan; Fang Wang; Lin Hu; Ruizhi Lv; Yujie Pu; Haitao Xu; Yongfen Tong; Bin Hu; Zhentian Xu; et al. (Chemical Engineering Journal, 2024)

Perovskite intermediate phase FAPbBr3·DMSO assisted in-situ growth of FAPbBr3 polycrystalline wafer for X-ray detection and imaging - Dan Liu; Wei Jiang; Siyin Dong; Haipeng Di; Haibin Li; Zhenning Xing; Hongbing Wang; Jiwei Ren; Xiaojia Zheng; Lin Lei; Yiying Zhao (Chemical Engineering Journal, 2024)

Pre-deposited biochar enhanced flux stabilization and pollutant removal in gravity-driven membrane system - Caihong Liu; Qingyang Zuo; Jingjun Bo; Haiqing Chang; Lin Li; Qiang He; Dan Song; Jun Ma (Chemical Engineering Journal, 2024)

Identification of Different Varieties of Oil Peony Seeds Combining ICP-MS with Chemometrics and Assessment of Associated Health Risk - Shuya Li; Dezhang Zhao; Yuan Shen; Lei Dai; Weihan Qin; Dan Yang; Yaxuan Li; Lin Yang; Yan Li; Dan He (Biological Trace Element Research, 2024)

New perspectives on the role of vitamin D in the mucosal barrier system of fish gills infected with Flavobacterium columnare - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Lu Zhang; Hai-Feng Mi; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2024)

Atractylenolide I ameliorates sepsis-induced cardiomyocyte injury by inhibiting macrophage polarization through the modulation of the PARP1/NLRP3 signaling pathway - Dan Wang; Zhiqiang Lin; Yiqing Zhou; Meixia Su; Haiwang Zhang; Lixia Yu; Minghui Li (Tissue and Cell, 2024)

Spatio-temporal patterns and population exposure risks of urban heat island in megacity Shanghai, China - Dan Liu; Rui Zhou; Qun Ma; Tianxing He; Xuening Fang; Lishan Xiao; Yina Hu; Jie Li; Lin Shao; Jun Gao (Sustainable Cities and Society, 2024)

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

Assessment of chlorine and hydrogen peroxide on airborne bacteria: Disinfection efficiency and induction of antibiotic resistance - Siyi Wang; Zhiwei Shao; Guang Chen; Bingjie Lin; Dan Li; Jianmin Chen (Journal of Hazardous Materials, 2024)

Effective or useless? Assessing the impact of park entrance addition policy on green space services from the 15-min city perspective - Qinyu Cui; Lin Tan; Haoran Ma; Xuelin Wei; Shengao Yi; Dan Zhao; Huiyuan Lu; Peiqun Lin (Journal of Cleaner Production, 2024)

Preparation and characterization of quercetin@ZIF-L/GO@AgNPs nanocomposite film for room-temperature strawberry preservation - Chen Yin; Xin Ding; Zhihao Lin; Jiayong Cao; Weiye Shi; Jian Wang; Dan Xu; Donghui Xu; Yuan Liu; Guangyang Liu (Food Chemistry, 2024)

Investigations of the highly efficient processing technique, chemical constituents, and anti-inflammatory effect of N-ethyl-2-pyrrolidinone-substituted flavan-3-ol (EPSF)-enriched white tea - Jianjian Gao; Dan Chen; Dongchao Xie; Jiakun Peng; Zhengyan Hu; Zhi Lin; Weidong Dai (Food Chemistry, 2024)

Comprehensive comparison of aroma profiles and chiral free and glycosidically bound volatiles in Fujian and Yunnan white teas - Han Yan; Wei-Xuan Li; Ying-Lin Zhu; Zhi-Yuan Lin; Dan Chen; Yue Zhang; Hai-Peng Lv; Wei-Dong Dai; De-Jiang Ni; Zhi Lin; Yin Zhu (Food Chemistry, 2024)

Construction and characterization of a novel Myr-OSADS-CIn micelle for enhanced stability and bioavailability of myricetin - Zhi-Yuan Nie; Xue-Ying Li; Ying-Ying Chen; Yuan-Yuan Deng; Dan-Dan Kuang; Yu-Lin Sun; Huan-Huan Xiao; Qiang-Ming Li; Jian-Ping Luo; Xue-Qiang Zha (Food Bioscience, 2024)

Exploring the novel benefits of leucine: Protecting nitrite-induced liver damage in sub-adult grass carp (Ctenopharyngodon idella) through regulating mitochondria quality control - Lu-Lu Zhen; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

pH-responsive coacervate with adrenergic nerve blockade function inhibits triple-negative breast cancer metastasis by blocking nerve-tumor-immune loop - Jieting Chen; Chaoming Mei; Yan Tan; Fan Yang; Shirui Yang; Xin Wen; Xin Peng; Yong Lin; Dan Li (Chemical Engineering Journal, 2024)

Human Amniotic Epithelial Stem Cells Alleviate Autoimmune Premature Ovarian Insufficiency in Mice by Targeting Granulosa Cells via AKT/ERK Pathways - Xiaohang Ye; Yifeng Lin; Yanyun Ying; Xuezhi Shen; Feida Ni; Feixia Wang; Jianpeng Chen; Wei Zhao; Xiaoming Yu; Dan Zhang; Yifeng Liu (Stem Cell Reviews and Reports, 2024)
Autoimmune factors play an important role in premature ovarian insufficiency (POI). Human amniotic epithelial stem cells (hAESCs) have recently shown promising treatment effects on chemotherapy-induced POI. However, the therapeutic efficacy and underlying mechanisms of hAESCs in autoimmune POI remain to be investigated. In this study, we showed for the first time that intravenous transplantation of hAESCs could reside in the ovary of zona pellucida 3 peptide (pZP3) induced autoimmune POI mice model for at least 4 weeks. hAESCs could improve ovarian function and fertility, alleviate inflammation and reduce apoptosis of granulosa cells (GCs) in autoimmune POI mice. The transcriptome analysis of mice ovaries and in vitro co-cultivation experiments suggest that activation of the AKT and ERK pathways may be the key mechanism in the therapeutic effect of hAESCs. Our work provides the theoretical and experimental foundation for optimizing the administration of hAESCs, as well as the clinical application of hAESCs in autoimmune POI patients. Graphical Abstract

SIRT1-Mediated HMGB1 Deacetylation Suppresses Neutrophil Extracellular Traps Related to Blood–Brain Barrier Impairment After Cerebral Venous Thrombosis - Shuwen Mu; Ziqi Li; Long Lin; Di Wang; Fei Yang; Li Chen; Liang Xian; Kunzhe Lin; Yinghong Lin; Dan Ye; Yang Yang; Liangfeng Wei; et al. (Molecular Neurobiology, 2024)

Correction to: The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Prediction of Pier Scour Depth under Extreme Typhoon Storm Tide - Zongyu Li; Weiwei Lin; Dongdong Chu; Feng Liu; Zhilin Sun; Wankang Yang; Hanming Huang; Dan Xu (Journal of Marine Science and Engineering, 2024)
The Western Pacific region is highly vulnerable to typhoon storm surge disasters, with localized erosion posing a particularly prominent issue for coastal marine structures. The prevalence of extreme typhoon storm surges poses a significant threat to the safety of engineering projects in these areas. In this study, a parameterized wind field model with precise calculation of wind speed was employed to establish a numerical model for typhoon storm tides. Based on the Western Pacific typhoon data from 1949 to 2023, hydraulic simulations were conducted for Hangzhou Bay, Xiangshan Port, and Yueqing Bay, revealing maximum flow velocities of 4.5 m/s, 1.95 m/s, and 2.09 m/s, respectively. These velocities exceeded the maximum possible tidal flow by 0.47–1.17 m/s. Additionally, using Sun’s velocity formula, the initiation flow velocities were calculated to be 1.85 m/s, 1.81 m/s, and 2.06 m/s for the aforementioned locations. Through localized erosion tests conducted around typical bridge piers and the subsequent application of similarity criteria, the maximum depth of localized erosion in the study area was determined to range from 2.16 m to 16.1 m, which corresponds to 1.1–2.3 times the scour caused by the maximum tidal flow scenario. A comparison of the erosion test results with calculations based on several formulas demonstrated that the scour prediction formula proposed by Sun exhibited the highest accuracy. This study supplements the understanding of the impact of typhoon storm surges on bridge pier erosion and provides a scientific basis for the design of bridge foundations.

Taurine prevented the decline of fillet quality and muscle antioxidant capacity in on-growing grass carp (Ctenopharyngodon idella) fed non-fishmeal diet - Shun-Shi Sun; Liang-Chao Yan; Lin Feng; Wei-Dan Jiang; Yang Liu; Ling Tang; Pei Wu; Xiao-Qiu Zhou (Aquaculture, 2024)

Association between ambient air pollution and dry eye symptoms among Chinese individuals during the COVID-19 pandemic: A national-based study - Jia-Yan Kai; Yi-Bo Wu; Xing-Xuan Dong; Yi-Fan Miao; Dan-Lin Li; Dan-Ning Hu; Carla Lanca; Andrzej Grzybowski; Chen-Wei Pan (Science of The Total Environment, 2024)

Enhancing the phytoextraction efficiency of heavy metals in acidic and alkaline soils by Sedum alfredii Hance: A study on the synergistic effect of plant growth regulator and plant growth-promoting bacteria - Zhiqin Chen; Qizhen Liu; Dan Chen; Yingjie Wu; Yasir Hamid; Qiang Lin; Shijun Zhang; Ying Feng; Zhenli He; Xianyuan Yin; Xiaoe Yang (Science of The Total Environment, 2024)

Critical insights into the Hormesis of antibiotic resistome in saline soil: Implications from salinity regulation - Jianbin Sun; Dan Zhang; Shuang Peng; Xiaoqian Yang; Qingqing Hua; Wei Wang; Yiming Wang; Xiangui Lin (Journal of Hazardous Materials, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

Safety assessment of polypropylene self-heating food container: The release of microplastics and volatile organic compounds - Can Xu; Jia-ling Hu; Ben Dong; Qin-bao Lin; Si-liang Wu; Jie Chen; Jing Wang; Dan Li; Huai-ning Zhong (Food Packaging and Shelf Life, 2024)

Priming effects of surface soil organic carbon decreased with warming: a global meta-analysis - Hongxin Dong; Junjie Lin; Jiayu Lu; Lujun Li; Zhiguo Yu; Amit Kumar; Qin Zhang; Dan Liu; Beibei Chen (Plant and Soil, 2024)

Association between pre-diagnosis recreational physical activity and risk of breast cancer recurrence: the California Teachers Study - Dan Lin; Cheryl L. Thompson; Alaina Demalis; Rebecca Derbes; Laila Al-Shaar; Emma S. Spielfogel; Kathleen M. Sturgeon (Cancer Causes & Control, 2024)

Molecular phylogenetic analysis of the East Asian hemicultrine fishes ( Teleostei: Cyprinidae: Xenocypridinae ), with suggestions to their generic classification and redescription of the recently described species Hemiculter yungaoi Vasil'eva et al. 2022 - Qiaoling Deng; Mingzheng Li; Dan Yu; Lin Chen; Wenjing Li; Xingwei Cai; Huanzhang Liu (Journal of Fish Biology, 2024)
The hemicultrine fishes are a group of small‐sized cyprinids, widely distributed but endemic to East Asian rivers and lakes. Till now, the taxonomic boundaries and relationships within this group remain poorly explored. In the present study, we study the phylogeny of this group, providing suggestions for classification of the hemicultrine group. Using two mitochondrial and three nuclear genes, and samples representing all genera, our results showed that the group consists of seven major lineages, of which four ( Hemiculterella , Hainania , Pseudolaubuca , and Anabarilius ) were monophyletic and three ( Hemiculter , Toxabramis , and Pseudohemiculter ) were not. Based on the phylogenetic tree, we redefined the genera. We revive the genus Siniichthys , which has three species, Siniichthys bleekeri , Siniichthys lucidus , and S. varpachovskii , that were previously treated as members of the genus Hemiculter but showed distant relationships to the genus Hemiculter in our phylogenetic tree. With the new results, a diagnostic key for clades of the hemicultrine group is provided. Furthermore, we provide more detailed information on diagnostic features of the recently described species Hemiculter yungaoi (Vasil'eva et al., 2022). This work will facilitate future systematic studies, pave the way for evolutionary studies, and provide valuable information for the urgent conservation of hemicultrine fishes.

Complete long-term monitoring of greenhouse gas emissions from a full-scale industrial wastewater treatment plant with different cover configurations - Qinyi Wang; Yangyue Sheng; Yili Zhang; Xinrun Zhong; Hui Liu; Zhengfeng Huang; Dan Li; Hao Wu; Yuanzhi Ni; Junqi Zhang; Weiqing Lin; Kaipei Qiu; et al. (Journal of Environmental Management, 2024)

LCQDs modified Bi2MoO6 hydrangea composite photocatalyst for tetracycline degradation from wastewater: Performance, efficiency, and adsorption synergistic photocatalytic mechanism - Dan Xu; Hong Yan; Fen Li; Yuchen Lin; Yuanbo Zhang; Cailian Yu (Journal of Environmental Chemical Engineering, 2024)

BmNPV p35 regulates apoptosis in Bombyx mori via a novel target of interaction with the BmVDAC2-BmRACK1 complex - Lin-Bao Zhu; Han-Dan Zhu; Zhi-Hao Huang; Hui-Hua Cao; Sadaf Ayaz; Jia-Yue Yang; Xi-Ya Chen; Ying Zhang; Shi-Huo Liu; Jia-Ping Xu (Insect Biochemistry and Molecular Biology, 2024)

A lychee fermentate with enriched acetate but lowered GABA attenuates DSS-induced colitis by reinforcing gut barrier function and modulating intestinal microbiota - Rui Huang; Hong Yao; Suying Ji; Junfeng Wu; Qingran Lin; Tanushree B. Gupta; Dan Gan; Xiyang Wu (Food Bioscience, 2024)

Constructing blocked-nanolayer by surface charge inversion over anion exchange membrane for improved antifouling performance - Dan Lu; Hongyu Jin; Yunchen Mao; Yukun Qian; Ge Li; Jing Wang; Ying Mei; Zhikan Yao; Zhuofan Gao; Lin Zhang (Desalination, 2024)

Embryogenic callus induction, proliferation, protoplast isolation, and PEG induced fusion in Camellia oleifera - Xian-Yu He; Lin-Jie Xu; Xiang-Shuai Xu; Dan-Dan Yi; Si-Lu Hou; De-Yi Yuan; Shi-Xin Xiao (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

RETRACTED ARTICLE: Micafungin exerts antitumor effect on breast cancer and osteosarcoma through preventing EMT in tumor cells in an USP7/AKT/GSK-3β pathway-dependent manner - Qian-Lin Wang; Li Wang; Qiong-Yu Li; Hui-Yin Li; Ling Lin; Dan Wei; Jin-Yun Xu; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Zinc-a2-Glycoprotein Acts as a Component of PNN to Protect Hippocampal Neurons from Apoptosis - Kewei Chang; Liyan Lin; Tingting Cui; Hao Zhao; Jiaxin Li; Chang Liu; Dan Gao; Shemin Lu (Molecular Neurobiology, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Spatially confined CuFe2O4 nanosphere in N/O-codoped porous carbon mimetics for triple-mode sensing of antibiotics and visual detection of neurotransmitters in biofluids - Ying Lin; Wan-Wan Shao; Dan Wu; Tong Zhang; Dan-Ni Fei; Ya-Nan Kong; Yi-Fan Gao; Shu-Chang Zhao; Rui-Lin Liu (Analytica Chimica Acta, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Unlocking the potential of odor-induced sugar reduction: an updated review of the underlying mechanisms, substance selections, and technical methodologies - Lin Zhu; Fei Pan; Felix Stöppelmann; Jiaqi Liang; Dan Qin; Can Xiang; Marina Rigling; Lea Hannemann; Tim Wagner; Youfeng Zhang; Yanyan Zhang (Trends in Food Science & Technology, 2024)

Life cycle assessment of traditional and innovative sludge management scenarios in Australia: Focusing on environmental impacts, energy balance, and economic benefits - Zhenyao Wang; Xuan Li; Huan Liu; Jibin Li; Dan Cristian Vodnar; Carol Sze Ki Lin; Qilin Wang (Resources, Conservation and Recycling, 2024)

Hypoxia leads to gill endoplasmic reticulum stress and disruption of mitochondrial homeostasis in grass carp (Ctenopharyngodon idella): Mitigation effect of thiamine - Ke-Jing Huang; Lin Feng; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Xiao-Qiu Zhou; Wei-Dan Jiang (Journal of Hazardous Materials, 2024)

Energy-efficient bubble aeration guided by bubble dynamics model: From bubble formation at submerged orifice to oxygen utilization during uprising - Zhen Chen; Jiaao Yu; Yang Huo; Jiancong Liu; Dan Xiao; Lipeng He; Shanshan Lin; Wei Fan; Mingxin Huo (Journal of Cleaner Production, 2024)

Strengthening the diffusion of sodium ions by interactions between gum Arabic and oral mucin - Yanlei Li; Ruiting Chang; Duanyang Zhu; Lin Lu; Zhiming Gao; Yuehan Wu; Wenxin Jiang; Dan Yuan (Food Hydrocolloids, 2024)

From growth promotion to intestinal inflammation alleviation: Unraveling the potential role of Lactobacillus rhamnosus GCC-3 in juvenile grass carp (Ctenopharyngodon idella) - Zhen Chen; Lin Feng; Pei Wu; Wei-Dan Jiang; Jun Jiang; Xiao-Qiu Zhou; Yang Liu (Fish & Shellfish Immunology, 2024)

Driving soil N2O emissions under nitrogen application by soil environmental factor changes in garlic-maize rotation systems - Dan Liu; Chi Ma; Yang Liu; Qin Mo; Wei Lin; Wenjing Li; Hui Li; Baoping Yang; Ruixia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Landfill leachate treatment by direct contact membrane distillation: Impacts of landfill age on contaminant removal performance, membrane fouling and scaling - Zhimeng Yang; Songze Lin; Linxiong Ye; Dan Qu; Haiyang Yang; Haiqing Chang; Huarong Yu; Zhongsen Yan; Hongwei Rong; Fangshu Qu (Desalination, 2024)

Self-supporting honeycomb coaxial carbon fibers: A new strategy to achieve an efficient hydrogen evolution reaction both in base and acid media - Jiaqi Lin; Duanduan Yin; Wurigamula He; Lili Wang; Bin Yue; Tianqi Wang; Dan Li; Ce Han; Xiangting Dong (Chemical Engineering Journal, 2024)

Regulating photoluminescence through single-crystal-to-single-crystal transformation of solvent-containing zero-dimensional hybrid metal halide isomers - Ying-Chen Peng; Jian-Ce Jin; Sheng-Hua Zhou; Hao-Wei Lin; Dan-Dan Huang; Zhong-Hua Deng; Yu Dong; Hao-Jie Xu; Ke-Zhao Du; Ze-Ping Wang; Xiao-Ying Huang (Chemical Engineering Journal, 2024)

Removing Efficiency and Mechanism of Ciprofloxacin from Aqueous Solution Using Rectorite - Dan Su; Jingyi Huang; Yang Li; Lin Chen; Yingru Wang (Water, Air, & Soil Pollution, 2024)

The emerging role of zinc on alleviating inflammatory responses and enhancing immunity in grass carp (Ctenopharyngodon idella) - Xin Zeng; Zheng-Xing Song; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Juan Yang; Lin Feng (Aquaculture, 2024)

Comparison of life cycle assessment between hydrogen production from silicon waste and alkaline water electrolysis - Shengqiang Yang; Dan Mao; Zhiqiang Yu; Wenhui Ma; Lin Ma; Xiufeng Li; Fengshuo Xi (Science of The Total Environment, 2024)

Atmospheric CO2 and 14CO2 observations at the northern foot of the Qinling Mountains in China: Temporal characteristics and source quantification - Wanyu Liu; Zhenchuan Niu; Xue Feng; Weijian Zhou; Dan Liang; Mengni Lyu; Guowei Wang; Xuefeng Lu; Lin Liu; Jocelyn C. Turnbull (Science of The Total Environment, 2024)

Degradation of prometryn during UV/persulfate process: Kinetics and disinfection by-product formation - Chen-Yan Hu; Hao Liu; Ling Xu; Yi-Li Lin; Qiang-Bing Wang; Dan-Dan Huang; Yi-Hui Wu; Zi-Yi Dong; Sheng-Jie Ji (Journal of Water Process Engineering, 2024)

Boron-mediated amelioration of copper toxicity in Citrus sinensis seedlings involved reduced concentrations of copper in leaves and roots and their cell walls rather than increased copper fractions in their cell walls - Huan-Huan Chen; Zhi-Chao Zheng; Dan Hua; Xu-Feng Chen; Zeng-Rong Huang; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2024)

Dynamic changes in butyrate levels regulate satellite cell homeostasis by preventing spontaneous activation during aging - Shujie Chen; Liujing Huang; Bingdong Liu; Huimin Duan; Ze Li; Yifan Liu; Hu Li; Xiang Fu; Jingchao Lin; Yinlan Xu; Li Liu; Dan Wan; et al. (Science China Life Sciences, 2024)

Transplantation of MiR-28-5p-Modified BMSCs Promotes Functional Recovery After Spinal Cord Injury - Zhen Li; Haitao Su; Guandai Lin; Kai Wang; Yongming Huang; Yaqian Wen; Dan Luo; Yu Hou; Xuewei Cao; Jiaxian Weng; Dingkun Lin; Le Wang; et al. (Molecular Neurobiology, 2024)
Traumatic spinal cord injury (TSCI) is a prevalent central nervous system condition that imposes a significant burden on both families and society, affecting more than 2 million people worldwide. Recently, there has been increasing interest in bone marrow mesenchymal stem cell (BMSC) transplantation as a promising treatment for spinal cord injury (SCI) due to their accessibility and low immunogenicity. However, the mere transplantation of BMSCs has limited capacity to directly participate in the repair of host spinal cord nerve function. MiR-28-5p, identified as a key differentially expressed miRNA in spinal cord ischemia–reperfusion injury, exhibits differential expression and regulation in various neurological diseases. Nevertheless, its involvement in this process and its specific regulatory mechanisms in SCI remain unclear. Therefore, this study aimed to investigate the potential mechanisms through which miR-28-5p promotes the neuronal differentiation of BMSCs both in vivo and in vitro. Our results indicate that miR-28-5p may directly target Notch1, thereby facilitating the neuronal differentiation of BMSCs in vitro . Furthermore, the transplantation of lentivirus-mediated miR-28-5p-overexpressed BMSCs into SCI rats effectively improved footprint tests and Basso, Beattie, and Bresnahan (BBB) scores, ameliorated histological morphology (hematoxylin–eosin [HE] and Nissl staining), promoted axonal regeneration (MAP2 and growth-associated protein 43 [GAP43]), and facilitated axonal remyelination (myelin basic protein [MBP]). These findings may suggest that miR-28-5p-modified BMSCs could serve as a therapeutic target to enhance the behavioral and neurological recovery of SCI rats.

ESG implementation, public environmental concern, and corporate green technology innovation: analysis based on the background of China's "Dual Carbon" targets - Binghong Lin; Bingxiang Li; Dan Zhang (Environment, Development and Sustainability, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

New perspectives on the mechanism of curcumin in the gill mucosal immune barrier damaged by ochratoxin A in juvenile grass carp (Ctenopharyngodon idella) - Piao Zhao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; He-Qun Shi; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2024)

Reduction of antigenicity and emulsibility improvement of ovalbumin by dielectric-barrier discharge plasma treatment induced structure modification - Pan-Pan Tang; Lin-Lin Zhang; Yu-Xin Xiong; Dan-Dan Jiang; Xiu-Bin Liu; Jun-Hu Cheng; Rana Muhammad Aadil; Zhi-Wei Liu (Innovative Food Science & Emerging Technologies, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

Identification of key factors affecting neonicotinoid residues in crops and risk of dietary exposure - Wenfei Yu; Ruxin Wu; Li Zhang; Yangzhong Pan; Jun Ling; Dan Yang; Jiajia Qu; Zhen Tao; Ruirui Meng; Yuexing Shen; Jingtong Yu; Nan Lin; et al. (Environmental Pollution, 2024)

Norepinephrine-induced hydrophilic Pd aerogels with photothermal-boosted multienzyme-like activity for chemodynamic therapy of MRSA infections - Minghui Wang; Na Li; Nanyun Lin; Yingying Wu; Wei Zhou; Ximei Sun; Peixian Wu; Qian Fu; Wenjie Wang; Zheng Liu; Shuiyuan He; Mengyu Zhou; et al. (Chemical Engineering Journal, 2024)

Integrating water and insect pest management in agriculture - Po-An Lin; Sulav Paudel; Pin-Chu Lai; Raj K. GC; Dan-Hong Yang; Gary W. Felton (Journal of Pest Science, 2024)

Microfluidic platform for omics analysis on single cells with diverse morphology and size: A review - Shujin Lin; Dan Feng; Xiao Han; Ling Li; Yao Lin; Haibing Gao (Analytica Chimica Acta, 2024)

On the formation of postnoon auroral bright spots during weak substorm activity - Su Zhou; Yongzhi Cai; Ping Ou; Lin Zhu; Dan Wu (Advances in Space Research, 2024)

Cancer screening in hospitalized ischemic stroke patients: a multicenter study focused on multiparametric analysis to improve management of occult cancers - Jie Fang; Jielong Wu; Ganji Hong; Liangcheng Zheng; Lu Yu; Xiuping Liu; Pan Lin; Zhenzhen Yu; Dan Chen; Qing Lin; Chuya Jing; Qiuhong Zhang; et al. (EPMA Journal, 2024)

Mechanism of deltamethrin biodegradation by Brevibacillus parabrevis BCP-09 with proteomic methods. - Yingyue Zhang; Jie Tang; Su Wang; Xuerui Zhou; Chuanning Peng; Hu Zhou; Dan Wang; Haoran Lin; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Chemosphere, 2024)

Immunomodulation of potassium diformate in juvenile grass carp (Ctenopharyngodon idella) after Aeromonas hydrophila infection: T-cell differentiation and cytokine production - Qiu-Ping Chai; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2024)

How does urban thermal environmental factors impact diurnal cycle of land surface temperature? A multi-dimensional and multi-granularity perspective - Zhongli Lin; Hanqiu Xu; Xiong Yao; Changxin Yang; Dan Ye (Sustainable Cities and Society, 2024)

Potential causal links and mediation pathway between urban greenness and lung cancer mortality: Result from a large cohort (2009 to 2020) - Wenjing Wu; Gonghua Wu; Jing Wei; Wayne R Lawrence; Xinlei Deng; Yuqin Zhang; Shirui Chen; Ying Wang; Xiao Lin; Dan Chen; Xinling Ruan; Qiaoxuan Lin; et al. (Sustainable Cities and Society, 2024)

Mitochondrial coding genes mediate insecticide tolerance in the oriental fruit fly, Bactrocera dorsalis (Hendel) - Shi-Die Jiang; Lei Wang; Lin Wang; Jun Sun; Jin-Jun Wang; Dan-Dan Wei (Pesticide Biochemistry and Physiology, 2024)

The Earth Summit Mission-2022: Successful ozone soundings contribute to source identification in the north Mt. Qomolangma region - Jinqiang Zhang; Chunxiang Ye; Yuejian Xuan; Zhixuan Bai; Weili Lin; Dan Li; Lingkun Ran; Baofeng Jiao; Yaoming Ma; Weiqiang Ma; Nan Yao; Yunshu Zeng; et al. (Journal of Environmental Sciences, 2024)

A facile, green strategy to synthesize N/P self-doped, biomass-derived, hierarchical porous carbon from water hyacinth for efficient VOCs adsorption - Chenglong Yu; Junhui Dan; Zewei Liu; Jinliang Wang; Jiayang Wang; Hansun Fang; Fayin Lai; Danping Li; Lin Li; Fengying Li; Chunhuo Zhou; Bichun Huang (Fuel, 2024)

Enocyanin alleviates experimental colitis and restores gut microbiota homeostasis as functional foods - Cang Li; Yu Huang; Meilin Qin; Qian He; Zhuoyu Lin; Xiaojing Zhang; Hao Ren; Dan Xu; Xiaoping Liao; Yahong Liu; Jian Sun (Food Bioscience, 2024)

Hydrogeochemistry and indicators of flowback and produced water from wells that are hydraulically fractured with recycled wastewater: A case study of the Changning gas field in the Sichuan Basin - Dan Liu; Wei Xiong; Xiaowei Zhang; Wei Guo; Wanting Li; Jinliang Gao; Lixia Kang; Yuyang Liu; Zhaoyuan Shao; Lin Zhang; Cong Yu; Fengrong Liao; et al. (Applied Geochemistry, 2024)

Foliar N 2 O emissions constitute a significant source to atmosphere - Shuping Qin; Yaxing Pang; Huixian Hu; Ting Liu; Dan Yuan; Timothy Clough; Nicole Wrage‐Mönnig; Jiafa Luo; Shungui Zhou; Lin Ma; Chunsheng Hu; Oene Oenema (Global Change Biology, 2024)
Nitrous oxide (N 2 O) is a potent greenhouse gas and causes stratospheric ozone depletion. While the emissions of N 2 O from soil are widely recognized, recent research has shown that terrestrial plants may also emit N 2 O from their leaves under controlled laboratory conditions. However, it is unclear whether foliar N 2 O emissions are universal across varying plant taxa, what the global significance of foliar N 2 O emissions is, and how the foliage produces N 2 O in situ. Here we investigated the abilities of 25 common plant taxa, including trees, shrubs and herbs, to emit N 2 O under in situ conditions. Using 15 N isotopic labeling, we demonstrated that the foliage‐emitted N 2 O was predominantly derived from nitrate. Moreover, by selectively injecting biocide in conjunction with the isolating and back‐inoculating of endophytes, we demonstrated that the foliar N 2 O emissions were driven by endophytic bacteria. The seasonal N 2 O emission rates ranged from 3.2 to 9.2 ng N 2 O–N g −1 dried foliage h −1 . Extrapolating these emission rates to global foliar biomass and plant N uptake, we estimated global foliar N 2 O emission to be 1.21 and 1.01 Tg N 2 O–N year −1 , respectively. These estimates account for 6%–7% of the current global annual N 2 O emission of 17 Tg N 2 O–N year −1 , indicating that in situ foliar N 2 O emission is a universal process for terrestrial plants and contributes significantly to the global N 2 O inventory. This finding highlights the importance of measuring foliar N 2 O emissions in future studies to enable the accurate assigning of mechanisms and the development of effective mitigation.

Effects of field-aging on the impact of biochar on herbicide fate and microbial community structure in the soil environment - Hongguang Cheng; Dan Xing; Gratien Twagirayezu; Shan Lin; Shangyi Gu; Chenglong Tu; Paul W. Hill; David R. Chadwick; Davey L. Jones (Chemosphere, 2024)

Effect of dietary supplementation of the quenching enzyme AiiO-AIO6 on growth performance, digestion and absorption capacity, and intestinal barrier function of grass carp (Ctenopharyngodon idella) - Yun Wang; Pei Wu; Wei-Dan Jiang; Yang Liu; Mei-Hong Ren; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Cobalt-induced apoptosis of cochlear organotypic cultures and HEI-OC1 cells is mediated by Dicer - Xuexin Lin; Liling Li; Jia Luo; Dan Chen; Jingqian Tan; Peng Li (NeuroToxicology, 2024)

Understanding the impact of cultivated land-use changes on China's grain production potential and policy implications: A perspective of non-agriculturalization, non-grainization, and marginalization - Dan Lu; Zhanpeng Wang; Kangchuan Su; Yajuan Zhou; Xinxin Li; Aiwen Lin (Journal of Cleaner Production, 2024)

Overview of life cycle assessment of recycling end-of-life photovoltaic panels: A case study of crystalline silicon photovoltaic panels - Dan Mao; Shengqiang Yang; Lin Ma; Wenhui Ma; Zhiqiang Yu; Fengshuo Xi; Jie Yu (Journal of Cleaner Production, 2024)

Screening and degradation characteristics of plastic-degrading microorganisms in film-mulched vegetable soil - Zhenyan Lin; Tuo Jin; Xin Xu; Xiao Yin; Dan Zhang; Mengjiao Geng; Chunyu Pang; Gongwen Luo; Lizhi Xiong; Jianwei Peng; Jiangchi Fei (International Biodeterioration & Biodegradation, 2024)

Glycogen plays a key role in survival of Salmonella Typhimurium on dry surfaces and in low-moisture foods - Zejia Lin; Shaoqian Jiang; Ye Htut Zwe; Kexin Zhang; Dan Li (Food Research International, 2024)

Gaseous signaling molecule H2S as a multitasking signal molecule in ROS metabolism of Oryza sativa under thiocyanate (SCN−) pollution - Yu-Xi Feng; Peng Tian; Yu-Juan Lin; Dan-Yang Cao; Cheng-Zhi Li; Abid Ullah (Environmental Pollution, 2024)

Coconut husk-derived nanocellulose as reinforcing additives in thermal-responsive hydrogels - Yihao Leow; Yi Jian Boo; Ming Lin; Ying Chuan Tan; Rubayn Zhi Rong Goh; Qiang Zhu; Xian Jun Loh; Kun Xue; Dan Kai (Carbohydrate Polymers, 2024)

Fluorescent starch-based hydrogel with cellulose nanofibrils and carbon dots for simultaneous adsorption and detection of Pb(II) - Zhixu Zhang; Zhengwu Huang; Dan Qin; Dongbo Liu; Xin Guo; Haiyan Lin (Carbohydrate Polymers, 2024)

Health risks and environmental influence of volatile organic compounds (VOCs) in a residential area near an industrial park in Southeast China - Dan Liao; Lei Wang; Yanyun Wang; Chengqi Lin; Jinlei Chen; Huabin Huang; Zhixia Zhuang; Sung-Deuk Choi; Youwei Hong (Atmospheric Pollution Research, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Isalo scorpion Cytotoxic peptide (IsCT) improved the physical barrier of the intestine on on-growing grass carp (Ctenopharyngodon idella) - Chong Zhang; Qi-Yu Hu; Lin Feng; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Jiang Li; Xiao-Qiu Zhou; Wei-Dan Jiang (Aquaculture, 2023)

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

The variability in CYP3A4 activity determines the metabolic kinetic characteristics of ketamine - Mengfang Li; Qingqing Li; Dan Lin; Xiang Zheng; Lehao Jin; Jianping Cai; Guoxin Hu; Jianchang Qian (Toxicology, 2023)

Overexpression of ABCB transporter genes confer multiple insecticide tolerances in Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) - Lin Wang; Shu-Hang Tian; Wei Zhao; Jin-Jun Wang; Dan-Dan Wei (Pesticide Biochemistry and Physiology, 2023)

Solar wind dynamic pressure enhancements in upstream region near Mars - Dan Zhao; Jianpeng Guo; Yichun Hong; Weiduo Meng; Hui Huang; Haibo Lin; Xianghan Wang; Yan Chen; Linxia He; Yong Wei; Libo Liu (Icarus, 2023)

Bioinspired construction of histidine-doped porphyrin covalent organic framework nanozyme with enhanced peroxidase-like activity for sensitive uric acid detection - Chao Zhong; Cong Hu; Dan Ouyang; Akang Dan; Yanhui Zhong; Zongwei Cai; Zian Lin (Chemical Engineering Journal, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Analysis of volatile organic compounds and potential odour compounds in food contact paperboard using headspace two-dimensional GC-QTOF-MS - Dan Li; Ying Zeng; Zhi-Kang Ye; Han-Ke Li; Yu-Zhe Li; Ben Dong; Qi-Zhi Su; Qin-Bao Lin; Jing Xiao; Huai-Ning Zhong (Food Additives & Contaminants: Part A, 2023)

New perspective into possible mechanism in growth promotion of potassium diformate (KDF) on the juvenile grass carp (Ctenopharyngodon idella) - Xue Xue; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

In situ enrichment of sulphate-reducing microbial communities with different carbon sources stimulating the acid mine drainage sediments - Zhuo-hui Wu; Xiao-dan Yang; Li-ying Huang; Shi-lin Li; Fei-yun Xia; Yong-zhi Qiu; Xin-zhu Yi; Pu Jia; Bin Liao; Jie-Liang Liang; Wen-sheng Shu; Jin-tian Li (Science of The Total Environment, 2023)

Distinct patterns of the soil and phyllosphere antibiotic resistome in natural forest ecosystems under an altitudinal gradient - Shu-Yi-Dan Zhou; Fu-Yi Huang; Wei Su; Zhiyang Lie; Yue Liu; Chenshuo Lin; Kai Yang; Ze Meng; Zhanfeng Liu; Roy Neilson; Jian-Qiang Su; Juxiu Liu (Science of The Total Environment, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

Insights of the fate of antibiotic resistance genes during organic solid wastes composting based on bibliometric analysis: Development, hotspots, and trend directions - Jianbin Sun; Dan Zhang; Shuang Peng; Yiming Wang; Xiangui Lin (Journal of Cleaner Production, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Facile preparation of nitrogen-doped microporous carbon from potassium citrate/urea for effective CH4 separation and uptake - Li Zhang; Yonggang Dong; Dan Zhang; Wenfei Li; Hong Qin; Ziming Luo; Yongyong Shi; Yutao Lv; Cuiwei Zhang; Hongyan Pan; Qian Lin (Fuel, 2023)

Study on the relationship between primary structure/ spatial conformation and gel properties of pectins from different varieties - Jiefen Cui; Lin Zhang; Jirong Wang; Shaojie Zhao; Cheng Zhao; Dan Liu; Wenxiang Li; Jinkai Zheng (Food Hydrocolloids, 2023)

Identification and characterisation of microplastics released from plastic-coated paper cups using micro-Raman spectroscopy - Tianlong Zhang; Jia-Ling Hu; Yipin Duan; Sheng Chen; Dan Li; Ben Dong; Ming-Zhen Mo; Jing Wang; Jian-Guo Zheng; Huai-Ning Zhong; Qin-Bao Lin (Food Control, 2023)

Ultralow friction polymer composites enabled by the solid–liquid core microcapsules at high temperatures - Hao Chen; Yi Zhang; Kai Gao; Yilong Ren; Jianguo Jiao; Lin Zhang; Dan Guo; Guoxin Xie (Chemical Engineering Journal, 2023)

CYP72D19 from Tripterygium wilfordii catalyzes C-2 hydroxylation of abietane-type diterpenoids - Jie Gao; Lin Ma; Yuan Liu; Lichan Tu; Xiaoyi Wu; Jian Wang; Dan Li; Xianan Zhang; Wei Gao; Yifeng Zhang; Changli Liu (Plant Cell Reports, 2023)

Hybrid chain reaction and selective recognition-based homogeneous dual-fluorescence analysis of circulating tumor cells in clinical ovarian cancer samples - Qian Hu; Dan Tang; Mei Li; Xiaodu Liang; Juan Zhou; Yanming Meng; Yinhao Wei; Shixin Yan; Ruoyu Lin; Xiaoyu Niu; Lin Zhang (Analytica Chimica Acta, 2023)

The connection between six common air pollution particles and adult brain tumors: a meta-analysis of 26,217,930 individuals - Lu-Ting Shen; Meng-Wei Ge; Fei-Hong Hu; Yi-Jie Jia; Wen Tang; Wan-Qing Zhang; Dan-Yan Zhao; Wang-Qin Shen; Hong-Lin Chen (Environmental Science and Pollution Research, 2023)

Dietary selenium promoted muscle growth (myofiber hypertrophy rather than hyperplasia) by reducing endoplasmic reticulum stress in juvenile grass carp (Ctenopharyngodon idella) - Ya Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Xiao-Wan Jin; Jun Jiang; Jia-Yong Tang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Application of enzymatically treated Artemisia annua L. on adult grass carp (Ctenopharyngodon idella): Improved growth performance, intestinal antioxidant capacity and apical junctional complex - Qin-Qin Dai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; He-Qun Shi; Lu Zhang; Hai-Feng Mi; Jia-Yong Tang; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

Culturable and inhalable airborne bacteria in a semiunderground municipal wastewater treatment plant: Distribution, transmission, and health risk assessment - Xiang Zhang; Bingjie Lu; Guang Chen; Lihua Wang; Bingjie Lin; Zhengliang Peng; Songliu Lu; Dan Li; Jianmin Chen (Journal of Hazardous Materials, 2023)

Heterogeneous activation of permonosulfate by biochar supporting CuCoFe layered double hydroxide for rapid degradation of phenanthrene - Lin Wu; Tao Jin; Dan Li; Liping Wang; Yichen Sun (Journal of Environmental Chemical Engineering, 2023)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

Dietary threonine improves muscle nutritional value and muscle hardness associated with collagen synthesis in grass carp (Ctenopharyngodon idella) - Mei-Lan Wen; Pei Wu; Wei-Dan Jiang; Yang Liu; Cai-Mei Wu; Cheng-Bo Zhong; Shu-Wei Li; Ling Tang; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

High-throughput screening and investigation of the inhibitory mechanism of α-glucosidase inhibitors in teas using an affinity selection-mass spectrometry method - Jianjian Gao; Mengxue Zhou; Dan Chen; Jiye Xu; Zhe Wang; Jiakun Peng; Zhiyuan Lin; Shuai Yu; Zhi Lin; Weidong Dai (Food Chemistry, 2023)

Ensemble machine learning reveals key structural and operational features governing ion selectivity of polyamide nanofiltration membranes - Dan Lu; Xuanchao Ma; Jiancong Lu; Yukun Qian; Yifang Geng; Jing Wang; Zhikan Yao; Lijun Liang; Zhilin Sun; Songmiao Liang; Lin Zhang (Desalination, 2023)

Multi-dimensional micro-nano scale manganese oxide catalysts induced chemical-based advanced oxidation processes (AOPs) in environmental applications: A critical review - Lin Lin; Junsen Wang; Zhifang Zhao; Jiayi Zhu; Aikeyidanmu Zhamaerding; Lingyun Feng; Dan Yang; Lite Meng; Chuanshu He; Wenbing Wang; Yunhui Zhang; Wei Jin (Chemical Engineering Journal, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

Batch-fed composting of food waste: Microbial diversity characterization and removal of antibiotic resistance genes - Haichao Wang; Shuye Lin; Huan Zhang; Dong Guo; Dan Liu; Xiaowei Zheng (Bioresource Technology, 2023)

New perspective on mechanism in muscle toxicity of ochratoxin A: Model of juvenile grass carp (Ctenopharyngodon idella) - Piao Zhao; Xin Liu; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Juan Yang; Xiao-Qiu Zhou (Aquatic Toxicology, 2023)

Expression analysis, clinical significance and potential function of PLXNB2 in acute myeloid leukaemia - Zhibo Guo; Dan Guo; Desheng Kong; Sicheng Bian; Linlin Zhao; Qi Li; Leilei Lin; Jiali Hao; Lili Sun; Yinghua Li (Molecular Biology Reports, 2023)

Critical Roles of Protein Arginine Methylation in the Central Nervous System - Kewei Chang; Dan Gao; Jidong Yan; Liyan Lin; Tingting Cui; Shemin Lu (Molecular Neurobiology, 2023)

Omega-3 Polyunsaturated Fatty Acids Protect Neurological Function After Traumatic Brain Injury by Suppressing Microglial Transformation to the Proinflammatory Phenotype and Activating Exosomal NGF/TrkA Signaling - Long Lin; Shaorui Zheng; Jinqing Lai; Dan Ye; Qiaomei Huang; Zhe Wu; Xiangrong Chen; Shousen Wang (Molecular Neurobiology, 2023)

Drynaria Naringin alleviated mechanical stress deficiency-caused bone loss deterioration via Rspo1/Lgr4-mediated Wnt/β-catenin signalling pathway - Gui-Xun Shi; Wei-Dong Sun; Zeng-Huan Chen; Chuan-Jun Yang; Wang-Lin Luo; Dan-Feng Wang; Ze-Zhu Zhou (In Vitro Cellular & Developmental Biology - Animal, 2023)

Thermodynamic sensitivity of ammonia oxidizers-driven N2O fluxes under oxic-suboxic realms - Hussnain Mukhtar; Andrianto Ansari; Thanh Ngoc-Dan Cao; Rainer Ferdinand Wunderlich; Yu-Pin Lin (Chemosphere, 2023)

Designing and planning sustainable customized bus service for departing attendees of planned special events: A two-phase methodology integrating data-driven and demand-responsive - Yuan Tian; Dan Yang; Jian Wang; Wenfeng Lin; Yin Jiang; Shi An (Sustainable Cities and Society, 2023)

Enhanced biomethane production with a low carbon footprint via anaerobic co-digestion of swine wastewater with rice husk - Hung-Cheng Lin; Shu-Yuan Pan; Yu-I Lin; Dan-Thanh Ngoc Cao (Science of The Total Environment, 2023)

Self-assembled synthesis of Pd/SPEn from polyelectrolyte membranes for efficient direct synthesis of H2O2 via inhibiting the dissociation of O − O bond - Entong Ye; Zheng Chen; Yongyong Shi; Dan Zhang; Wenfei Li; Hong Qin; Ziming Luo; Quansheng Wu; Qian Lin; Hongyan Pan; Keliang Wang (Chemical Engineering Journal, 2023)

Limestone hydrogenation combined with reverse water–gas shift reaction under fluidized and iso-thermal conditions using MFB-TGA-MS - Iwei Wang; Dan Li; Shihui Wang; Yang Wang; Gang Lin; Binhang Yan; Zhenshan Li (Chemical Engineering Journal, 2023)

Designing functionalized graphene-stitched-SiC/fluoropolymer novel composite coating with excellent corrosion resistance and hydrogen diffusion barrier properties - Sicheng Yuan; Kun Li; Yue Sun; Chang Cong; Yaran Liu; Dan Lin; Luchao Pei; Yanji Zhu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

Genome-Wide Identification, Evolution Analysis of PI-PLC Family and Their Expression Patterns in Response to Different Hormones and Growth in Banana (Musa L.) - Qiuzhen Wu; Zhengyang Fan; Feng Qi; Dan Li; Zihao Zhang; Yukun Chen; Yuji Huang; Yuling Lin; Zhongxiong Lai (Tropical Plant Biology, 2023)

Eurycoma longifolia alkaloid components ameliorate hyperuricemic nephropathy via regulating serum uric acid level and relieving inflammatory reaction - Dan Wang; Lin Liu; Kaiwen Li; Huiya Cao; Mengyang Liu; Qian Chen; Yuzheng Wu; Yi Zhang; Tao Wang (Journal of Natural Medicines, 2023)

Targeting NF-κB pathway by dietary lignans in inflammation: expanding roles of gut microbiota and metabolites - Dan Li; Feijun Luo; Tianyi Guo; Shuai Han; Hanqing Wang; Qinlu Lin (Critical Reviews in Food Science and Nutrition, 2023)

Comparison of bacterial and fungal communities structure and dynamics during chicken manure and pig manure composting - Dan Zhang; Jianbin Sun; Danqing Wang; Shuang Peng; Yiming Wang; Xiangui Lin; Xiaoqian Yang; Qingqing Hua; Pan Wu (Environmental Science and Pollution Research, 2023)

Edge-based wireless imaging system for continuous monitoring of insect pests in a remote outdoor mango orchard - Dan Jeric Arcega Rustia; Wei-Che Lee; Chen-Yi Lu; Ya-Fang Wu; Pei-Yu Shih; Sheng-Kuan Chen; Jui-Yung Chung; Ta-Te Lin (Computers and Electronics in Agriculture, 2023)

Exosomal miR-17–92 derived from human mesenchymal stem cells promotes wound healing by enhancing angiogenesis and inhibiting endothelial cell ferroptosis - Wenbo Nie; Xuemiao Huang; Lijing Zhao; Taiwei Wang; Dan Zhang; Tianxin Xu; Lin Du; Yuxiang Li; Weiyuan Zhang; Fengjun Xiao; Lisheng Wang (Tissue and Cell, 2023)

Mid-Neoproterozoic tectonic switch from orogeny to intraplate extension in NW Tarim Craton: New evidence from a composite dike of the Aksu Group - Hong-Xiang Wu; Feng-Qi Zhang; Yildirim Dilek; Han-Lin Chen; Kong-Yang Zhu; Xiu-Bin Lin; Qin-Yan Wang; Hong-Dan Deng; Xiao-Gan Cheng (Precambrian Research, 2023)

How do livelihood capital affect farmers' energy-saving behaviors: Evidence from China - Lin Li; Jianjun Jin; Chenyang Zhang; Xin Qiu; Dan Liu (Journal of Cleaner Production, 2023)

Dppa3 Improves the Germline Competence of Pluripotent Stem Cells - Siying Liu; Shuang Zhao; Chuanyu Zhang; Chenglei Tian; Dan Wang; Huaxin Yu; Zongjin Li; Lin Liu; Na Liu (Stem Cell Reviews and Reports, 2023)

Elevated methylmercury in Antarctic surface seawater: The role of phytoplankton mass and sea ice - Fange Yue; Yanbin Li; Yanxu Zhang; Longquan Wang; Dan Li; Peipei Wu; Hongwei Liu; Lijin Lin; Dong Li; Ji Hu; Zhouqing Xie (Science of The Total Environment, 2023)

Soil microbiome feedback to climate change and options for mitigation - Hussnain Mukhtar; Rainer Ferdinand Wunderlich; Adnan Muzaffar; Andrianto Ansari; Oleg V. Shipin; Thanh Ngoc-Dan Cao; Yu-Pin Lin (Science of The Total Environment, 2023)

Effective adsorption and removal of malachite green and Pb2+ from aqueous samples and fruit juices by pollen–inspired magnetic hydroxyapatite nanoparticles/hydrogel beads - Yuwei Hua; Donghui Xu; Zhongxiao Liu; Jie Zhou; Jiatong Han; Zhihao Lin; Dan Xu; Ge Chen; Xiaodong Huang; Jing Chen; Jun Lv; Guangyang Liu (Journal of Cleaner Production, 2023)

Removal and mechanism analysis of NOx emissions in carbon-free ammonia combustion systems with a secondary fuel injection - Tao Cai; Dan Zhao; Lin Ji; Avinash Kumar Agarwal (Fuel, 2023)

Soy protein isolate-citrus pectin-gallic acid ternary composite high internal phase Pickering emulsion for delivery of β-carotene: Physicochemical, structural and digestive properties - Xinyu Xu; Lin Li; Chunmin Ma; Dan Li; Yang Yang; Xin Bian; Jing Fan; Na Zhang; Feng Zuo (Food Research International, 2023)

Exploring the effects of livelihood capital on clean cooking of rural households in the Tibetan region of China - Xin Qiu; Jianjun Jin; Chenyang Zhang; Dan Liu; Lin Li; Foyuan Kuang (Energy and Buildings, 2023)

MiR-370-3p aggravates blood–brain barrier injury and neuron apoptosis by targeting SMURF1 to activate the TLR4/MyD88/NF-κB signaling in sepsis-associated encephalopathy - Neng Wang; Dan Zhong; Jie Lin; Mei Ye; Yu Chen; Lili Wang; Mei Chen; Cong Luo (Molecular & Cellular Toxicology, 2023)

Combined Application of Tank-mix Adjuvants, Mist Sprayer and Nano-selenium Promoted Pesticide Reduction and Enhanced Strawberry Quality - Qinyong Dong; Guanyu Chen; Yilu Zhou; Yangliu Wu; Chunran Zhou; Yongxi Lin; Dan Liu; Canping Pan (Bulletin of Environmental Contamination and Toxicology, 2023)

A robust activatable two-photon fluorescent probe for endogenous formaldehyde biomarker visualization diagnosis and evaluation of diabetes mellitus - Jiangyan Wang; Jiangfeng Li; Lizhen Xu; Dan Tan; Rui Guo; Weiying Lin (Analytica Chimica Acta, 2023)

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Dietary zearalenone alters gill epithelial morphology and subsequent risk of infection: Insights from a freshwater grass carp (Ctenopharyngodon idella) model - Hong-Yun Zhang; Ya-Li Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Shu-wei Li; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Hemocyte proliferation is associated with blood color shade variation in the blood clam, Tegillarca granosa - Zexin Yang; Xin He; Hongyu Jin; Dan Su; Zhihua Lin; Hongxing Liu; Yongbo Bao (Aquaculture, 2023)

Aflatoxin B1 exposure induced developmental toxicity and inhibited muscle development in zebrafish embryos and larvae - Xiang-Ning He; Pei Wu; Wei-Dan Jiang; Yang Liu; Sheng-Yao Kuang; Ling Tang; Hong-Mei Ren; Hua Li; Lin Feng; Xiao-Qiu Zhou (Science of The Total Environment, 2023)

Evaluation of modified bitumen properties using waste plastic pyrolysis wax as warm mix additives - Chuanqiang Li; Haobo Wang; Chaoliang Fu; Shaosong Shi; Guannan Li; Qizheng Liu; Dan Zhou; Lin Jiang; Ying Cheng (Journal of Cleaner Production, 2023)

Mechanism of polycyclic aromatic hydrocarbons degradation in the rhizosphere of Phragmites australis: Organic acid co-metabolism, iron-driven, and microbial response - Ni-chen Zhang; Dan A; Yuan-qing Chao; Hai-Yan Li; Charles Li; Qing-qi Lin; Ya-ying Li; Rong-liang Qiu (Environmental Pollution, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

RNA-Sequencing Reveals Gene Expression and Pathway Signatures in Umbilical Cord Blood Affected by Birth Delivery Mode - Yongjie Liu; Kun Sun; Yuexin Gan; Han Liu; Juehua Yu; Wei Xu; Lin Zhang; Dan Chen (Phenomics, 2023)

Effects of phosphorus fertilizer application rate on transformation processes of phosphorus fractions in the purple alluvial soil of a riparian zone - Li-ping He; Kai-tao Jia; Dan Liu; Ke-hong Wang; Lin-Yan Duan; Jun-jie Lin (Journal of Mountain Science, 2023)

Expression profiles of the CD274 and PLEKHH2 gene and association of its polymorphism with hematologic parameters in sheep - Yukun Zhang; Xiaoxue Zhang; Fadi Li; Changchun Lin; Deyin Zhang; Benzhen Duan; Yuan Zhao; Xiaolong Li; Dan Xu; Jiangbo Cheng; Liming Zhao; Jianghui Wang; et al. (Veterinary Immunology and Immunopathology, 2023)

Priming effects induced by degradable microplastics in agricultural soils - Guohao Zhang; Dan Liu; Junjie Lin; Amit Kumar; Kaitao Jia; Xiaoxuan Tian; Zhiguo Yu; Biao Zhu (Soil Biology and Biochemistry, 2023)

Developing a novel framework to re-examine half a century of compound drought and heatwave events in mainland China - Lin Zhao; Xinxin Li; Zhijiang Zhang; Moxi Yuan; Shao Sun; Sai Qu; Mengjie Hou; Dan Lu; Yajuan Zhou; Aiwen Lin (Science of The Total Environment, 2023)

A Strecker-like reaction triggering fluorescent sensing platform for enzyme-free and visual quantitative monitoring of carbamates - Lingling Qin; Jie Cao; Dan Lin; Shihao Xu; Yucheng Li; Changlong Jiang (Chemical Engineering Journal, 2023)

The shadows hang over immunotherapy-neutrophil extracellular traps in cancer - Dan Pu; Liyuan Yin; Xiaoqian Zhai; Ruoxiang Wang; Lin Huang; Qiang Wu; Lingling Zhu; Yuwen Zhou; Qinghua Zhou; Lu Li (Science China Life Sciences, 2023)

Arbuscular mycorrhizal fungi increase the interspecific competition between two forage plant species and stabilize the soil microbial network during a drought event: Evidence from the field - Xionghui Liao; Jie Zhao; Lin Xu; Li Tang; Jiangnan Li; Wei Zhang; Jun Xiao; Dan Xiao; Peilei Hu; Yunpeng Nie; Dongsheng Zou; Kelin Wang (Applied Soil Ecology, 2023)

Mitochondrial division inhibitor (mdivi-1) inhibits proliferation and epithelial-mesenchymal transition via the NF-κB pathway in thyroid cancer cells - Lin Zhang; Lei Sun; Lirong Wang; Juan Wang; Dan Wang; Jue Jiang; Jinhui Zhang; Qi Zhou (Toxicology in Vitro, 2023)

The ginsenoside Rh2 protects porcine oocytes against aging and oxidative stress by regulating SIRT1 expression and mitochondrial activity - Hongye Liu; Zhi-Yong An; Zhou-Yan Li; Liu-Hui Yang; Xiu-Li Zhang; Yan-Tong Lv; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2023)

Future hotter summer greatly increases residential electricity consumption in Beijing: A study based on different house layouts and shared socioeconomic pathways - Qiyuan Hu; Jiayue Tang; Xiang Gao; Sijia Wang; Dan Zhang; Yuting Qin; Qihan Wang; Yi Zhou; Na Huang; Josep Penuelas; Jordi Sardans; Josep G. Canadell; et al. (Sustainable Cities and Society, 2023)

Spatio-temporal variation of the relationship between air pollutants and land surface temperature in the Yangtze River Delta Urban Agglomeration, China - Yue Jiang; Wenpeng Lin; Di Xu; Dan Xu (Sustainable Cities and Society, 2023)

Effects of polyethylene and biodegradable microplastics on photosynthesis, antioxidant defense systems, and arsenic accumulation in maize (Zea mays L.) seedlings grown in arsenic-contaminated soils - Huarong Sun; Yilan Shi; Ping Zhao; Guangqiang Long; Chaohang Li; Jiajing Wang; Dan Qiu; Chunmiao Lu; Yue Ding; Lin Liu; Shuran He (Science of The Total Environment, 2023)

Highly efficient catalysts of polyoxometalates supported on biochar for antibiotic wastewater treatment: Performance and mechanism - Lihe Zhu; Fang Yang; Xue Lin; Dan Zhang; Xixin Duan; Junyou Shi; Zhong Sun (Process Safety and Environmental Protection, 2023)

Dual photoluminescence emission carbon dots for ratiometric optical dual-mode and smartphone-integrated visual detection of mercury ion - Dan Chang; Lin Li; Xiaorui Dong; Hu Shi; Shuo Wang; Zhonghua Zhao; Liuliu Lv; Yongxing Yang; Lihong Shi (Journal of Environmental Chemical Engineering, 2023)

Assessment of exhaled pathogenic droplet dispersion and indoor-outdoor exposure risk in urban street with naturally-ventilated buildings - Jian Hang; Xia Yang; Cui-Yun Ou; Zhi-Wen Luo; Xiao-Dan Fan; Xue-Lin Zhang; Zhong-Li Gu; Xian-Xiang Li (Building and Environment, 2023)

Aflatoxin B1 damaged structural barrier through Keap1a/Nrf2/ MLCK signaling pathways and immune barrier through NF-κB/ TOR signaling pathways in gill of grass carp (Ctenopharyngodon idella) - Xiang-Ning He; Zhen-Zhen Zeng; Lin Feng; Pei Wu; Wei-Dan Jiang; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Aquatic Toxicology, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Identification and characterization of biocontrol agent Lysinibacillus boronitolerans P42 against Cerrena unicolor that causes root rot of arecanut palm - Xiang Ma; Yuxiao Gao; Hong Li; Dan Wang; Juanjuan Li; Xinwen Hu; Xi Huang; Min Lin; Yanqiong Tang; Zhu Liu (Archives of Microbiology, 2023)

Comparisons in molecular weight distributions and size-dependent optical properties among model and reference natural dissolved organic matter - Dan Li; Hui Lin; Laodong Guo (Environmental Science and Pollution Research, 2023)

Eradicating the tumor “seeds”: nanomedicines-based therapies against cancer stem cells - Lin Li; Rui Ni; Dan Zheng; Lin Chen (DARU Journal of Pharmaceutical Sciences, 2023)

Association between co-exposure of polycyclic aromatic hydrocarbons and chronic obstructive pulmonary disease among the US adults: results from the 2013–2016 National Health and Nutrition Examination Survey - Lin Wen; Xiaosong Ben; Zhiyu Yang; Yingying Wu; Yuxuan Tan; Qian Chen; Huanzhu Liang; Yexin Li; Xiaomei Wu; Shan Liu; Xueqiong Weng; Dan Tian; et al. (Environmental Science and Pollution Research, 2023)

Leonurine improves bovine oocyte maturation and subsequent embryonic development by reducing oxidative stress and improving mitochondrial function - Lv Zheng; Yuwen Luo; Dan Zhou; Hongyu Liu; Guizhen Zhou; Lin Meng; Yunpeng Hou; Changbin Liu; Jun Li; Xiangwei Fu (Theriogenology, 2023)

Geochemical record of methane seepage in carbon cycling and possible correlation with climate events in the Qiongdongnan basin, South China Sea - Xiaopeng Dan; Shuang Liu; Xiuli Feng; Lin Lin; Rong Tang; Chao Yang; Jinya Xu; Zihan Wu (Marine and Petroleum Geology, 2023)

Occurrence of volatile contaminants in recycled poly(ethylene terephthalate) by HS-SPME-GC×GC-QTOF-MS combined with chemometrics for authenticity assessment of geographical recycling regions - Ben Dong; Xuefeng Wu; Siliang Wu; Hanke Li; Qi-Zhi Su; Dan Li; Qinbao Lin; Sheng Chen; Jianguo Zheng; Lei Zhu; Huai-Ning Zhong (Journal of Hazardous Materials, 2023)

The impact of different fermenting microbes on residual purine content in fermented lamb jerky following in vitro digestion - Jianlin Liu; Xueying Sun; Yue Zhang; Ye Jin; Lina Sun; Xueying Chai; Dan Wang; Lin Su; Lihua Zhao (Food Chemistry, 2023)

The structure-function relationships of pectins separated from three citrus parts: Flavedo, albedo, and pomace - Lin Zhang; Jiefen Cui; Shaojie Zhao; Dan Liu; Cheng Zhao; Jinkai Zheng (Food Hydrocolloids, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

Hydraulic determinants of drought-induced tree mortality and changes in tree abundance between two tropical forests with different water availability - Yong-Qiang Wang; Hui-Qing Song; Ya-Jun Chen; Pei-Li Fu; Jiao-Lin Zhang; Kun-Fang Cao; Shi-Dan Zhu (Agricultural and Forest Meteorology, 2023)

Trade-offs between fertilizer-N availability and Cd pollution potential under crop straw incorporation by 15 N stable isotopes in rice - Anqi Shan; Lukuan Huang; Dan Chen; Qiang Lin; Rongjie Liu; Mei Wang; Kyong Ju Kang; Minghui Pan; Gang Wang; Zhenli He; Xiaoe Yang (Environmental Science and Pollution Research, 2023)

Transformer neural network to predict and interpret pregnancy loss from activity data in Holstein dairy cows - Dan Lin; Ákos Kenéz; Jessica A.A. McArt; Jun Li (Computers and Electronics in Agriculture, 2023)

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Identification of SNPs and candidate genes associated with early growth in orange-spotted grouper (Epinephelus coioides) by a genome-wide association study - Chun Hui Ai; Zong Xian Zhu; Dan Dan Huang; Gan Yang; Tong De Liu; Ying Bai; Xue Ying Liang; Ying Ying Xiong; Yi Long Lin; Hao Ran Lin; Shui Sheng Li; Jun Hong Xia (Aquaculture, 2023)

Enhancements in flavor substances, mouthfeel characteristics and collagen synthesis in the muscle of sub-adult grass carp (Ctenopharyngodon Idella): Application of a dietary lysine nutrition strategy - Yan-Jie Tang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Linking bacterial life strategies with soil organic matter accrual by karst vegetation restoration - Peilei Hu; Wei Zhang; Yakov Kuzyakov; Lumei Xiao; Dan Xiao; Lin Xu; Hongsong Chen; Jie Zhao; Kelin Wang (Soil Biology and Biochemistry, 2023)

Association of walkability and fine particulate matter with chronic obstructive pulmonary disease: A cohort study in China - Yonghao Wu; Peng Shen; Zongming Yang; Luhua Yu; Zhanghang Zhu; Tiezheng Li; Lisha Xu; Dan Luo; Xuecheng Yao; Xinhan Zhang; Lin Meng; Hongbo Lin; et al. (Science of The Total Environment, 2023)

Bedrock outcrops weakly promote rather than inhibit soil carbon sequestration after vegetation restoration - Lin Xu; Jiguang Zhang; Peilei Hu; Wei Zhang; Lumei Xiao; Yingying Ye; Dan Xiao; Jie Zhao; Jun Xiao; Kelin Wang (Science of The Total Environment, 2023)

Hydrogen-bond induced enhanced emission ratiometric fluorescent handy needle for visualization assay of amoxicillin by smartphone sensing platform - Lingfei Li; Liang Yang; Dan Lin; Shihao Xu; Chunsheng Mei; Shaoming Yu; Changlong Jiang (Journal of Hazardous Materials, 2023)

Bacterial coculture enhanced Cd sorption and As bioreduction in co-contaminated systems - Huaiting Liu; Zhiqi Hong; Jiahui Lin; Dan Huang; Lena Q. Ma; Jianming Xu; Zhongmin Dai (Journal of Hazardous Materials, 2023)

Lipid peroxide-derived short-chain aldehydes promote programmed cell death in wheat roots under aluminum stress - Xin Liang; Ruyi Qian; Yiqun Ou; Dan Wang; Xianyong Lin; Chengliang Sun (Journal of Hazardous Materials, 2023)

Catalytic pyrolysis of 5-Amino-1H-Tetrazole with copper and its oxide: A deep insight into the combustion mechanism for high nitrogen compound - Si-Yuan Zhou; Jiu Chen; Xuan Li; Fan Jia; Dan Zhang; Li-Feng Xie; Bin Li; Lin Jiang (Fuel, 2023)

Revealing key structural and operating features on water/salts selectivity of polyamide nanofiltration membranes by ensemble machine learning - Xuanchao Ma; Dan Lu; Jiancong Lu; Yukun Qian; Shun Zhang; Zhikan Yao; Lijun Liang; Zhilin Sun; Lin Zhang (Desalination, 2023)

Marangoni-driven biomimetic salt secretion evaporator - Yu Chen; Jin Yang; Lin Zhu; Sizhe Wang; Xiaohua Jia; Yong Li; Dan Shao; Lei Feng; Haojie Song (Desalination, 2023)

A multifunctional and long-term waterborne anti-corrosion coating with excellent ‘hexagonal warrior’ properties - Luchao Pei; Dan Lin; Sicheng Yuan; Renjie Lu; Ziheng Bai; Yue Sun; Yanji Zhu; Yuanxu Jiang; Jiajun Zhu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

Analysis of microplastics released from plastic take-out food containers based on thermal properties and morphology study - Jia-Ling Hu; Yipin Duan; Huai-Ning Zhong; Qin-Bao Lin; Tianlong Zhang; Chuang-Chuang Zhao; Sheng Chen; Ben Dong; Dan Li; Jing Wang; Ming-Zhen Mo; Jie Chen; et al. (Food Additives & Contaminants: Part A, 2023)

Somatostatin-Positive Neurons in the Rostral Zona Incerta Modulate Innate Fear-Induced Defensive Response in Mice - Shan Lin; Meng-Yue Zhu; Meng-Yu Tang; Mi Wang; Xiao-Dan Yu; Yi Zhu; Shi-Ze Xie; Dan Yang; Jiadong Chen; Xiao-Ming Li (Neuroscience Bulletin, 2023)
Defensive behaviors induced by innate fear or Pavlovian fear conditioning are crucial for animals to avoid threats and ensure survival. The zona incerta (ZI) has been demonstrated to play important roles in fear learning and fear memory, as well as modulating auditory-induced innate defensive behavior. However, whether the neuronal subtypes in the ZI and specific circuits can mediate the innate fear response is largely unknown. Here, we found that somatostatin (SST)-positive neurons in the rostral ZI of mice were activated by a visual innate fear stimulus. Optogenetic inhibition of SST-positive neurons in the rostral ZI resulted in reduced flight responses to an overhead looming stimulus. Optogenetic activation of SST-positive neurons in the rostral ZI induced fear-like defensive behavior including increased immobility and bradycardia. In addition, we demonstrated that manipulation of the GABAergic projections from SST-positive neurons in the rostral ZI to the downstream nucleus reuniens (Re) mediated fear-like defensive behavior. Retrograde trans-synaptic tracing also revealed looming stimulus-activated neurons in the superior colliculus (SC) that projected to the Re-projecting SST-positive neurons in the rostral ZI (SC-ZIr SST -Re pathway). Together, our study elucidates the function of SST-positive neurons in the rostral ZI and the SC-ZIr SST -Re tri-synaptic circuit in mediating the innate fear response.

Correction to: Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2023)

Dexmedetomidine alleviates acute lung injury by promoting Tregs differentiation via activation of AMPK/SIRT1 pathway - Zheng-tao Zhang; Ke Xie; Ren-jie Luo; Dan-ying Zhang; Zhi-wei He; Ke-feng Li; Shi-hui Lin; Fang Xu (Inflammopharmacology, 2023)

Evaluation of Copper Levels in Dental Calculus of OSF Patients with Chewing Dried Areca-Nut Quids in Hunan Province of Mainland China - Xi-Fan He; Hui Wang; Ye Tian; Te Zhang; Zhi-Peng Qiu; Xiao-Jiao Cui; Jing-Sha Zhou; Xin-Lan Yan; Yi-Wei Wu; Yi-Sha Pan; Yang-Bo Ning; Lin Chen; et al. (Biological Trace Element Research, 2023)

The beneficial effects of exogenous protease K originated from Parengyodontium album on growth performance of grass carp (Ctenopharyngodon idella) in relation to the enhanced intestinal digestion and absorption capacities - Ling Feng; Lin Feng; Wei-Dan Jiang; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou; Pei Wu (Aquaculture, 2023)

Impaired intestinal physical barrier of on-growing grass carp by deficient iron under Aeromonas hydrophila infection - Yan-Lin Guo; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Shu-wei Li; Ling Tang; Lu Zhang; Haifeng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Simultaneous detection of two herbicides in fruits and vegetables with nanoparticle-linked immunosorbent and lateral flow immunoassays - Eunice Y. Kwon; Xiaofan Ruan; Fei Yu; Yuehe Lin; Dan Du; Bernard J. Van Wie (Food Chemistry, 2023)

Dietary cinnamaldehyde improves muscle protein content by promoting muscle fiber growth via PTP1B/IGF1/PI3K/AKTs-TOR/FOXO3a signaling pathway in grass carp (Ctenopharyngodon idella) - Yang Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Yan Peng; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

A novel all-natural (collagen+pectin)/chitosan aqueous two-phase microcapsule with improved anthocyanin loading capacity - Zhenyang Jiang; Shaojie Zhao; Zhiying Fan; Chengying Zhao; Lin Zhang; Dan Liu; Yuming Bao; Jinkai Zheng (Food Hydrocolloids, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Dual-activation interfacial polymerization based anionic covalent organic framework nanofiltration membrane for high-flux dye separation - Yixin Yang; Guorong Li; Dan Ouyang; Zongwei Cai; Zian Lin (Chemical Engineering Journal, 2023)

Nonoxidative propane dehydrogenation by isolated Co2+ in BEA zeolite: Dealumination-determined key steps of propane C H activation and propylene desorption - Sheng Wei; Hua Dai; Jiangping Long; Hongqiao Lin; Junkun Gu; Xupeng Zong; Dan Yang; Yu Tang; Yanhui Yang; Yihu Dai (Chemical Engineering Journal, 2023)

Sn2P2S6: A lead-free reversible thermochromic ferroelectric with high near-infrared reflectance - Meixia Wu; Xiao Zhou; Xihui Liang; Yifeng Han; Yonghong Li; Xingan Jiang; Xueyun Wang; Yisheng Chai; Xiang Zhou; Hui Yang; Dan Lin; Ping Xu; et al. (Chemical Engineering Journal, 2023)

Activate whole-body passivation ability of small isomeric D-π-A molecules via amino position effect to improve the photovoltaic performance of perovskite solar cells - Zonghan Guo; Tongxin Xue; Xiaoxu Sun; Dan Li; Fengyou Wang; Lin Fan; Xiaoyan Liu; Lili Yang; Maobin Wei (Chemical Engineering Journal, 2023)

N-type small molecule electron transport materials with D-A-D conjugated core for non-fullerene organic solar cells - Dan Zhou; Yubing Li; Hehui Zhang; Haolan Zheng; Xingxing Shen; Wen You; Lin Hu; Liangjing Han; Yongfen Tong; Lie Chen (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

A smart composite coating with photothermal response, anti-UV and anti-corrosion properties - Yue Sun; Sicheng Yuan; Weihao Fan; Dan Lin; Kun Zhang; Ziheng Bai; Yanji Zhu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

Capture of iodine gas by Bi0 modified silica with different morphologies: Influence of pore characteristic on the stable and unstable forms of adsorption - Yi Ding; Weijie Fan; Qiang Xian; Hui Dan; Lin Zhu; Tao Duan (Chemical Engineering Journal, 2023)

Response of performance, antibiotic resistance genes and bacterial community exposure to compound antibiotics stress: Full nitrification to shortcut nitrification and denitrification - Lin Wang; Zhaoli Wang; Fan Wang; Yue Guan; Dan Meng; Xin Li; Houzhen Zhou; Xudong Li; Yangwu Chen; Zhouliang Tan (Chemical Engineering Journal, 2023)

Improving yield and nitrogen use efficiency of hybrid indica rice through optimizing nitrogen application strategies in the rice season under different rotation patterns - YongJian Sun; Dan Lin; YuanYuan Sun; FengJun Yan; Peng Ma; ChangChun Guo; FeiJie Li; ZhiYuan Yang; FuXian Xu; Jun Ma (Paddy and Water Environment, 2023)

Size-specific particulate matter and outpatient visits for allergic conjunctivitis in children: a time-stratified case-crossover study in Guangzhou, China - Jin Zhou; Lijun Fan; Hualiang Lin; Dehui Zheng; Lihong Yang; Dan Zhuo; Jiayang Zhuoma; Huan Li; Shiyu Zhang; Zengliang Ruan (Environmental Science and Pollution Research, 2022)

From Initiation to Maintenance: HIV-1 Gp120-induced Neuropathic Pain Exhibits Different Molecular Mechanisms in the Mouse Spinal Cord Via Bioinformatics Analysis Based on RNA Sequencing - Jian Huang; Fei Lin; Yanling Hu; Chris Bloe Bloe; Dan Wang; Wenping Zhang (Journal of Neuroimmune Pharmacology, 2022)

Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2022)

Therapeutic effects of JLX001 on neuronal necroptosis after cerebral ischemia–reperfusion in rats - Wanting Li; Xue Gou; Dan Xu; Lin Zhou; Fengyang Li; Anqi Ye; Yahui Hu; Yunman Li (Experimental Brain Research, 2022)

Physical activity from menarche-to-first pregnancy and risk of breast cancer: the California teachers study - Dan Lin; Ying Liu; Deirdre K. Tobias; Kathleen Sturgeon (Cancer Causes & Control, 2022)

Long‐term series variation in fishery biology of Dosidicus gigas off Peru: Response to climate variability from 2008 to 2020 - Ya Ting Dan; Bi Lin Liu; Xin Jun Chen; Wei Guo Qian (Fisheries Oceanography, 2022)
As a cephalopod with a short life cycle, the Dosidicus gigas (jumbo flying squid) is extremely sensitive to climate variability and marine environment changes in terms of individual growth and resource changes. Based on 7514 D. gigas samples collected off Peru from 2008 to 2020, the fishery biological characteristics such as size, sexual maturity, and size‐at‐maturity were analyzed to explore the impacts of climate variability on individual growth. The results showed that there were significant differences in the relationship between mantle length and body weight and in the composition of sexual maturity between male and female individuals in different years ( P D. gigas and slowed down their sexual maturity, producing D. gigas groups in medium and large sizes; El Niño events inhibited the individual growth of D. gigas and accelerated their sexual maturity, producing D. gigas groups in a smaller size. From 2008 to 2020, the mantle length of the small‐size group decreased by 46 mm, while that of the medium‐size group increased by 28 mm. Size‐at‐maturity of female D. gigas decreased by 201.2 mm and that of male D. gigas decreased by 143 mm. The study concluded that the changes in the marine environment caused by climate variability from 2008 to 2020 have had a significant impact on the population structure, growth, and development of the D. gigas off Peru.

Original and improved interspecies correlation estimation models in China for potential application in water quality criteria - Jiangyue Wu; Lin Gao; Songhua Jiang; Ning Jia; Dan Wang; Jin Wu (Environmental Science and Pollution Research, 2022)

Identification and characteristic analysis of urban vegetation spectra under different dust deposition - Xumiao Yu; Wenpeng Lin; Dan Wang; Ying Li; Yue Sun (Environmental Science and Pollution Research, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Temporal and spatial distribution characteristics of drought and flood considering the influence of underlying surface in Hainan Island, tropical areas of China - Changqing Ye; Yi Zou; Yanhu He; Youwen Lin; Dan Li; Lirong Zhu (Theoretical and Applied Climatology, 2022)

A refined model of a typhoon near-surface wind field based on CFD - Youtian Yang; Lin Dong; Jiazi Li; Wenli Li; Dan Sheng; Hua Zhang (Natural Hazards, 2022)

Elevation of microRNA-365 impedes malignant behaviors of gastric cancer cells by inhibiting PAX6 - Dan Hong; Aimin Zang; Zhiyu Wang; Lin Yang; Guanying Ren; Chong Zhang; Liwei Zhang; Wei Hou; Yaning Wei (Functional & Integrative Genomics, 2022)

Effect modification by aging on the associations of nicotine exposure with cognitive impairment among Chinese elderly - Jian Hou; Chao Huang; Bo Zhu; Wei Liu; Qing-qing Zhu; Lu Wang; Tian Li; Chun-jie Yuan; Shao-yang Lai; De-sheng Wu; Fei-qi Zhu; Jia-fei Zhang; et al. (Environmental Science and Pollution Research, 2022)

Ectopic expression of a bamboo SVP-like gene alters flowering time and floral organs in Arabidopsis thaliana - Shinan Liu; Naresh Vasupalli; Dan Hou; Xinchun Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Identification and QTL mapping of important agronomic traits based on rice short-wide grain CSSL-Z752 with restorer line Xihui 18 as background - Lin-Jun Cai; Han Yun; Xiao-Long Zhong; Dan Du; Xi-Man Peng; Ji-Chao Dai; Zhen-Lin Yang; Fang-Ming Zhao; Chang-Wei Zhang (Cereal Research Communications, 2022)

Intrauterine hyperglycemia impairs endometrial receptivity via up-regulating SGK1 in diabetes - Haiyan Xu; Jingyi Li; Luyang Jin; Dan Zhang; Bin Chen; Xinmei Liu; Xianhua Lin; Yiting Huang; Zhanghong Ke; Juan Liu; Lin Gao; Jianzhong Sheng; et al. (Science China Life Sciences, 2022)

Integrated Analyses of miRNome and Transcriptome Reveal the Critical Role of miRNAs Toward Heat Stress Response in Isochrysis galbana - Jia-Yi Cao; Si-Min Xu; Ying-Ying Wang; Xie-Dan Long; Shuo-Nan Ma; Cheng-Xu Zhou; Ji-Lin Xu; Xiao-Jun Yan (Marine Biotechnology, 2022)

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Potential Application of Biosurfactant-Producing Bacteria for Bioremediation of Oil Polluted Marine Intertidal Sediments - Ping Guo; Wei-Wei Xu; Dan-Na Wei; Man-Xia Zhang; Jin Zhang; Shi Tang; Bin-Xia Cao; Jian-Guo Lin; Wei Li (Journal of Marine Science and Engineering, 2022)
The removal of oil contaminants in marine intertidal sediments under cold climate is an urgent issue. Although the bioavailability of petroleum hydrocarbons decreases at low temperatures, biosurfactants can promote oil biodegradation. In this study, characteristics of biosurfactants produced by cold-adapted oil-degrading bacteria Planococcus sp. XW-1 were studied. Adding the XW-1 biosurfactant could effectively facilitate the solubility of phenanthrene, pyrene, diesel oil, and crude oil. The solubilization was limited by the number of rings and the molecular weight (WSRphenanthrene = 0.0234; WSRpyrene = 0.0165; WSRdiesel oil = 0.0027; WSRcrude oil = 0.0015). Additional biosurfactants significantly washed out crude oil adsorbed to the sand (reduction from 17.1%, 22.7% to 87.9% and 94.28% in 24 h). With the increase in particle size, the removal efficiency increased from 87.9% to 94.28%. After the addition of biosurfactant, the effect of degradation increased by 20% in 20 days. The results suggest that the biosurfactant-producing bacteria Planococcus sp. XW-1 is a promising candidate used in the in situ bioremediation of petroleum-contaminated intertidal sediment.

Links between continental subduction and generation of Cenozoic potassic–ultrapotassic rocks revealed by olivine oxygen isotopes: A case study from NW Tibet - Gong-Jian Tang; Derek A. Wyman; Qiang Wang; Lin Ma; Wei Dan; Ya-Nan Yang; Xi-Jun Liu; Hong-Yi Chen (Contributions to Mineralogy and Petrology, 2022)

Nighttime N2O5 chemistry in an urban site of Beijing in winter based on the measurements by cavity ring-down spectroscopy - Zhiyan Li; Dan Wang; Pinhua Xie; Renzhi Hu; Hao chen; Chuan Lin (Air Quality, Atmosphere & Health, 2022)

Two new 7,20-epoxy- ent -kaurane diterpenoids from the aerial parts of Isodon serra - Juan-Juan Hu; Bai-Lin Li; Jin-Dan Xie; Hui-Jun Liang; Qian-Ran Li; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2022)

TRIP13 knockdown inhibits the proliferation, migration, invasion, and promotes apoptosis by suppressing PI3K/AKT signaling pathway in U2OS cells - De-Chen Yu; Xiang-Yi Chen; Hai-Yu Zhou; De-Quan Yu; Xiao-Lei Yu; Yi-Cun Hu; Rui-Hao Zhang; Xiao-Bo Zhang; Kun Zhang; Mao-Qiang Lin; Xi-Dan Gao; Tao-Wen Guo (Molecular Biology Reports, 2022)

Zkscan3 affects erythroblast development by regulating the transcriptional activity of GATA1 and KLF1 in mice - Zixuan Li; Binjie Sheng; Tingting Zhang; Tian Wang; Dan Chen; Gangli An; Xingbing Wang; Huimin Meng; Lin Yang (Journal of Molecular Histology, 2022)
ZKSCAN3 encodes a zinc-finger transcription factor that regulates the expression of important genes and plays a significant role in tumor development, pathogenesis, and metastasis. However, its biological functions under normal physiological conditions remain largely unknown. In our previous studies, using flow cytometry, we found that the deletion of Zkscan3 may cause abnormal erythropoiesis. In this study, we found that, in a Zkscan3 knockout mice model, the number of splenic early-stage (basophilic-erythroblasts) and late-stage (chromatophilic-erythroblasts to polychromatophilic-erythroblasts through orthochromatophilic-erythroblasts) erythroblasts increased, whereas the number of late erythroblasts in the bone marrow decreased. Moreover, the phenotype was exacerbated after treating mice with phenylhydrazine (PHZ), which causes severe hemolytic anemia. In the knockout mice treated with PHZ, the percentage of reticulocyte in the peripheral blood conspicuously increased, whereas MCHC and red blood cells decreased. Then, we performed RNA-seq and quantitative-polymerase chain reaction assay and found that the expression of GATA1 and Tiam1 in erythroblasts were upregulated, whereas KLF1 was downregulated. Luciferase assays showed that Zkscan3 inhibited the transcription of GATA1 and Tiam1 and promoted the expression of KLF1 . Additionally, ChIP and CO-IP results confirmed that Zkscan3 directly interacts with GATA1 and inhibits its transcriptional activity in MEL cells. Our results demonstrate, for the first time, the significant role of Zkscan3 in physiological erythropoiesis through the interaction with GATA1, both at the DNA and protein level, and with Tiam1 and KLF1 at the DNA level.

Effects of Environmental and Spatial Variables on Bacteria in Zhanjiang Mangrove Sediments - Di-Hua Zhu; Qing-Lang Song; Fang-Hong Nie; Wan Wei; Meng-Meng Chen; Min Zhang; Hong-Ying Lin; Dan-Ju Kang; Zhi-Bao Chen; Anthony G. Hay; Jin-Jun Chen (Current Microbiology, 2022)

The effect of preoperative statin treatment on acute kidney injury in elderly patients undergoing valve replacement surgery - Bing-qi Fu; Xue-biao Wei; Zedazhong Su; Ying-wen Lin; Zu-hui Ke; Tong Tan; Ji-yan Chen; Shou-hong Wang; Dan-qing Yu (European Journal of Clinical Pharmacology, 2022)

Can transportation infrastructure reduce haze pollution in China? - Chenggang Li; Tao Lin; Zhifei Zhang; Dan Xu; Lei Huang; Wanping Bai (Environmental Science and Pollution Research, 2022)

Phactr1 negatively regulates bone mass by inhibiting osteogenesis and promoting adipogenesis of BMSCs via RhoA/ROCK2 - Wei Lin; Zhipeng Chen; Xiaoyi Mo; Shengli Zhao; Zhenxing Wen; Wing Hoi Cheung; Dan Fu; Bailing Chen (Journal of Molecular Histology, 2022)

Chemical constituents from the fruits of Piper longum L. and their vascular relaxation effect on rat mesenteric arteries - Dan Li; Rui Wang; Xiaohan Cheng; Jianfeng Yang; Yihui Yang; Huichong Qu; Sen Li; Shan Lin; Donghua Wei; Yuhua Bai; Xiaodong Zheng (Natural Product Research, 2022)

PHD2 attenuates high-glucose-induced blood retinal barrier breakdown in human retinal microvascular endothelial cells by regulating the Hif-1α/VEGF pathway - Jia Li; Xi Lu; Liqing Wei; Dan Ye; Jianqiang Lin; Xiaoyu Tang; Kaixuan Cui; Shanshan Yu; Yue Xu; Xiaoling Liang (Inflammation Research, 2022)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

Phenolic glycosides and flavonoids with antioxidant and anticancer activities from Desmodium caudatum - Qian-Nan Xu; Dan Zhu; Guang-Hui Wang; Ting Lin; Cui-Ling Sun; Rong Ding; Wen-Jing Tian; Hai-Feng Chen (Natural Product Research, 2021)

AUV Obstacle Avoidance Planning Based on Deep Reinforcement Learning - Jianya Yuan; Hongjian Wang; Honghan Zhang; Changjian Lin; Dan Yu; Chengfeng Li (Journal of Marine Science and Engineering, 2021)
In a complex underwater environment, finding a viable, collision-free path for an autonomous underwater vehicle (AUV) is a challenging task. The purpose of this paper is to establish a safe, real-time, and robust method of collision avoidance that improves the autonomy of AUVs. We propose a method based on active sonar, which utilizes a deep reinforcement learning algorithm to learn the processed sonar information to navigate the AUV in an uncertain environment. We compare the performance of double deep Q-network algorithms with that of a genetic algorithm and deep learning. We propose a line-of-sight guidance method to mitigate abrupt changes in the yaw direction and smooth the heading changes when the AUV switches trajectory. The different experimental results show that the double deep Q-network algorithms ensure excellent collision avoidance performance. The effectiveness of the algorithm proposed in this paper was verified in three environments: random static, mixed static, and complex dynamic. The results show that the proposed algorithm has significant advantages over other algorithms in terms of success rate, collision avoidance performance, and generalization ability. The double deep Q-network algorithm proposed in this paper is superior to the genetic algorithm and deep learning in terms of the running time, total path, performance in avoiding collisions with moving obstacles, and planning time for each step. After the algorithm is trained in a simulated environment, it can still perform online learning according to the information of the environment after deployment and adjust the weight of the network in real-time. These results demonstrate that the proposed approach has significant potential for practical applications.

Alfalfa (Medicago sativa L.) MsCML46 gene encoding calmodulin-like protein confers tolerance to abiotic stress in tobacco - Binghao Du; Naiyu Chen; Lili Song; Dan Wang; Hongsheng Cai; Lin Yao; Xiuting Li; Changhong Guo (Plant Cell Reports, 2021)

Dynamics of antibiotic resistance and its association with bacterial community in a drinking water treatment plant and the residential area - Fu-Yi Huang; Qing-Lin Chen; Xian Zhang; Roy Neilson; Jian-Qiang Su; Shu-Yi-Dan Zhou (Environmental Science and Pollution Research, 2021)

Role of nucleus accumbens microRNA-181a and MeCP2 in incubation of heroin craving in male rats - Wenjin Xu; Qingxiao Hong; Zi Lin; Hong Ma; Weisheng Chen; Dingding Zhuang; Huaqiang Zhu; Miaojun Lai; Dan Fu; Wenhua Zhou; Huifen Liu (Psychopharmacology, 2021)

Advantage of Multi-Directional Stability of Spiral Clavicle Plate in Treatment of Middle One-Third Clavicle Fracture: A Finite Element Study - Dan-Kai Wu; Wen-Chuan Chen; Kun-Jhih Lin; Cheng-Lun Tsai; Kang-Ping Lin; Hung-Wen Wei (Journal of Medical and Biological Engineering, 2021)

Synthesis, characterization, and biological activity of selenium nanoparticles conjugated with polysaccharides - Xiao-Dan Shi; Yong-Qi Tian; Jiu-Lin Wu; Shao-Yun Wang (Critical Reviews in Food Science and Nutrition, 2021)

Natural constituents from food sources as therapeutic agents for obesity and metabolic diseases targeting adipose tissue inflammation - Dan Li; Tian Zhang; Jinjian Lu; Cheng Peng; Ligen Lin (Critical Reviews in Food Science and Nutrition, 2021)

Prenylated xanthones and biphenyls from Garcinia esculenta with antistaphylococcal activity - Dan Zheng; Hong Zhang; Jia-Ming Jiang; Yu-Yu Chen; Shi-Jie Wan; Zhi-Xiu Lin; Hong-Xi Xu (Natural Product Research, 2021)

Identification of a delayed leaf greening gene from a mutation of pummelo - Hui-Wen Yu; Zhi-Hao Lu; Xia Wang; Dan Liu; Jia-Xian He; Xiao-Lin Jiang; Ling-Jun Ke; Wen-Wu Guo; Xiu-Xin Deng; Qiang Xu (Science China Life Sciences, 2021)

Maribacter hydrothermalis sp. nov., Isolated from Shallow-Sea Hydrothermal Systems Off Kueishantao Island - Huaying Lin; Dan Lin; Mu Zhang; Jianing Ye; Jia Sun; Kai Tang (Current Microbiology, 2021)

p -Terphenyls and actinomycins from a Streptomyces sp. associated with the larva of mud dauber wasp - Dan-Dan Lu; Jin-Wei Ren; Qian-Qian Du; Ya-Jie Song; Shi-Qi Lin; Xia Li; Er-Wei Li; Wei-Dong Xie (Natural Product Research, 2021)

Luteolin alleviates ulcerative colitis through SHP-1/STAT3 pathway - Bo-Lin Li; Dan-Yang Zhao; Peng-Li Du; Xiao-Tian Wang; Qian Yang; Yan-Ru Cai (Inflammation Research, 2021)

Analysis of the palladium response relationship of a receiving water body under multiple scenario changes in rainfall-runoff pollution - Fangfang Ding; Yuyan Liu; Lin Wang; Haofeng Liu; Caiye Ji; Lan Zhang; Dan Wu (Environmental Science and Pollution Research, 2021)

QTL mapping of the genetic basis of stem diameter in soybean - Chong-Yuan Sun; Yu-Ming Yang; Lin Jia; Xiao-Qian Liu; Huan-Qing Xu; Hai-Yan Lv; Zhong-Wen Huang; Dan Zhang (Planta, 2021)

Amygdala-based Functional Network Reveals Dissociated Neural Correlates of Consensual and Idiosyncratic Emotional Movie Experiences - Lin Cui; Bingbing Guo; Dan Zhao; Jiaxin Li; Yu Luo; Ming Meng (Neuroscience Bulletin, 2021)

Rosanortriterpenes A–B, two new nortriterpenes from the fruits of Rosa laevigata var. leiocapus - Yu-Nong Tian; Bai-Lin Li; Juan-Juan Hu; Jin-Dan Xie; Wen-Jing Xiao; Ling-Hui Nie; Jie-Wei Wu (Natural Product Research, 2021)

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

A review on furan: Formation, analysis, occurrence, carcinogenicity, genotoxicity and reduction methods - Zahra Batool; Dan Xu; Xia Zhang; Xiaoxi Li; Yuting Li; Zhiyi Chen; Bing Li; Lin Li (Critical Reviews in Food Science and Nutrition, 2021)

Response of palladium in receiving water bodies to rainfall-runoff - Fangfang Ding; Yuyan Liu; Zucheng Wang; Caiye Ji; Dan Wu; Lin Wang; Bo Fu; Lan Zhang; Haofeng Liu (Environmental Science and Pollution Research, 2021)

Correction to: Establishment of Neurobehavioral Assessment System in Tree Shrew SCT Model - Yang-Yang Wang; Jie -Dong Wang; Lei Wang; Qi-Qin Dan; Qing- Jie Xia; Ting-Hua Wang; Liu-Lin Xiong (Journal of Molecular Neuroscience, 2021)

New application of lanthanum-modified bentonite (Phoslock®) for immobilization of arsenic in sediments - Jingzhen Cui; Dan Wang; Juan Lin; Yan Wang; Mingyi Ren; Youwei Yang; Pengling Shi (Environmental Science and Pollution Research, 2021)

Low ambient temperature increases hospital re-admissions for systemic lupus erythematosus in humid subtropical region: a time series study - Qian Wu; Zhiwei Xu; Yi-Lin Dan; Peng Wang; Yan-Mei Mao; Chan-Na Zhao; Yan-Feng Zou; Dong-Qing Ye; Wenbiao Hu; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Adakitic rocks at convergent plate boundaries: Compositions and petrogenesis - Qiang Wang; Lulu Hao; Xiuzheng Zhang; Jinsheng Zhou; Jun Wang; Qiwei Li; Lin Ma; Long Zhang; Yue Qi; Gongjian Tang; Wei Dan; Jingjing Fan (Science China Earth Sciences, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Two new compounds from the heartwood of Dalbergia melanoxylon - Shuai Lin; Rong-Hua Liu; Guang-Qiang Ma; Dan-Yi Mei; Feng Shao; Lan-Ying Chen (Natural Product Research, 2020)

Ridge subduction, magmatism, and metallogenesis - Qiang Wang; Gongjian Tang; Lulu Hao; Derek Wyman; Lin Ma; Wei Dan; Xiuzheng Zhang; Jinheng Liu; Tongyu Huang; Chuanbing Xu (Science China Earth Sciences, 2020)

Effect of dietary isoleucine on skin mucus barrier and epithelial physical barrier functions of hybrid bagrid catfish Pelteobagrus vachelli × Leiocassis longirostris - Long Yin; Ye Zhao; Xiao-Qiu Zhou; Chao Yang; Lin Feng; Yang Liu; Wei-Dan Jiang; Pei Wu; Jian Zhou; Juan Zhao; Jun Jiang (Fish Physiology and Biochemistry, 2020)

Neo-debromoaplysiatoxin C, with new structural rearrangement, derived from debromoaplysiatoxin - Yang-Hua Tang; Ting-Ting Liang; Ting-Ting Fan; Lawrence Jordan Keen; Xiao-Dan Zhang; Lin Xu; Qi Zhao; Rong Zeng; Bing-Nan Han (Natural Product Research, 2020)

Cinnamaldehyde improves the growth performance and digestion and absorption capacity in grass carp (Ctenopharyngodon idella) - Yang Zhou; Wei-Dan Jiang; Jin-Xiu Zhang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Yan Peng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

The dynamic process of dietary soybean β-conglycinin in digestion, absorption, and metabolism among different intestinal segments in grass carp (Ctenopharyngodon idella) - Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Jun Jiang; Bei-Ping Tan; Qi-Hui Yang; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

Supportive role of the Na+ transporter CmHKT1;1 from Cucumis melo in transgenic Arabidopsis salt tolerance through improved K+/Na+ balance - Li-Wei Gao; Sen-Lin Yang; Shi-Wei Wei; Dan-Feng Huang; Yi-Dong Zhang (Plant Molecular Biology, 2020)

Structure Elucidation and Mechanistic Study of a New Dimeric Degradant in Ropinirole Hydrochloride Extended-Release Tablets - Zijian Kuang; Tianpei Huang; Dan Li; Danna Zhao; Jianyang Jin; Jinsheng Lin; Wenquan Zhu; Wenbin Chen; Min Li; Weiyang Shen (Pharmaceutical Research, 2020)

Biofertilizers with beneficial rhizobacteria improved plant growth and yield in chili (Capsicum annuum L.) - Jing-Yi Gou; Sheng-Zhou Suo; Kun-Zhong Shao; Qi Zhao; Dan Yao; Hui-Ping Li; Jin-Lin Zhang; Christopher Rensing (World Journal of Microbiology and Biotechnology, 2020)

Long interpregnancy interval and adverse perinatal outcomes: A retrospective cohort study - Jing Lin; Han Liu; Dan-Dan Wu; Hong-Tao Hu; Hui-Hui Wang; Cheng-Liang Zhou; Xin-Mei Liu; Xiao-Jun Chen; Jian-Zhong Sheng; He-Feng Huang (Science China Life Sciences, 2020)

Beneficial consequences of Lupeol on middle cerebral artery-induced cerebral ischemia in the rat involves Nrf2 and P38 MAPK modulation - Zhiyuan Zhang; Chongfu Xu; Jiheng Hao; Meng Zhang; Zidong Wang; Tengkun Yin; Kai Lin; Weidong Liu; Qunlong Jiang; Zhongchen Li; Dan Wang; Zhiqi Mao; et al. (Metabolic Brain Disease, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

The effects of maternal exposure to BPA during pregnancy on the male reproductive system and the testicular microRNA expression profile - Lin Ma; Haiyang Yu; Xu Wang; Dan Li; Yumin Zhang; Xiucong Pei; Zhiwen Duan; Mingyue Ma (Environmental Science and Pollution Research, 2020)

The nucleic acid positive rate and genotype distribution of human cytomegalovirus in human milk banks in China - Xiaoyu Min; Lin Wang; Aili Cui; Chunli Zhang; Dan Wang; Ying Liu; Zhenghong Li; Wenbo Xu (Archives of Virology, 2020)

Nanochemoprevention with therapeutic benefits: An updated review focused on epigallocatechin gallate delivery - Qiong-Qiong Yang; Xin-Lin Wei; Ya-Peng Fang; Ren-You Gan; Min Wang; Ying-Ying Ge; Dan Zhang; Li-Zeng Cheng; Harold Corke (Critical Reviews in Food Science and Nutrition, 2020)

Abnormal differentiation of regulatory T cells and Th17 cells induced by perinatal bisphenol A exposure in female offspring mice - You-dan Dong; Liang Gao; Feng-juan Wu; Ren Lin; Yuan Meng; Li-hong Jia; Xiao-fei Wang (Molecular & Cellular Toxicology, 2020)

Effects of Dietary Supplementation of Recombinant Plectasin on Growth Performance, Intestinal Health and Innate Immunity Response in Broilers - Jing Lin Ma; Li Hua Zhao; Dan Dan Sun; Jing Zhang; Yong Peng Guo; Zhi Qiang Zhang; Qiu Gang Ma; Cheng Ji; Li Hong Zhao (Probiotics and Antimicrobial Proteins, 2020)

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

Establishment of Neurobehavioral Assessment System in Tree Shrew SCT Model - Yang-Yang Wang; Jie-Dong Wang; Lei Wang; Qi-Qin Dan; Qing-Jie Xia; Ting-Hua Wang; Liu-Lin Xiong (Journal of Molecular Neuroscience, 2020)

Transcriptome analysis of axillary bud differentiation in a new dual-axillary bud genotype of sugarcane - Dan Chen; Xin Lu; Xiaoyang Wu; Xiongmei Ying; Wenjie Long; Huosheng Su; Hongbo Liu; Xiuqin Lin; Chaohua Xu; Qing Cai (Genetic Resources and Crop Evolution, 2020)

Correction to: Microsatellite records for volume 10, issue 2 - Dan Yu; Xueyun Ding; Zhi Zhang; Yu Zeng; Huanzhang Liu; Lin Wang; Ye Gong; Xingtu Liu; Xianguo Lyu; Gregory R. McCracken; Francisca V. Valenzuela-Aguayo; Evelyn M. Habit; et al. (Conservation Genetics Resources, 2020)

Stilbenoids from aerial parts of Dendrobium plicatile - Dan-Na Chen; Yu-Ye Wang; Wen-Jian Liu; Yue-Juan Chen; Ya-Ping Wu; Jing-Xian Wang; Feng He; Lin Jiang (Natural Product Research, 2020)

The impact of uniform and nonuniform CO2 concentrations on global climatic change - Yongli Wang; Jinming Feng; Li Dan; Shan Lin; Jing Tian (Theoretical and Applied Climatology, 2020)

Joined fragment segmentation for fractured bones using GPU-accelerated shape-preserving erosion and dilation - Yue Zhang; Ruofeng Tong; Dan Song; Xiaobo Yan; Lanfen Lin; Jian Wu (Medical & Biological Engineering & Computing, 2020)

Nitrogen fertilizer enhances zinc and cadmium uptake by hyperaccumulator Sedum alfredii Hance - Ziwen Lin; Chunying Dou; Yongfu Li; Hailong Wang; Nabeel Khan Niazi; Shaobo Zhang; Dan Liu; Keli Zhao; Weijun Fu; Yongchun Li; Zhengqian Ye (Journal of Soils and Sediments, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Geochemistry of the fracture-cave calcite of the Ordovician Yingshan Formation and its paleokarst environment in the Tazhong area, Tarim Basin, China - Yong Dan; Liangbiao Lin; Bin Liang; Qingyu Zhang; Jianwen Cao; Jingrui Li (Carbonates and Evaporites, 2019)

Association between social health status and depressive symptoms among community-dwelling elderly adults in Zhejiang Province, China - Hong-lei Dai; Zhe-bin Yu; Liu-qing You; Min-hua Fan; Hong-wei Zhu; Dan-jie Jiang; Meng-yin Wu; Shu-juan Lin; Xiao-cong Zhang; Kun Chen (Journal of Zhejiang University-SCIENCE B, 2019)

Immunological microenvironment alterations in follicles of women with proven severe endometriosis undergoing in vitro fertilization - Xiao-Dan Mao; Chen-Yu Hu; Meng-Chu Zhu; Hui-Lin Ou; Yu-Li Qian (Molecular Biology Reports, 2019)

Soybean glycinin decreased growth performance, impaired intestinal health, and amino acid absorption capacity of juvenile grass carp (Ctenopharyngodon idella) - Ya-Lin Zhang; Xu-Dong Duan; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Wu-Neng Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2019)

Dietary tryptophan affects growth performance, digestive and absorptive enzyme activities, intestinal antioxidant capacity, and appetite and GH–IGF axis-related gene expression of hybrid catfish (Pelteobagrus vachelli♀ × Leiocassis longirostris♂) - Ye Zhao; Xiao-yun Wu; Shang-xiao Xu; Jia-yuan Xie; Kai-wen Xiang; Lin Feng; Yang Liu; Wei-dan Jiang; Pei Wu; Juan Zhao; Xiao-qiu Zhou; Jun Jiang (Fish Physiology and Biochemistry, 2019)

Rapamycin Removes Damaged Mitochondria and Protects Human Trabecular Meshwork (TM-1) Cells from Chronic Oxidative Stress - Jing Na He; Shao Dan Zhang; Yang Qu; Hai Lin Wang; Clement C. Tham; Chi Pui Pang; Wai Kit Chu (Molecular Neurobiology, 2019)

STAT3-induced SMYD3 transcription enhances chronic lymphocytic leukemia cell growth in vitro and in vivo - Fujia Lin; Danjuan Wu; Dan Fang; Yao Chen; Haitao Zhou; Caiwen Ou (Inflammation Research, 2019)

Differential Transcriptomic and Metabolomic Responses in the Liver of Nile Tilapia (Oreochromis niloticus) Exposed to Acute Ammonia - Zong Xian Zhu; Dan Li Jiang; Bi Jun Li; Hui Qin; Zi Ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Early secreted antigenic target of 6-kDa of Mycobacterium tuberculosis promotes caspase-9/caspase-3-mediated apoptosis in macrophages - Jiahui Lin; Qun Chang; Xueting Dai; Dan Liu; Yuyin Jiang; Yalei Dai (Molecular and Cellular Biochemistry, 2019)

QTL analysis of delayed maize flowering in response to low phosphate across multi-environments - Zhiyong Ren; Xiao Zhang; Hailan Liu; Wenjun Liu; Zhi Nie; Dan Liu; Ling Wu; Haijian Lin; Shunzong Su; Duojiang Gao; Bowen Luo; Peng Ma; et al. (Euphytica, 2019)

Role of mTOR complex in IGF-1 induced neural differentiation of DPSCs - Dan Huang; Shuling Shen; Ming Cai; Lin Jin; Jun Lu; Ke Xu; Jinlong Zhang; Guijuan Feng; Yingzi Hu; Ke Zheng; Xingmei Feng (Journal of Molecular Histology, 2019)

The LRP6 functional mutation rs2302685 contributes to individual susceptibility to alcoholic liver injury related to the Wnt/β-catenin-TCF1-CYP2E1 signaling pathway - Ying Xu; Dan Chen; Xiu-Xian Lin; Qing Zhao; Jing Guo; Li-jie Chen; Wei Zhang; Jian Xiao; Guang-Hui Lian; Shi-Fang Peng; Dong Guo; Hong Yang; et al. (Archives of Toxicology, 2019)

Identifying a Long QTL Cluster Across chrLG18 Associated with Salt Tolerance in Tilapia Using GWAS and QTL-seq - Dan Li Jiang; Xiao Hui Gu; Bi Jun Li; Zong Xian Zhu; Hui Qin; Zi ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Trace metal pollution and ecological risk assessment in agricultural soil in Dexing Pb/Zn mining area, China - Junjie Hu; Boji Lin; Meiyi Yuan; Zhilang Lao; Kangming Wu; Yanyan Zeng; Zhihui Liang; Huiru Li; Yanliang Li; Dan Zhu; Junlong Liu; Hongbo Fan (Environmental Geochemistry and Health, 2019)

Detection and genetic characterization of porcine pegivirus from pigs in China - Dan Lei; Yu Ye; Kun Lin; Fanfan Zhang; Dongyan Huang; Kai Li; Weifeng Yuan; Qiong Wu; Zhen Ding; Leyi Wang; Deping Song; Yuxin Tang (Virus Genes, 2019)

Bioavailability of selenium in soil-plant system and a regulatory approach - Quang Toan Dinh; Mengke Wang; Thi Anh Thu Tran; Fei Zhou; Dan Wang; Hui Zhai; Qin Peng; Mingyue Xue; Zekun Du; Gary S. Bañuelos; Zhi-Qing Lin; Dongli Liang (Critical Reviews in Environmental Science and Technology, 2019)

The effect of phosphorus addition, soil moisture, and plant type on soil nematode abundance and community composition - Olusanya Abiodun Olatunji; Shanxing Gong; Akash Tariq; Kaiwen Pan; Xiaoming Sun; Wenkai Chen; Lin Zhang; Mohammed A. Dakhil; Dan Huang; Xue Tan (Journal of Soils and Sediments, 2019)

The research progress in mechanism and influence of biosorption between lactic acid bacteria and Pb(II): A review - Derong Lin; Ran Ji; Dan Wang; Mengshi Xiao; Jingjing Zhao; Jinpeng Zou; Yutong Li; Tao Qin; Baoshan Xing; Yuan Chen; Peng Liu; Zhijun Wu; et al. (Critical Reviews in Food Science and Nutrition, 2019)

Genome-wide analysis identified 17 new loci influencing intraocular pressure in Chinese population - Lulin Huang; Yuhong Chen; Ying Lin; Pancy O. S. Tam; Yilian Cheng; Yi Shi; Bo Gong; Fang Lu; Jialiang Yang; Haixin Wang; Yi Yin; Yong Cao; et al. (Science China Life Sciences, 2019)

Noise reduction for desert seismic data using spectral kurtosis adaptive bandpass filter - Haitao Ma; Zebin Qian; Yue Li; Hongbo Lin; Dan Shao; Baojun Yang (Acta Geophysica, 2019)

A new benzofuran from the heartwood of Dalbergia latifolia - Rong-Hua Liu; Dan-Yi Mei; Shuai Lin; Ding-Qing Wang; Feng Shao; Lan-Ying Chen; Shan-Liang Guo (Natural Product Research, 2019)

Assessment of frozen ground organic carbon pool on the Qinghai-Tibet Plateau - Lin Jiang; Huai Chen; Qiuan Zhu; Yanzheng Yang; Mingxu Li; Changhui Peng; Dan Zhu; Yixin He (Journal of Soils and Sediments, 2019)

Chemical nature of soil organic carbon under different long-term fertilization regimes is coupled with changes in the bacterial community composition in a Calcaric Fluvisol - Dandan Li; Lin Chen; Jisheng Xu; Lei Ma; Dan C. Olk; Bingzi Zhao; Jiabao Zhang; Xiuli Xin (Biology and Fertility of Soils, 2018)

Structure elucidation and antitumour activity of a new macrolactam produced by marine-derived actinomycete Micromonospora sp. FIM05328 - Yi-Lei Nie; Yun-Dan Wu; Chuan-Xi Wang; Ru Lin; Yang Xie; Dong-Sheng Fang; Hong Jiang; Yun-Yang Lian (Natural Product Research, 2018)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Effects of Different Treatments on Fishy Odor of Fish Soups - Dan-Dan Xue; Tian-Peng He; Meng-Chen You; Huan-Lu Song; Lin Gong; Wenqing Pan (Journal of Aquatic Food Product Technology, 2018)

Expression of BC1 Impairs Spatial Learning and Memory in Alzheimer’s Disease Via APP Translation - Tongmei Zhang; Pei Pang; Zemin Fang; Yu Guo; Hao Li; Xinyan Li; Tian Tian; Xin Yang; Wenting Chen; Shu Shu; Na Tang; Jianhua Wu; et al. (Molecular Neurobiology, 2018)

Plasma miR-124 Is a Promising Candidate Biomarker for Human Intracerebral Hemorrhage Stroke - Zifeng Wang; Gang Lu; Johnny Sze; Yao Liu; Sheng Lin; Hong Yao; Ji Zhang; Dan Xie; Quentin Liu; Hsiang-fu Kung; Marie Chia-mi Lin; Wai Sang Poon (Molecular Neurobiology, 2018)

MiR-519d-3p suppresses breast cancer cell growth and motility via targeting LIM domain kinase 1 - Dengfeng Li; Hongming Song; Tianqi Wu; Dan Xie; Jiashu Hu; Junyong Zhao; Qiang Shen; Lin Fang (Molecular and Cellular Biochemistry, 2018)

Effects of body mass index on the outcomes of in vitro fertilization in Chinese patients with polycystic ovary syndrome: a retrospective cohort study - Xiao-ming Pan; Zhong Lin; Nan Li; Jia-qi Wu; Dan-qing Chen; Yi-min Zhu; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2018)

Responses of Tree Transpiration and Growth to Seasonal Rainfall Redistribution in a Subtropical Evergreen Broad-Leaved Forest - Yanting Hu; Ping Zhao; Weijun Shen; Liwei Zhu; Guangyan Ni; Xiuhua Zhao; Zhenzhen Zhang; Xingquan Rao; Lei Ouyang; Xiaomin Zeng; Dan Sun; Yongbiao Lin (Ecosystems, 2018)

A new pair of enantiomeric lignans from the fruits of Morinda citrifolia and their absolute configuration - Wen-Jian Liu; Yue-Juan Chen; Dan-Na Chen; Ya-Ping Wu; Yu-Jie Gao; Jing Li; Wen-Jun Zhong; Lin Jiang (Natural Product Research, 2018)

Sorption-desorption behaviors of heavy metals by biochar-compost amendment with different ratios in contaminated wetland soil - Zhaoxue Yang; Jie Liang; Lin Tang; Guangming Zeng; Man Yu; Xiaodong Li; Xuemei Li; Yingying Qian; Haipeng Wu; Yuan Luo; Dan Mo (Journal of Soils and Sediments, 2018)

Comparative genomic analysis of the Lipase3 gene family in five plant species reveals distinct evolutionary origins - Dan Wang; Lin Zhang; JunFeng Hu; Dianshuai Gao; Xin Liu; Yan Sha (Genetica, 2018)

Antibacterial constituents from Antarctic fungus, Aspergillus sydowii SP-1 - Wen-ting Li; Dan Luo; Jia-ning Huang; Lin-lin Wang; Feng-guo Zhang; Tao Xi; Jian-min Liao; Yuan-yuan Lu (Natural Product Research, 2018)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

Development of a stable Japanese encephalitis virus replicon cell line for antiviral screening - Qiu-Yan Zhang; Xiao-Dan Li; Si-Qing Liu; Cheng-Lin Deng; Bo Zhang; Han-Qing Ye (Archives of Virology, 2017)

Comparison of the ameliorative effects of Qingfei Tongluo formula and azithromycin on Mycoplasma pneumoniae pneumonia - Zhen Xiao; Yonghong Jiang; Xuan Gao; Shuzhu Lin; Yan Lin; Xiuxiu Liu; Dan Tan; Zhiyan Jiang (Journal of Natural Medicines, 2017)

Male-Produced Aggregation Pheromone of Coffee Bean Weevil, Araecerus fasciculatus - Shuai Yang; Xiao-Fang Zhang; Yu-Lin Gao; Dan Chen; Dong-Mei She; Tao Zhang; Jun Ning (Journal of Chemical Ecology, 2017)

Global changes of 5-hydroxymethylcytosine and 5-methylcytosine from normal to tumor tissues are associated with carcinogenesis and prognosis in colorectal cancer - Yi-ping Tian; Ai-fen Lin; Mei-fu Gan; Hao Wang; Dan Yu; Chong Lai; Dan-dan Zhang; Yi-min Zhu; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2017)

An amplitude suppression method based on the decibel criterion - Xuan-Lin Kong; Hui Chen; Jin-Long Wang; Zhi-quan Hu; Dan Xu; Lu-Ming Li (Applied Geophysics, 2017)

Interleukin-18, matrix metalloproteinase-22 and -29 are independent risk factors of human coronary heart disease - Dong-Yi Jin; Cong-Lin Liu; Jun-Nan Tang; Zhao-Zhong Zhu; Xue-Xi Xuan; Xiao-Dan Zhu; Yun-Zhe Wang; Tian-Xia Zhang; De-Liang Shen; Xiao-Fang Wang; Guo-Ping Shi; Jin-Ying Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

Evaluation of climatic variables as yield‐limiting factors for maize in Kansas - Qing Ye; Xiaomao Lin; Eric Adee; Doohong Min; Yared Assefa Mulisa; Dan O'Brien; Ignacio A. Ciampitti (International Journal of Climatology, 2017)
Kansas is situated from the lower Missouri Basin to the high plains lying along the eastern slope of the Rockies so that distinct climates across the state make crop production systems vulnerable to changes in climate. Based on climatic indices such as growing degree‐day ( GDD ), extreme degree‐day ( EDD ), and precipitation (P), this study assessed the sensitivity of maize ( Zea mays L.) yield to a changing climate for seven diverse cropping areas from 1981 to 2013 across Kansas. Our results indicated that maize yield increased by 2.4 and 3.4% per annum 100 GDD increase under non‐irrigated (i.e. rainfed) and irrigated environments, respectively. Maize yield positive response to changes in GDD during the pre‐silking period was more significantly pronounced for irrigated environments than rainfed sites. Rainfed yields showed a significantly negative response to EDD (−3.0% per +10 EDD ) compared with irrigated environments (−1.2% per +10 EDD ). This EDD negative effect was more pronounced during post‐silking growth as compared with the pre‐silking period for both irrigated and non‐irrigated conditions. Yield sensitivity to a unit change of P (mm) was less than the sensitivity to a unit change of GDD (in °C days) and EDD (in °C days) indices. Nonetheless, maize productivity has a positive response to post‐silking P with a greater yield gain at rainfed sites compared with irrigated sites. Irrigation could partially mitigate the effect of extreme heat on maize yield potential. Because the frequency of extreme temperatures and P are predicted to increase in Kansas and the Great Plains region, this study might provide guidelines to farmers, crop consultants, and agronomists to manage maize production thereby providing the ability to mitigate or adapt to climate change impacts.

Phenolic compounds from the stems of Flickingeria fimbriata - Ya-Ping Wu; Wen-Jian Liu; Wen-Jun Zhong; Yue-Juan Chen; Dan-Na Chen; Feng He; Lin Jiang (Natural Product Research, 2017)

An improved temporal correction method for mobile measurement of outdoor thermal climates - Lin Liu; Yaoyu Lin; Dan Wang; Jing Liu (Theoretical and Applied Climatology, 2017)

The Interaction of Mitochondrial Biogenesis and Fission/Fusion Mediated by PGC-1α Regulates Rotenone-Induced Dopaminergic Neurotoxicity - Kaige Peng; Likui Yang; Jian Wang; Feng Ye; Guorong Dan; Yuanpeng Zhao; Ying Cai; Zhihong Cui; Lin Ao; Jinyi Liu; Zhongmin Zou; Yan Sai; et al. (Molecular Neurobiology, 2017)

Densoviruses in oyster Crassostrea ariakensis - Yan-Jun Kang; Wei Huang; A-li Zhao; Dan-Dan Lai; Lin Shao; Yan-Qin Shen; Xutao Deng; Eric Delwart; Wen Zhang (Archives of Virology, 2017)

NMR-based metabolomics reveals brain region-specific metabolic alterations in streptozotocin-induced diabetic rats with cognitive dysfunction - Hong Zheng; Qiuting Lin; Dan Wang; Pengtao Xu; Liangcai Zhao; Wenyi Hu; Guanghui Bai; Zhihan Yan; Hongchang Gao (Metabolic Brain Disease, 2017)

Anti-neuroinflammatory constituents from the fungus Penicillium purpurogenum MHZ 111 - Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Yi Ren; Dan Dong; Jiao Zheng; Ting Liu; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Effects of pre-pregnancy body mass index and gestational weight gain on neonatal birth weight - Meng-kai Du; Li-ya Ge; Meng-lin Zhou; Jun Ying; Fan Qu; Min-yue Dong; Dan-qing Chen (Journal of Zhejiang University-SCIENCE B, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Salidroside accelerates fracture healing through cell-autonomous and non-autonomous effects on osteoblasts - Xiao Qin Guo; Lin Qi; Jing Yang; Yue Wang; Chuan Wang; Zong Min Li; Ling Li; Ye Qu; Dan Wang; Ze Min Han (Cell and Tissue Research, 2017)

A new piperidine alkaloid from the leaves of Microcos paniculata L. - Gang Zhang; Na Zhang; Li Xu; Hong-Tan Wu; Dan Chen; Qi-Huang Lin; Lian-Zhong Luo (Natural Product Research, 2017)

First discovery of a Palaeoproterozoic A-type granite in southern Wuyishan terrane, Cathaysia Block: evidence from geochronology, geochemistry, and Nd–Hf–O isotopes - Zhi-Hong Chen; Ling Zhao; Dan-Dan Chen; Xi-Lin Zhao; Guang-Fu Xing (International Geology Review, 2017)

Synthesis and evaluation of novel benzene-ethanol bearing 1,2,4-triazole derivatives as potential antimicrobial agents - Bochao Li; Dawei Zhang; Yumin Zhang; Dan Jiang; Shuang Li; Wei Lei; Huiying Wang; Feng Lin (Medicinal Chemistry Research, 2017)

NMR-Based Metabolomics Reveal a Recovery from Metabolic Changes in the Striatum of 6-OHDA-Induced Rats Treated with Basic Fibroblast Growth Factor - Hong Zheng; Liangcai Zhao; Huanhuan Xia; Cuicui Xu; Dan Wang; Kun Liu; Li Lin; Xiaokun Li; Zhihan Yan; Hongchang Gao (Molecular Neurobiology, 2016)

Soil properties and species composition under different grazing intensity in an alpine meadow on the eastern Tibetan Plateau, China - Zhen’an Yang; Wan Xiong; Yingyi Xu; Lin Jiang; Erxiong Zhu; Wei Zhan; Yixin He; Dan Zhu; Qiuan Zhu; Changhui Peng; Huai Chen (Environmental Monitoring and Assessment, 2016)

Sialylation and desialylation dynamics of monocytes upon differentiation and polarization to macrophages - Dan Wang; Evgeny Ozhegov; Lin Wang; Aimin Zhou; Huan Nie; Yu Li; Xue-Long Sun (Glycoconjugate Journal, 2016)

FGF21 ameliorates nonalcoholic fatty liver disease by inducing autophagy - Shenglong Zhu; Yunzhou Wu; Xianlong Ye; Lei Ma; Jianying Qi; Dan Yu; Yuquan Wei; Guangxiao Lin; Guiping Ren; Deshan Li (Molecular and Cellular Biochemistry, 2016)

Identification and characterization of differentially expressed miRNAs between bamboo shoot and rhizome shoot - Qun-Ying Jin; Hua-Zheng Peng; Er-Pei Lin; Nan Li; Dan-Ni Huang; Yan-Li Xu; Xi-Qi Hua; Kui-Hong Wang; Tang-Jun Zhu (Journal of Plant Biology, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Lack of association between polymorphisms in interleukin (IL)-12, IL-12R, IL-23, IL-23R genes and Takayasu arteritis in a Chinese population - Kun-Qi Yang; Yan-Kun Yang; Xu Meng; Ying Zhang; Xiong-Jing Jiang; Hai-Ying Wu; Hui-Min Zhang; Lei Song; Jin Bian; Dan Wen; Lin-Ping Wang; Xian-Liang Zhou (Inflammation Research, 2016)

Reverse transcription genome exponential amplification reaction assay for rapid and universal detection of human rhinoviruses - Li Guan; Lin-Qing Zhao; Hang-Yu Zhou; Kai Nie; Xin-Na Li; Dan Zhang; Juan Song; Yuan Qian; Xue-Jun Ma (Archives of Virology, 2016)

Overexpression of SsDGAT2 from Sapium sebiferum (L.) Roxb Increases Seed Oleic Acid Level in Arabidopsis - YiQiang Wang; Dan Peng; Lin Zhang; XiaoFeng Tan; DeYi Yuan; XuanMing Liu; Bo Zhou (Plant Molecular Biology Reporter, 2016)

The phytotoxic effects of selenium–mercury interactions on root growth in Brassica rapa (LvLing) - Zhi-Wei Bian; Jian Chen; Hui Li; Dan-Dan Liu; Li-Fei Yang; Yue-Lin Zhu; Wen-Li Zhu; Wei Liu; Zheng-Zheng Ying (Horticulture, Environment, and Biotechnology, 2016)

Pacificimonas aurantium sp. nov., Isolated from the Seawater of the Pacific Ocean - Shuhui Li; Wenchu Zhou; Dan Lin; Kai Tang; Nianzhi Jiao (Current Microbiology, 2016)

Dielectric barrier discharge plasma induced degradation of aqueous atrazine - Jingwei Feng; Lin Jiang; Dan Zhu; Kuizu Su; Dayong Zhao; Jibiao Zhang; Zheng Zheng (Environmental Science and Pollution Research, 2016)

Phase 1 clinical trial demonstrated that MUC1 positive metastatic seminal vesicle cancer can be effectively eradicated by modified Anti-MUC1 chimeric antigen receptor transduced T cells - Fengtao You; Licui Jiang; Bozhen Zhang; Qiang Lu; Qiao Zhou; Xiaoyang Liao; Hong Wu; Kaiqi Du; Youcai Zhu; Huimin Meng; Zhishu Gong; Yunhui Zong; et al. (Science China Life Sciences, 2016)

Vermicomposting of sludge from animal wastewater treatment plant mixed with cow dung or swine manure using Eisenia fetida - Dan Xie; Weibing Wu; Xiaoxia Hao; Dongmei Jiang; Xuewei Li; Lin Bai (Environmental Science and Pollution Research, 2016)

Experimental Investigation on Non-Darcian Flow in Unbound Graded Aggregate Material of Highway Pavement - Han-Cheng Dan; Lin-Hua He; Bo Xu (Transport in Porous Media, 2016)

Therapeutic Intervention of Learning and Memory Decays by Salidroside Stimulation of Neurogenesis in Aging - Huijuan Jin; Lei Pei; Xiaogang Shu; Xin Yang; Tianhua Yan; Yan Wu; Na Wei; Honglin Yan; Shan Wang; Chengye Yao; Dan Liu; Qing Tian; et al. (Molecular Neurobiology, 2016)

QTL mapping of flag leaf traits in common wheat using an integrated high-density SSR and SNP genetic linkage map - Qiuhong Wu; Yongxing Chen; Lin Fu; Shenghui Zhou; Jiaojiao Chen; Xiaojie Zhao; Dong Zhang; Shuhong Ouyang; Zhenzhong Wang; Dan Li; Guoxin Wang; Deyun Zhang; et al. (Euphytica, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

The complete mitochondrial genome of fall armyworm Spodoptera frugiperda (Lepidoptera:Noctuidae) - Qiu-Ning Liu; Xin-Yue Chai; Dan-Dan Bian; Bao-Ming Ge; Chun-Lin Zhou; Bo-Ping Tang (Genes & Genomics, 2016)

Social Isolation During Adolescence Strengthens Retention of Fear Memories and Facilitates Induction of Late-Phase Long-Term Potentiation - Ji-Hong Liu; Qiang-Long You; Mei-Dan Wei; Qian Wang; Zheng-Yi Luo; Song Lin; Lang Huang; Shu-JI Li; Xiao-Wen Li; Tian-Ming Gao (Molecular Neurobiology, 2015)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

Effects of 3,5-Diiodotyrosine and Potassium Iodide on Thyroid Function and Oxidative Stress in Iodine-Excess Wistar Rats - Dan Liu; Xinying Lin; Fugui Yu; Man Zhang; Hongxia Chen; Wei Bao; Xia Wang (Biological Trace Element Research, 2015)

Two new eunicellin diterpenoids from the South China Sea gorgonian Muricella sibogae and their bioactivities - Xing-Wang Zhang; Xu-Li Tang; Hong-Rui Yuan; Dan-Qing Feng; Pei Su; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2015)

A Numerical Study of Water Loss Rate Distributions in MDCT-Based Human Airway Models - Dan Wu; Shinjiro Miyawaki; Merryn H. Tawhai; Eric A. Hoffman; Ching-Long Lin (Annals of Biomedical Engineering, 2015)

Effects of glutamate on growth, antioxidant capacity, and antioxidant-related signaling molecule expression in primary cultures of fish enterocytes - Jun Jiang; Dan Shi; Xiao-Qiu Zhou; Long Yin; Lin Feng; Yang Liu; Wei-Dan Jiang; Ye Zhao (Fish Physiology and Biochemistry, 2015)

Isolation of a new flavanone from Daidai fruit and hypolipidemic activity of total flavonoids extracts - Ling-Jun Zeng; Dan Chen; Qing-De Huang; Qun Huang; Yun-Fang Lian; Wei-Wei Cai; Hua-Ping Zeng; Yi-Li Lin (Natural Product Research, 2015)

Effect of Excessive Potassium Iodide on Rat Aorta Endothelial Cells - Man Zhang; Xiaoyan Zou; Xinying Lin; Jianchao Bian; Huicui Meng; Dan Liu (Biological Trace Element Research, 2015)

ERK Is Involved in the Process of Acrosome Reaction In Vitro of the Chinese Mitten Crab, Eriocheir sinensis - Wen-Juan Sun; Ming Zhu; Yuan-Li Wang; Qing Li; Hong-Dan Yang; Ze-Lin Duan; Lin He; Qun Wang (Marine Biotechnology, 2015)

Effect of dietary glutamine on growth performance, non-specific immunity, expression of cytokine genes, phosphorylation of target of rapamycin (TOR), and anti-oxidative system in spleen and head kidney of Jian carp (Cyprinus carpio var. Jian) - Kai Hu; Jing-Xiu Zhang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Jun Jiang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2015)

Arsenic tolerance, uptake, and accumulation by nonmetallicolous and metallicolous populations of Pteris vittata L - Fuyong Wu; Dan Deng; Shengchun Wu; Xiangui Lin; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Simultaneous determination of six constituents in Mahuang Fuzi Xixin by UPLC-PDA–MS/MS - Lin Zhang; Chengying Wang; Dezu Miao; Dan Yuan; Kaishun Bi; Jingyu Yang; Libin Zhan (Natural Product Research, 2015)

Energy balance-based SWAT model to simulate the mountain snowmelt and runoff — taking the application in Juntanghu watershed (China) as an example - Xian-Yong Meng; Dan-Lin Yu; Zhi-Hui Liu (Journal of Mountain Science, 2015)

Antidepressant-like effects of ferulic acid: involvement of serotonergic and norepinergic systems - Jianliang Chen; Dan Lin; Chong Zhang; Gaowen Li; Nianping Zhang; Lina Ruan; Qizhi Yan; Jianxin Li; Xuefeng Yu; Xupei Xie; Cong Pang; Liang Cao; et al. (Metabolic Brain Disease, 2015)

Network Analysis of Functional Brain Connectivity Driven by Gamma-Band Auditory Steady-State Response in Auditory Hallucinations - Jun Ying; Dan Zhou; Ke Lin; Xiaorong Gao (Journal of Medical and Biological Engineering, 2015)

Genetic variation in estrogen and progesterone pathway genes and breast cancer risk: an exploration of tumor subtype-specific effects - Sarah J. Nyante; Marilie D. Gammon; Jay S. Kaufman; Jeannette T. Bensen; Dan Yu Lin; Jill S. Barnholtz-Sloan; Yijuan Hu; Qianchuan He; Jingchun Luo; Robert C. Millikan (Cancer Causes & Control, 2015)

Compounds from marine-derived Verrucosispora sp. FIM06054 and their potential antitumour activities - Nie Yi-Lei; Wu Yun-Dan; Wang Chuan-Xi; Lin Ru; Xie Yang; Fang Dong-Sheng; Jiang Hong; Lian Yun-Yang (Natural Product Research, 2014)

Mechanism of bFGF-binding Peptide Reversing Adriamycin Resistance in Human Gastric Cancer Cells - Xiangpeng Tan; Xilei Chen; Tao Huang; Wu Luo; Dan He; Xiaomian Lin; Li Song; Xiaoping Wu (International Journal of Peptide Research and Therapeutics, 2014)

Changes of vertical groundwater recharge with increase in thickness of vadose zone simulated by one-dimensional variably saturated flow model - Siyuan Huo; Menggui Jin; Xing Liang; Dan Lin (Journal of Earth Science, 2014)

Calcitonin Gene-Related Peptide Inhibits Osteolytic Factors Induced by Osteoblast In Co-Culture System with Breast Cancer - Hui Zhao; Lin-lin Ning; Zhi-yu Wang; Hong-tao Li; Dan Qiao; Yang Yao; Huan-long Qin (Cell Biochemistry and Biophysics, 2014)

A Numerical Study of Heat and Water Vapor Transfer in MDCT-Based Human Airway Models - Dan Wu; Merryn H. Tawhai; Eric A. Hoffman; Ching-Long Lin (Annals of Biomedical Engineering, 2014)

TM4SF1: a new vascular therapeutic target in cancer - Chi-Iou Lin; Anne Merley; Tracey E. Sciuto; Dan Li; Ann M. Dvorak; Juan M. Melero-Martin; Harold F. Dvorak; Shou-Ching S. Jaminet (Angiogenesis, 2014)

The study of regulatory effects of Pdx-1, MafA and NeuroD1 on the activity of porcine insulin promoter and the expression of human islet amyloid polypeptide - Xiao-Dan Liu; Jin-Xue Ruan; Ji-Han Xia; Shu-Lin Yang; Jun-Hua Fan; Kui Li (Molecular and Cellular Biochemistry, 2014)

Theranostic Nanoparticles for Cancer and Cardiovascular Applications - Dan Wang; Bingbing Lin; Hua Ai (Pharmaceutical Research, 2014)

The effects of dietary thiamin on oxidative damage and antioxidant defence of juvenile fish - Xue-Yin Li; Hui-Hua Huang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Shu-Hong Li; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Effect of copper-induced oxidative stress on sclerotial differentiation and antioxidant properties of Penicillium thomii PT95 strain - Ze-Qing Zhang; Wen-Jing Zhao; Dan-Dan Long; Lin-Ru Niu; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

In vitro exposure to copper influences lipid metabolism in hepatocytes from grass carp (Ctenopharyngodon idellus) - Qing-Ling Zhu; Zhi Luo; Mei-Qin Zhuo; Xiao-Ying Tan; Lin-Dan Sun; Jia-Lang Zheng; Qi-Liang Chen (Fish Physiology and Biochemistry, 2014)

Two new compounds from a marine-derived fungus Penicillium oxalicum - Pei-Le Wang; Dan-Yi Li; Lei-Rui Xie; Xin Wu; Hui-Ming Hua; Zhan-Lin Li (Natural Product Research, 2014)

Spatial and temporal analysis of drought risk during the crop-growing season over northeast China - Xingyang Yu; Xingyuan He; Haifeng Zheng; Ruichao Guo; Zhibin Ren; Dan Zhang; Jixiang Lin (Natural Hazards, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

Generation of GGTA1 biallelic knockout pigs via zinc-finger nucleases and somatic cell nuclear transfer - Lei Bao; HaiDe Chen; UiMyong Jong; CholHo Rim; WenLing Li; XiJuan Lin; Dan Zhang; Qiong Luo; Chun Cui; HeFeng Huang; Yan Zhang; Lei Xiao; et al. (Science China Life Sciences, 2014)

Three new diterpenoids from the resin of Liquidambar formosana - Hong-Jie Shang; Dan-Yi Li; Wen-Jing Wang; Zhan-Lin Li; Hui-Ming Hua (Natural Product Research, 2014)

MicroRNA Expression Aberration in Chinese Patients with Relapsing Remitting Multiple Sclerosis - Dan Yang; Wei-Zhi Wang; Xue-Mei Zhang; Hui Yue; Bing Li; Lin Lin; Jin Fu (Journal of Molecular Neuroscience, 2014)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

A functional variant of pre-miRNA-196a2 confers risk for Behcet’s disease but not for Vogt–Koyanagi–Harada syndrome or AAU in ankylosing spondylitis - Jian Qi; Shengping Hou; Qi Zhang; Dan Liao; Lin Wei; Jing Fang; Yan Zhou; Aize Kijlstra; Peizeng Yang (Human Genetics, 2013)

DC Electric Fields Direct Breast Cancer Cell Migration, Induce EGFR Polarization, and Increase the Intracellular Level of Calcium Ions - Dan Wu; Xiuli Ma; Francis Lin (Cell Biochemistry and Biophysics, 2013)

Isolation and characterization of microsatellite loci in the short-tailed pit viper Gloydius brevicaudus (Viperidae) - Li Ma; Qing-Lin Tong; Ce Chen; Ying-Dan Pan; Long-Hui Lin (Conservation Genetics Resources, 2013)

Estimating groundwater recharge beneath irrigated farmland using environmental tracers fluoride, chloride and sulfate - Dan Lin; Menggui Jin; Xing Liang; Hongbin Zhan (Hydrogeology Journal, 2013)

Human white adipose tissue vasculature contains endothelial colony-forming cells with robust in vivo vasculogenic potential - Ruei-Zeng Lin; Rafael Moreno-Luna; Rocio Muñoz-Hernandez; Dan Li; Shou-Ching S. Jaminet; Arin K. Greene; Juan M. Melero-Martin (Angiogenesis, 2013)

IFNG polymorphisms are associated with tuberculosis in Han Chinese pediatric female population - Chen Shen; Wei-Wei Jiao; Wei-Xing Feng; Xi-Rong Wu; Jing Xiao; Qing Miao; Lin Sun; Bin-Bin Wang; Jing Wang; Fang Liu; Dan Shen; A-Dong Shen (Molecular Biology Reports, 2013)

A novel role of ribonuclease inhibitor in regulation of epithelial-to-mesenchymal transition and ILK signaling pathway in bladder cancer cells - Xue Yao; Dan Li; Dong-mei Xiong; Lin Li; Rong Jiang; Jun-xia Chen (Cell and Tissue Research, 2013)

Analysis of artificial corner reflector’s radar cross section: a physical optics perspective - Xin-Jian Shan; Jing-Yuan Yin; Dan-Lin Yu; Cheng-Fan Li; Jun-Juan Zhao; Gui-Fang Zhang (Arabian Journal of Geosciences, 2013)

Celastrol exerts synergistic effects with PHA-665752 and inhibits tumor growth of c-Met-deficient hepatocellular carcinoma in vivo - Hong-Lei Jiang; Jun-Zhe Jin; Dan Wu; Dong Xu; Guo-Fu Lin; Hao Yu; Dong-Yan Ma; Jian Liang (Molecular Biology Reports, 2013)

A new cyclonerol derivative from a marine-derived fungus Ascotricha sp. ZJ-M-5 - Lei-Rui Xie; Dan-Yi Li; Zhan-Lin Li; Hui-Ming Hua; Pei-Le Wang; Xin Wu (Natural Product Research, 2013)

Construction and analysis of different expression cDNA libraries in Rehmannia glutinosa plants subjected to continuous cropping - Yan Hui Yang; Zhong Yi Zhang; Hua Min Fan; Yi Dan Zhao; Ming Jie Li; Juan Li; Jun Ying Chen; Wen Xiong Lin; Xin Jian Chen (Acta Physiologiae Plantarum, 2013)

Two new triterpenoid saponins from the husks of Xanthoceras sorbifolia - Zhan-Lin Li; Dan-Yi Li; Xiao-Meng He; Hui-Ming Hua (Natural Product Research, 2013)

Biodegradation of poly(ε-caprolactone) (PCL) by a new Penicillium oxalicum strain DSYD05-1 - Fan Li; Dan Yu; Xiumei Lin; Dongbo Liu; Hongmei Xia; Shan Chen (World Journal of Microbiology and Biotechnology, 2012)

The dissection and SSR mapping of a high-temperature adult-plant stripe rust resistance gene in American spring wheat cultivar Alturas - Lei Zhao; Jing Feng; Chun-Yu Zhang; Xiao-Dan Xu; Xian-Ming Chen; Quan Sun; Qing Miao; Shi-Chang Xu; Feng Lin (European Journal of Plant Pathology, 2012)

Inhibitory effect of Salicornia europaea on the marine alga Skeletonema costatum - Dan Jiang; LingFeng Huang; YongQing Lin; LingLing Nie; SuLian Lv; TingYun Kuang; YinXin Li (Science China Life Sciences, 2012)

SIRT1 is required for long-term growth of human mesenchymal stem cells - Hong-Feng Yuan; Chao Zhai; Xin-Long Yan; Dan-Dan Zhao; Jing-Xue Wang; Quan Zeng; Lin Chen; Xue Nan; Li-Juan He; Si-Ting Li; Wen Yue; Xue-Tao Pei (Journal of Molecular Medicine, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Inhibition of Lymphoma Cell Proliferation by Peroxisomal Proliferator-Activated Receptor-γ Ligands via Wnt Signaling Pathway - Jia-Jun Liu; Xue-Jun Dai; Yan Xu; Pei-Qing Liu; Yong Zhang; Xiao-Dan Liu; Zhi-Gang Fang; Dong-Jun Lin; Ruo-Zhi Xiao; Ren-Wei Huang; He-Qing Huang (Cell Biochemistry and Biophysics, 2012)

Influences of climate change on California and Nevada regions revealed by a high-resolution dynamical downscaling study - Lin-Lin Pan; Shu-Hua Chen; Dan Cayan; Mei-Ying Lin; Quinn Hart; Ming-Hua Zhang; Yubao Liu; Jianzhong Wang (Climate Dynamics, 2011)

Tissue factor expression in ovarian cancer: implications for immunotherapy with hI-con1, a factor VII-IgGFc chimeric protein targeting tissue factor - Emiliano Cocco; Joyce Varughese; Natalia Buza; Stefania Bellone; Ken-Yu Lin; Marta Bellone; Paola Todeschini; Dan-Arin Silasi; Masoud Azodi; Peter E. Schwartz; Thomas J. Rutherford; Luisa Carrara; et al. (Clinical & Experimental Metastasis, 2011)

Optical coherence tomography: fundamental principles, instrumental designs and biomedical applications - Dan P. Popescu; Lin-P’ing Choo-Smith; Costel Flueraru; Youxin Mao; Shoude Chang; John Disano; Sherif Sherif; Michael G. Sowa (Biophysical Reviews, 2011)

Numerical study of M2 internal tide generation and propagation in the Luzon Strait - Huan Li; Dan Song; Xueen Chen; Hongbao Qian; Lin Mu; Jun Song (Acta Oceanologica Sinica, 2011)

The roles of ascorbic acid and glutathione in symptom alleviation to SA-deficient plants infected with RNA viruses - Shao-Dong Wang; Feng Zhu; Shu Yuan; Hui Yang; Fei Xu; Jing Shang; Mo-Yun Xu; Shu-Dan Jia; Zhong-Wei Zhang; Jian-Hui Wang; De-Hui Xi; Hong-Hui Lin (Planta, 2011)

The influence of genetic polymorphisms and interacting drugs on initial response to warfarin in Chinese patients with heart valve replacement - Shi-Long Zhong; Yuan Liu; Xi-Yong Yu; Dan Xu; Hong-Hong Tan; Qiu-Xiong Lin; Min Yang; Hai-Yan Lao; Shu-Guang Lin (European Journal of Clinical Pharmacology, 2011)

Effects of alginate gel on rheological properties of hair-tail (Trichiurus lepturus) surimi - Yong Xue; Xin Liu; Lili Zhang; Dan Lin; Jiachao Xu; Changhu Xue (Journal of Ocean University of China, 2011)

A novel prenylated xanthone from the stems and leaves of Calophyllum inophyllum - Zhan-Lin Li; Dan Liu; Dan-Yi Li; Hui-Ming Hua (Natural Product Research, 2011)

Establishment of a cerebral schistosomiasis experimental model in rabbits - Peng Wang; Dan Wang; Shi-Jie Chen; Ming-Can Wu; Xiang-Lin Cheng; Jun-Chuan Li; Ting-Xuan Chen; Zhan-Sheng Zhu (Neuroscience Bulletin, 2011)

Verapamil exerts biphasic modulation on phenobarbital transport across the blood–brain barrier: evidence from an in vivo and in vitro study - Dan Yao; Zhi-Hong Yang; Li Liu; Jia Li; Yun-Li Yu; Lu-Lu Zhang; Xian Pan; Xiao-Dong Liu; Lin Xie; Guang-Ji Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Characterization of Outer Membrane Proteins of Escherichia Coli in Response to Phenol Stress - Dan-Feng Zhang; Hui Li; Xiang-Min Lin; San-Ying Wang; Xuan-Xian Peng (Current Microbiology, 2011)

A broad-spectrum, efficient and nontransgenic approach to control plant viruses by application of salicylic acid and jasmonic acid - Jing Shang; De-Hui Xi; Fei Xu; Shao-Dong Wang; Sen Cao; Mo-Yun Xu; Ping-Ping Zhao; Jian-Hui Wang; Shu-Dan Jia; Zhong-Wei Zhang; Shu Yuan; Hong-Hui Lin (Planta, 2011)

Heterologous Expression of a Gibberellin 2-Oxidase Gene from Arabidopsis thaliana Enhanced the Photosynthesis Capacity in Brassica napus L. - Bo Zhou; Dan Peng; Jianzhong Lin; Xingqun Huang; Wusheng Peng; Reqing He; Ming Guo; Dongying Tang; Xiaoying Zhao; Xuanming Liu (Journal of Plant Biology, 2011)

Multi-variety bone bank in China - Dan Li; Long Bi; Guo-Lin Meng; Min Liu; Jing Jin; Yin Liu; Zhen Wang; Jian Liu; Yun-Yu Hu (Cell and Tissue Banking, 2010)

Soil organic carbon and nitrogen stocks in an age-sequence of poplar stands planted on marginal agricultural land in Northeast China - Rong Mao; De-Hui Zeng; Ya-Lin Hu; Lu-Jun Li; Dan Yang (Plant and Soil, 2010)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Biodelignification of rice straw by Phanerochaete chrysosporium in the presence of dirhamnolipid - Yun-Shan Liang; Xing-Zhong Yuan; Guang-Ming Zeng; Chen-Lu Hu; Hua Zhong; Dan-Lian Huang; Lin Tang; Jia-Jia Zhao (Biodegradation, 2010)

Application of multi-temporal ENVISAT ASAR data to agricultural area mapping in the Pearl River Delta - Dan Wang; Hui Lin; Jinsong Chen; Yuanzhi Zhang; Qiwei Zeng (International Journal of Remote Sensing, 2010)

Intratumoral as well as peritumoral lymphatic vessel invasion correlates with lymph node metastasis and unfavourable outcome in colorectal cancer - Mei Lin; Shu-Pei Ma; Hui-Zhong Lin; Ping Ji; Dan Xie; Jian-Xian Yu (Clinical & Experimental Metastasis, 2010)

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

Loss of functional diversity under land use intensification across multiple taxa - Dan F. B. Flynn; Melanie Gogol‐Prokurat; Theresa Nogeire; Nicole Molinari; Bárbara Trautman Richers; Brenda B. Lin; Nicholas Simpson; Margaret M. Mayfield; Fabrice DeClerck (Ecology Letters, 2009)
Land use intensification can greatly reduce species richness and ecosystem functioning. However, species richness determines ecosystem functioning through the diversity and values of traits of species present. Here, we analyze changes in species richness and functional diversity (FD) at varying agricultural land use intensity levels. We test hypotheses of FD responses to land use intensification in plant, bird, and mammal communities using trait data compiled for 1600+ species. To isolate changes in FD from changes in species richness we compare the FD of communities to the null expectations of FD values. In over one‐quarter of the bird and mammal communities impacted by agriculture, declines in FD were steeper than predicted by species number. In plant communities, changes in FD were indistinguishable from changes in species richness. Land use intensification can reduce the functional diversity of animal communities beyond changes in species richness alone, potentially imperiling provisioning of ecosystem services.

Global decomposition experiment shows soil animal impacts on decomposition are climate‐dependent - DIANA H. WALL; MARK A. BRADFORD; MARK G. ST. JOHN; JOHN A. TROFYMOW; VALERIE BEHAN‐PELLETIER; DAVID E. BIGNELL; J. MARK DANGERFIELD; WILLIAM J. PARTON; JOSEF RUSEK; WINFRIED VOIGT; VOLKMAR WOLTERS; HOLLEY ZADEH GARDEL; et al. (Global Change Biology, 2008)
Climate and litter quality are primary drivers of terrestrial decomposition and, based on evidence from multisite experiments at regional and global scales, are universally factored into global decomposition models. In contrast, soil animals are considered key regulators of decomposition at local scales but their role at larger scales is unresolved. Soil animals are consequently excluded from global models of organic mineralization processes. Incomplete assessment of the roles of soil animals stems from the difficulties of manipulating invertebrate animals experimentally across large geographic gradients. This is compounded by deficient or inconsistent taxonomy. We report a global decomposition experiment to assess the importance of soil animals in C mineralization, in which a common grass litter substrate was exposed to natural decomposition in either control or reduced animal treatments across 30 sites distributed from 43°S to 68°N on six continents. Animals in the mesofaunal size range were recovered from the litter by Tullgren extraction and identified to common specifications, mostly at the ordinal level. The design of the trials enabled faunal contribution to be evaluated against abiotic parameters between sites. Soil animals increase decomposition rates in temperate and wet tropical climates, but have neutral effects where temperature or moisture constrain biological activity. Our findings highlight that faunal influences on decomposition are dependent on prevailing climatic conditions. We conclude that (1) inclusion of soil animals will improve the predictive capabilities of region‐ or biome‐scale decomposition models, (2) soil animal influences on decomposition are important at the regional scale when attempting to predict global change scenarios, and (3) the statistical relationship between decomposition rates and climate, at the global scale, is robust against changes in soil faunal abundance and diversity.

A single residue mutation of 5-enoylpyruvylshikimate-3-phosphate synthase in Pseudomonas stutzeri enhances resistance to the herbicide glyphosate - Aimin Liang; Jiying Sha; Wei Lu; Ming Chen; Liang Li; Dan Jin; Yongliang Yan; Jin Wang; Shuzhen Ping; Wei Zhang; Yiding Wang; Min Lin (Biotechnology Letters, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Impact of genetic polymorphisms of leptin and TNF-α on rosiglitazone response in Chinese patients with type 2 diabetes - Hai-Ling Liu; Yang-Gen Lin; Jing Wu; Hong Sun; Zhi-Cheng Gong; Ping-Cheng Hu; Ji-Ye Yin; Wei Zhang; Dan Wang; Hong-Hao Zhou; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2008)

InlA and InlC2 of Listeria monocytogenes Serotype 4b Are Two Internalin Proteins Eliciting Humoral Immune Responses Common to Listerial Infection of Various Host Species - Wei Ling Yu; Hanhong Dan; Min Lin (Current Microbiology, 2008)

Medium optimization for enhanced production of cytosine-substituted mildiomycin analogue (MIL-C) by Streptoverticillium rimofaciens ZJU 5119 - Dan YE; Zhi-nan Xu; Pei-lin CEN (Journal of Zhejiang University-SCIENCE B, 2008)

Identification of a New Gene Encoding EPSPS with High Glyphosate Resistance from the Metagenomic Library - Dan Jin; Wei Lu; Shuzhen Ping; Wei Zhang; Jian Chen; Baoqing Dun; Ruiqiang Ma; Zhonglin Zhao; Jiying Sha; Liang Li; Zhirong Yang; Ming Chen; et al. (Current Microbiology, 2007)

Isolation and characterization of two novel colon cancer cell lines from Chinese patients - Dan-Ning Hu; Shiaw-Min Hwang; Xi-Zhang Lin; Pei-Yuh Yang; Chi-Hong Tsai; Qiang Huang; Hsin-Yi Huang; Min-Huo Hwang (In Vitro Cellular & Developmental Biology - Animal, 2007)

Real-time imaging of viable-apoptotic switch in GSNO-induced mouse thymocyte apoptosis - Dan-ying Lin; Wan-yun Ma; Shao-jin Duan; Yan Zhang; Li-ying Du (Apoptosis, 2006)

Copper‐dependent iron transport in coastal and oceanic diatoms - Maria T. Maldonado; Andrew E. Allen; Joanne S. Chong; Kevin Lin; Dan Leus; Nataliya Karpenko; Shannon L. Harris (Limnology and Oceanography, 2006)
We investigated the presence of plasmalemma‐bound copper‐containing oxidases associated with the inducible iron (Fe) transport system in two diatoms of the genus Thalassiosira . Under Fe‐limiting conditions, Thalassiosira oceanica , an oceanic isolate, was able to enzymatically oxidize inorganic Fe(II) extracellularly. This oxidase activity was dependent on copper (Cu) availability and diminished by exposure to a multi‐Cu oxidase (MCO) inhibitor. The rates of Fe uptake from ferrioxamine B by Fe‐limited T. oceanica were also dependent on Cu availability in the growth media. The effects of Cu limitation on Fe(II) oxidation and Fe uptake from ferrioxamine B were partially reversed after a short exposure to a Cu addition, indicating that the putative oxidases contain Cu. Limited physiological experiments were also performed with the coastal diatom Thalassiosira pseudonana and provided some evidence for putative Cu‐containing oxidases in the high‐affinity Fe transport system of this isolate. To support these preliminary physiological data, we searched the newly available T. pseudonan a genome for a multi‐Cu‐containing oxidase gene and, using real‐time polymerase chain reaction (PCR), quantified its expression under various Fe and Cu levels. We identified a putative MCO gene with predicted transmembrane domains and found that transcription levels of this gene were significantly elevated in Fe‐limited cells relative to Fe‐replete cells. These data collectively suggest that putative MCOs are part of the inducible Fe transport system of Fe‐limited diatoms, which act to oxidize Fe(II) following reductive dissociation of Fe(III) from strong organic complexes.

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

TransgenicLycium barbarum L. Established as HIV capsid protein expression system - Guo-Li Du; Chang-Zheng Song; Geng-Lin Zhang; Xiao-Guang Sun; Dan-Ru Liu (Plant Molecular Biology Reporter, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Oecologia, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

Association between tree-ring and needle δ13C and leaf gas exchange in Pinus halepensis under semi-arid conditions - Tamir Klein; Deborah Hemming; Tongbao Lin; José M. Grünzweig; Kadmiel Maseyk; Eyal Rotenberg; Dan Yakir (Biotechnology Letters, 2005)

Changing the way we think about global change research: scaling up in experimental ecosystem science - Barry Osmond; Gennady Ananyev; Joseph Berry; Chris Langdon; Zbigniew Kolber; Gunghui Lin; Russell Monson; Caroline Nichol; Uwe Rascher; Uli Schurr; Stan Smith; Dan Yakir (Global Change Biology, 2004)
Scaling is a naturally iterative and bi‐directional component of problem solving in ecology and in climate science. Ecosystems and climate systems are unquestionably the sum of all their parts, to the smallest imaginable scale, in genomic processes or in the laws of fluid dynamics. However, in the process of scaling‐up, for practical purposes thewhole usually has to be construed as a good deal less than this. This essay demonstrates how controlled large‐scale experiments can be used to deduce key mechanisms and thereby reduce much of the detail needed for the process of scaling‐up. Collection of the relevant experimental evidence depends on controlling the environment and complexity of experiments, and on applications of technologies that report on, and integrate, small‐scale processes. As the role of biological feedbacks in the behavior of climate systems is better appreciated, so the need grows for experimentally based understanding of ecosystem processes. We argue that we cannot continue as we are doing, simply observing the progress of the greenhouse gas‐driven experiment in global change, and modeling its future outcomes. We have to change the way we think about climate system and ecosystem science, and in the process move to experimental modes at larger scales than previously thought achievable.

Identification of a Second Flagellin Gene and Functional Characterization of a ? 70 -like Promoter Upstream of a Leptospira borgpetersenii flaB Gene - Min Lin; Hanhong Dan; Yijing Li (Current Microbiology, 2004)

Regional carrying capacity: case studies of Bohai Rim area - Yu Dan-lin; Mao Han-ying (Journal of Geographical Sciences, 2002)